Study on coalbed methane desorption induced by water infiltration in closed mines - Junbo Zhang; Biming Shi; Yuehui Liang; Qijun Han; Yongxin Sun; Shihao Chen; Ximao Zhai; Ting Zong; Xuanyu Li; Taojie Zhang (Fuel, 2027)

RLX-2 ameliorates post-traumatic joint contracture by inhibiting the cGAS-STING signaling pathway - Jian-Jun Chen; Quan-Bing Zhang; Yan Wang; Chen Chen; Yi Liu; Zun-Yu Du; Xiu-Li Kan; Han Xiao; Xue-Ming Li; Run Zhang; De-Ting Zhu; Xian-Liang Rao; et al. (Tissue and Cell, 2027)

Prohexadione-calcium inhibits fruit russeting formation by increasing the wax accumulation in 'Hongdan' apple - Xiaolong Xu; Zhongkang Wang; Yimeng Shang; Ting Zhang; Tingting Han; Yizhou Chen; Hongmin Hou; Jihua Xu; Xiao Liang; Min Chen; Yugang Zhang; Shenghui Jiang (Postharvest Biology and Technology, 2027)

Prevalence of Klebsiella pneumoniae in raw milk and biocontrol potential of phage vB_Kpn_18-1 - Ting Qin; Xinyan Yao; Dai Peng; Chaoxiang Jia; Linlin Huang; Yingqian Han; Yanbin Yang; Yang Liu; Guoyu Yang; Juan Geng; Yueying Wang; Heping Li (International Dairy Journal, 2026)

Thermo-mechanical behavior of medium sandstone under cryogenic conditions: Role of unfrozen water content - Bo Liu; Jie Zhang; Yanhui Han; Ting Li; Lulu He; Lei Gao; Shuhui Li (Cold Regions Science and Technology, 2026)

Correction to: Spil mediated sEH overexpression contributes to the senescence of alveolar epithelial cells during pulmonary fibrosis in mice - Chen-Yu Zhang; Wen-Jing Zhong; Jin-Tong Yang; Yan-Ling Qiu; Han-Xi Sha; An-Jun Ou; Yu-Biao Liu; Xiao-Ting Huang; Yong Zhou; Jia-Xi Duan; Cha-Xiang Guan (Journal of Molecular Medicine, 2026)

Fibrotic microRNAs in the suppression of HSC activation and ECM deposition to facilitate the regression of hepatic fibrosis in zebrafish - Yu-Heng Lai; Mu-Kuang He; Chung-Tsui Huang; Han-Yu Tseng; Tzu-Ching Lin; Ting-Yu Yang; Semon Wu; Guor Mour Her (Journal of Molecular Medicine, 2026)
During liver injury, early pathological changes may go unnoticed, delaying the diagnosis until the disease has advanced to stages such as fibrosis, cirrhosis, or hepatocellular carcinoma. Hepatic fibrosis is a sign of long-term liver injury that leads toward permanent liver damage. It involves the buildup of too much extracellular matrix (ECM) and is activated by hepatic stellate cells (HSCs). The transforming growth factor-β1 (TGF-β1)/SMAD pathway is central to this process, which shows great potential for therapeutic strategies. Therefore, we investigated the therapeutic potential of microRNA (miRNA)-mediated regulation of fibrogenesis by using zebrafish models. A group of fibrosis-related miRNAs was identified and used to generate transgenic zebrafish lines. Fibrosis was induced via doxycycline (DOX)-controlled overexpression of TGF-β1a, and the antifibrotic efficacy of miRNAs was evaluated. Quantitative real-time PCR showed a marked downregulation of the target miRNAs, accompanied by decreased expression of fibrotic markers. Next, we confirmed that TGF-β1a, GREM1, and α-SMA protein levels were decreasing. Histological staining revealed improved liver structure and diminished collagen deposition. These findings indicate that through manipulating the miRNA expressions, we can effectively disrupt TGF-β-induced fibrogenesis, inactivate HSC, inhibit ECM remodeling, and attenuate liver fibrosis, and highlight the potential of miRNA-based therapeutic strategies for early intervention in liver disease. Key messages Establishment of an in vivo model for developing an inducible miRNA expression system in zebrafish. Predicting and evaluating targeted miRNAs that attenuate TGF-β-induced hepatic fibrosis. Elucidate the potential mechanism for fibrosis that may be a strategy for future therapies. Graphical Abstract MicroRNA-mediated modulation attenuates hepatic fibrosis by coordinately suppressing the TGF-β/SMAD signaling pathway, hepatic stellate cell activation, and extracellular matrix deposition. Protein-level validation confirms reduced phosphorylation of Smad2 and decreased expression of key fibrotic markers, including α-SMA, collagen I, and fibronectin. These findings highlight a multi-target regulatory mechanism through which miRNAs exert antifibrotic effects at the systems level.

Spil-mediated sEH overexpression contributes to the senescence of alveolar epithelial cells during pulmonary fibrosis in mice - Chen-Yu Zhang; Wen-Jing Zhong; Jin-Tong Yang; Yan-Ling Qiu; Han-Xi Sha; An-Jun Ou; Yu-Biao Liu; Xiao-Ting Huang; Yong Zhou; Jia-Xi Duan; Cha-Xiang Guan (Journal of Molecular Medicine, 2026)

Role of chaihu yujin decoction in cholecystitis: a systematic investigation integrating multi-omics and experimental validation - Feng Xu; Jia-Han Xu; Xiao-Min Chen; Kai-Li Mao; Jie Hu; Hong-Liang Zheng; Huan-Huan Xia; Zhi-Hui Zhang; Qiu-Ting Lin (Functional & Integrative Genomics, 2026)

Whole-genome and Comparative Genomic Analysis Reveal the Biocontrol and Plant Growth-Promoting Potential of Bacillus velezensis JN.Y2 Against Oat Anthracnose - Wei Quan; Ting Zhang; Chen-Lu Liu; Shao-xuan Shi; Xi-xi Zhang; Ke-han Liu; Chun-Yang Wang; Ming-min Zhao; Bao-Zhu Dong; Hong-You Zhou (Functional & Integrative Genomics, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

XsiAMT1.1a was identified as a novel ammonium uptake functional gene and its overexpression combined with GA4 application significantly increased yield in Arabidopsis thaliana - Xiao Han; Zhao-Hua Gong; Jie Cao; Li-Na Ye; Yuan Cheng; Yu-Xuan Du; Ting-Ting Zhao; Hai-Long Wu; Chang Zhang (Plant Science, 2026)

Saebias A–G, eudesmane sesquiterpenes from Salvia plebeia with potential for Alzheimer's disease prevention via anti-neuroinflammatory and neuroprotective effects - Xiao-Die Shu; Han-Fei Liu; Yu-Qiong Liao; Wan-Jun Pu; Ting Zhao; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2026)

Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; Dave W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Persistent carbon composition converges across vegetated and unvegetated coastal soils despite contrasting stabilization pathways - Yuan Li; Joeri Kaal; Chuancheng Fu; Dongdong Zhang; Peter I. Macreadie; Ting Wang; Lin Zeng; Feilong Hu; Guangxuan Han; Yongming Luo (Water Research, 2026)

Targeting viral Fe-S clusters with TEMPOL confers broad-spectrum anti-coronavirus activity - Leyu Hu; Lexi Gao; Xingwei Fu; Zesheng Rong; Yue Cheng; Yuhan Hou; Lu Han; Xin Ran; Guiwen Guan; Ting Zhou; Lingling Chang; Xiaomin Zhao; et al. (Veterinary Microbiology, 2026)

Integrating optical remote sensing and airborne gamma for lithological classification using an artificial neural network: A case study in Wuliji, North China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Mechanisms of high-humidity hot air impingement blanching (HHAIB) on microbial counts, functional properties, phenolic profile transformation, and volatile compounds in celery stalks (Apium graveolens L.) - You-Sheng Shi; Yu-Ting Ding; Jun Zhang; Jing-Shou Zhang; Shi-Han Yu; Fan Yang; Wei-Peng Zhang; Feng-Kui Xiong; Ming-Qiang Xu; Gang Shen; Wei-Qiao Lv; Hong-Wei Xiao (Food Research International, 2026)

Multifunctional EC-SERS platforms for food safety: A comprehensive review of strategies for sensitive and selective pesticide detection - Ruiming Wen; Ting Zhang; Yu Han; Wei Yang; Yang Zhou; Sihang Zhang; Long Wu (Food Research International, 2026)

Enhanced stability of CH3NH3PbBr3 quantum dots for electrochemiluminescence detection of saxitoxin - Yu Han; Ting Zhang; Rui Kang; Xin Gao; Jiawei Liu; Qingchun Yin; Hongmei Cao; Long Wu (Food Chemistry, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Synergizing conventional and unconventional water to promote water resources spatial equilibrium: An integrated multi-system compatibility evaluation framework - Yufei Han; Fengping Wu; Lina Zhang; Wei Wang; Yu Wang; Chuanyi Wang; Weichao Zhao; Ting Cheng; Xianbin Zeng (Environmental Research, 2026)

Immune response as a modifier linking phthalate exposure to lung function decline: Results from a longitudinal study - Wei-Chi Wang; Yuan-Ting C. Lo; Hsiu-Ying Ku; Hsu-Kai Huang; You-Zhen Chen; Wei-Yu Lin; Han-Bin Huang (Environmental Pollution, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

Organic matter in Martian radiation environment: Occurrence, evolutionary pathways, influence factors, characterization techniques, and further perspectives - Zhongyi Liu; Peixin Du; Meng Han; Enming Ju; David C. Fernández-Remolar; Ting Huang; Shaolin Li; Peng Yuan (Earth-Science Reviews, 2026)

Glycocalyx-mimetic ionotronic silk films for immunoregulatory infected wound repair and wearable motion sensing - Zi-Xian Dang; Ke Ma; Han Zhang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Amine-functionalized oyster shell waste for hexavalent chromium removal and phosphate recovery - Kamonchanok Huangmee; Liang-Ching Hsu; Guan-Ru Liu; Pei-Chieh Tseng; Heng Yi Teah; Yu-Min Tzou; Nhu Anh Thi Than; Han-Yu Hsueh; Yu-Ting Liu (Bioresource Technology, 2026)

A spatiotemporal framework for GNSS-based rainfall nowcasting with FluxFormer and attention-based graph neural networks - Xiangyang Han; Xianwei Wang; Jinhua Wu; Yuli Wang; Joseph Awange; Bo Zhang; Ting On Chan (GPS Solutions, 2026)

Removal efficiency and mechanisms of natural mineral materials for bacteriophages MS2 and ΦX174 in aqueous environments - Ying Song; Ya-ting Wang; Ying Han; Rong-xuan Xu; Yang Wang; Shuang Xu; Ming-da Liu (Journal of Contaminant Hydrology, 2026)

Cadmium induced ferroptosis of TM4 cells through PERK-ATF4-CHOP signaling pathway - Xuan Li; Juan Dai; Jiaoyang Wei; Yan He; Yue Han; Ting Zhou; Rui Li; Ling Zhang; Yuqin Shi (Reproductive Toxicology, 2026)

Waste mop cloth recycling enables rapid, high-throughput removal of viscous winter oil spills - Min Zhang; Ching-Wen Lou; Kaifang Xie; Hengshu Zhou; Jia-Horng Lin; Guangting Han; Que Chen; Ting Dong (Journal of Hazardous Materials, 2026)

Heat stress modulates the size-dependent effects of aminated polystyrene particles on a marine diatom - Ting-Ting Xu; Zhen-Liang Li; Zhi-Yan Wang; Yu-Han Xie; Heng-Xiang Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2026)

Integrative transcriptomic and functional analysis reveals fatty acyl elongases involved in sex pheromone biosynthesis in rice leaffolder, Cnaphalocrocis medinalis (Lepidoptera: Pyraloidea) - Ling-Yue Chen; Xiao-Yang Lin; Ke-Xin Wang; Xiao Feng; Hong-Ting Tang; Shuang-Lin Dong; Ling-Ling Zheng; Yi-Han Xia (Insect Biochemistry and Molecular Biology, 2026)

Fractal characteristics of roughness in inclined self-supported fractures of shale with embedding multi-layer proppants - Han Cao; Ziyi Zhang; Ling Zhu; Junsheng Zhu; Yan Lv; Ting Bao (Geomechanics for Energy and the Environment, 2026)

Personality and body condition variation in a resident passerine bird under heavy metal pollution: insights from an industrial city in Northwestern China - Han Hai; Fuqiang Zhao; Ying Yang; Ting Bai; Wenzhi Yang (Environmental Research, 2026)

A one-stone-three-birds strategy: Manipulating sodiation depth of SnTe anode enabling fast ion conduction, shuttle avoidance, and sodium replenishment for durable sodium-ion batteries - Zhiming Jia; Guoping Liu; Xu Han; Gangyong Zhou; Haihui chen; Chunjiang Jin; Ting Liu; Lingfeng Xu; Renyun Kuang; Changwang Pan; Shengping Dai; Dingwa Zhang; et al. (Chemical Engineering Journal, 2026)

Condensate-boosted SOD/CAT-mimetic nanozyme reactivity for antioxidant therapy of wear particle-induced periprosthetic osteolysis - Han Zhang; Ke Ma; Zi-Xian Dang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Substrate-mediated spatial cooperation in Bacillus-Saccharomyces consortia enhance starch hydrolysis and flavor formation during solid-state fermentation - Liming Wu; Yitong Ge; Zichang Peng; Zinuan Han; Jiaqi Bai; Ting Lan; Zhenchao Zhang; Fuhao Liang; Xiaole Xia (Bioresource Technology, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Taixinan contourite and mixed systems on the Gaoping Slope: Influence of intermediate water masses on the Taixinan canyon group - Zhi Lin Ng; Shan Liu; Kunwen Luo; Xinyu Xue; Zhixuan Lin; Tzu-Ting Chen; Ho-Han Hsu; Ming Su (Quaternary Science Reviews, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Early Oligocene paleoclimatic reconstruction of the Qaidam Basin (northern Qinghai-Xizang Plateau): Insights from sporopollen and n-alkane records - Fang Han; Ting-Lu Yang; Yu Liang; Ke-Xin Zhang; Jun-Liang Ji; Bo-Wen Song (Palaeoworld, 2026)

Axially coordinated cobalt single-atom membrane enabling electron-transfer–singlet oxygen synergy for highly selective micropollutant oxidation - Ting Liu; Zuoming Fan; Mingrui He; Mengfei Wang; Yulun He; Bo Han; Jun Ma (Journal of Hazardous Materials, 2026)

Associations between prenatal exposure to indoor air pollution and ambient particulate matter with infant growth - Jinlang Lyu; Tiantian Li; Shuang Zhou; Xin Yuan; Zheng Bao; Na Han; Gongbo Chen; Yuelong Ji; Qin Li; Jue Liu; Hui Wang; Jianlin Hu; et al. (Journal of Environmental Sciences, 2026)

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Disentangling the source and loss effects of ship-related HONO on coastal ozone over China - Liliang Chen; Yanhui Liu; Ting Wu; Liyao Guo; Xinhua Wang; Jia Xu; Shaojie Song; Peng Wang; Zhipeng Bai; Bin Han (Environmental Pollution, 2026)

Evolution of multiscale pore structure and microscopic flow behavior in shales subject to fluid-rock interaction - Jianchao Cai; Xuanzhe Xia; Derek Elsworth; Yuxuan Xia; Han Wang; Ting Chen; Hongjian Zhu (Engineering Geology, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

A Sea State Estimation and Uncertainty Awareness Model Integrating Multi-Scale Convolution and DropKey-Transformer - Ting Cui; Runze Mao; Xinyu Guo; Peihua Han; Houxiang Zhang (Journal of Marine Science and Engineering, 2026)
Accurate sea state estimation is of great significance to marine engineering safety and disaster prevention and mitigation. This paper proposes a new sea state estimation architecture integrating multi-scale 1D-CNN, transformer encoder, and the MC-DropKey mechanism. First, the front-end multi-scale 1D-CNN is used in sequence modeling to extract high-quality local features. Then, the back-end transformer encoder is used to capture global long-range temporal dependencies. In addition, the MC-DropKey mechanism is introduced. It achieves dynamic uncertainty quantification while maintaining high-precision estimation. Comprehensive comparative and ablation experiments show that the proposed model significantly outperforms the baseline models in wave height and wave direction estimation tasks, achieving the lowest MAE of 0.117 m and CAE of 5.212°. Moreover, the uncertainty intervals output by the model effectively quantify estimation confidence, reaching a 96.67% prediction interval coverage probability. The obtained results provide strong technical support for scientific scheduling and decision-making in complex marine environments.

Microbiome immune crosstalk in Sjögren’s syndrome: mechanistic insights and translational perspectives - Xiang-Yu Qi; Meng-Yuan Wang; Tian-Chi Wei; Fu-Biao Shao; Shu-Han Liu; Ding Han; Jing-Wen Cheng; Yun-He Zhao; Lei Shi; Jing Luo; Ting Cheng; Sheng-Xiao Zhang (Immunologic Research, 2026)

NPY-Y2R driven neuroimmune signaling as a potential therapeutic target for trigeminal neuralgia: clinical and experimental evidence - Zi-Le He; Chao Xu; Qi-Fan Yang; Cong-Zhou Han; Ting Wu; Yu-Qing Xu; Yun-Ze Liu; Liang-Yu Ni; Si-Qi Jia; Tang-Yu Zhang; Yun Wang; Yi Feng (Science Bulletin, 2026)

Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

Utilizing machine learning to accelerate the identification and quantification of plastics or microplastics via only their basic elemental compositions - Guiqing Han; Zejian Ai; Weijin Zhang; Yige Yuan; Ting Xiong; Hao Zhan; Lijian Leng; Hailong Li (Journal of Hazardous Materials, 2026)

Economic and environmental trade-offs in circular food systems: Toward cleaner agricultural production and responsible consumption - Zhan Li; Xinping Han; Ting Zhang (Journal of Cleaner Production, 2026)

Novel insights into the legacy effects of NBPT on fungal interactions and pathogenic fungal reduction in agricultural soils - Tikun Guan; Jilin Lei; Huangwei Liu; Jiarui Li; Ting Yang; Qi Wang; Han Wu; Meng Wang; Weizheng Shu; Rui Liu (Journal of Environmental Sciences, 2026)

Changes in flavor profiles and microbial community diversity throughout rice wine fermentation with Rhizopus oryzae from different sources - Ting Tong; Jing-Rong Hu; Zhen-Jia Li; Zi-Zhen Qin; Cai-Hua Shi; Han-Cheng Wang (International Journal of Food Microbiology, 2026)

Aggregated-state remodeling of quinoa protein gels by thermal pretreatment and transglutaminase - Zhen-Yang Quan; Ting-Ting Ji; Jia-Han Liu; Dong-Ping Zeng; Xiu-Nan Zhang; Ying Chen; Jian-Ya Qian; Liang Zhang (Food Chemistry, 2026)

Corrigendum to “Effects of germplasm type and geographic origin on juice quality of sea buckthorn: A comparative study of physicochemical properties, functional activities, and flavor chemistry” [Food Chem. 511 (2026) 148850] - Jingyi Ren; Ting Liu; Saige Zhang; Xingnan Wang; Wenzhi Lei; Yike Han; Guohao Tang; Mengtong Wang; Xiaoning Tu; Bin Zhang; Guangquan Liu; Zhenpeng Gao (Food Chemistry, 2026)

Covalent organic frameworks membrane with gradient hydrophilic channel for moisture-enabled electric generation - Jun Zhang; Jing-Dong Feng; Ruo-Meng Zhu; Yong Liu; Yu-Ou He; Yu-Ting Que; Shuai Geng; Wang-Kang Han; Zhi-Guo Gu (Chemical Engineering Journal, 2026)

Correction: Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Mitophagy activation for jawbone radiation injury therapy via angiogenesis/osteogenesis-active nanozymes - Tianxiao Wang; Weihua Shao; Ting Zhou; Yuchao Li; Ran Qin; Ziyu Chen; Jikang Cao; Xinyu Hu; Jingxuan Cang; Chang Sun; Yuli Wang; Huijun Jiang; et al. (Science China Life Sciences, 2026)

Hydroxyapatite nanoparticles improve vitrified bovine MII oocyte developmental competence by reducing ultrastructural damage and modulating gene expression - Xiao-Xia Li; Yi-Hang Wang; Jun Wang; Shi-Yu Zhang; Jia-Hao Zhang; Shi-Han Zhao; Qi Yan; Ping-Hua Cao; Zi-Qiang Zhang; Chen Zhou; Zhen Zhang; Qiao-Ting Shi; et al. (Animal Reproduction Science, 2026)

A label-free magnetic bead affinity approach for direct target identification of herbal extract: Ganoderma lucidum as a case - Han Li; Bo Peng; Bo Li; Ting Li; Zihan Zhu; Pengfei Tu; Jun Li; Yuelin Song (Analytica Chimica Acta, 2026)

Straw return coupled with subsoiling tillage reduces N₂O emissions and increases nitrogen content under long-term (12 years) trial in a coastal saline cotton field - Han Wang; Zhitao Liu; Qiyuan Guo; Lunxiao Shang; Longhao Zhou; Jiaxue Zhao; Ting Huang; Xiaoyu Li; Chenxi Shi; Baltaevich Ahmedov Miraziz; Xianliang Song; Xiaopei Zhang; et al. (Agriculture, Ecosystems & Environment, 2026)

From the neotropics to East Asia: first population of the Rio Grande cichlid (Herichthys cyanoguttatus) reported in Taiwan - Yu-Hsiang Lin; Jhao-Cian Hou; Yu-San Han; Yen-Ting Lin (Biological Invasions, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Potential Causes of Anti‐Phase Summer Precipitation Variability Between the Middle and Lower Reaches of the Yangtze River - Yuwei Zhou; Ge Liu; Xiaolu Yan; Sulan Nan; Ting Zhang; Yinghan Sang; Xuefeng Han; Yuhan Feng; Hancheng Zou (International Journal of Climatology, 2026)
Summer precipitation in the middle and lower reaches of the Yangtze River generally shows synchronous variability and is thus extensively studied as a unified climatic region. However, out‐of‐phase variations occur between the middle and lower reaches in some years. This study investigates the mechanisms of the positive middle Yangtze River precipitation (MYRP)–negative lower Yangtze River precipitation (LYRP) pattern from the perspectives of atmospheric circulation and land‐ocean thermal anomalies. The results suggest that a non‐canonical Silk Road Pattern (SRP) teleconnection in the upper troposphere, coupled with a mid‐to‐lower tropospheric anomalous anticyclone over Northeast Asia and a weakened western Pacific subtropical high (WPSH), contributes to this precipitation pattern. Further analysis reveals that colder‐than‐normal land thermal anomalies in the Greater Caucasus Mountains and the northeastern Tibetan Plateau, as well as warmer‐than‐normal sea surface temperature anomalies (SSTAs) in the Sea of Japan, may help maintain the SRP‐like Rossby wave train (SLWT), therefore influencing the positive MYRP–negative LYRP pattern. Linear baroclinic model sensitivity experiments further support the identified thermal anomalies can excite and maintain the SLWT. Given that the SLWT differs to some extent from the classical SRP in both wave source and downstream structure, this study also proposes a SLWT index based on 200‐hPa vorticity anomalies. This index effectively captures both the spatial structure of the SLWT and its link with out‐of‐phase precipitation anomalies between the middle and lower reaches of the Yangtze River and may serve as a potential indicator for the occurrence probability of the positive MYRP–negative LYRP pattern. These findings may improve our understanding of regional precipitation mechanisms in the Yangtze River basin, thereby providing a scientific basis for improved disaster prevention and mitigation strategies.

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Research on the Highly Efficient and Low-Dose Improvement of Alcohol-Induced Liver Injury by High-Selenium-Content Modified Lycium barbarum Polysaccharides - Shuangzhe Mao; Xin Zhang; Lulu Wei; Han Zhang; Abo Li; Mengmeng Sun; Jiao Feng; Ting Ren; Yiting Huang; Xiaoying Liu; Zhifeng Zhang; Zhihui Zhao; et al. (Biological Trace Element Research, 2026)

An integrated geochemical and isotopic framework for nitrate source apportionment in a shallow coastal aquifer under multiple environmental pressures - Sa Xiao; Ya Wang; Tao Gu; Xiaoli Yang; Ting Han; Chaoan Mai (Water Research, 2026)

Quorum sensing in fermented food microbiomes: Regulatory circuits, functional roles, practical applications, and future perspectives for intelligent fermentation - Liming Wu; Zinuan Han; Shicong Liang; Fuhao Liang; Ting Lan; Zhenchao Zhang; Xiaole Xia (Trends in Food Science & Technology, 2026)

High-resolution temporal biogeochemical variations in a seagrass-coral cohabitate ecosystem: day-night, rain, and coral spawning - Huei-Ting Lin; Yu-Chen Yen; Chih-Chiang Hsieh; Hirofumi Watanabe; Yiing-Jang Yang; Hui-Yu Wang; Han Song Ong; Shi-Ming Chen; Pei-Ling Wang (Science of The Total Environment, 2026)

Endothelial FAM171A2 is required for maintaining autophagy flux and blood–brain barrier integrity - Si-Da Han; Ning Ding; Jia-hui Huang; Yi-Wei Feng; Kai-Min Wu; Shi-Dong Chen; Qiang Dong; Mei Cui; Ting-ting Wang; Peng Yuan; Jin-Tai Yu (Science Bulletin, 2026)

Impact of environmental factors on the distribution characteristics of phytoplankton functional groups in Beijing - Linlin Qin; Xu Han; Ting Zhu; Yixuan Zhang; Na Cui; Yuepeng Liu; Wenyan Liang (Protist, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Evolution of sand wave migration and morphodynamic changes in the Taiwan Strait - Yin-Hsuan Tiffany Liao; Ho-Han Hsu; Tzu-Ting Chen; Jyun-Nai Wu; Sung-Ping Chang; Arif Mirza; Song-Chuen Chen; Liwen Chen (Marine Geology, 2026)

Recent advances in nanosensors for food safety: Principles, applications and future perspectives - Sujia Jiao; Ting Zhang; Jiawei Liu; Yu Han; Qingchun Yin; Jing Wei; Long Wu (Food Control, 2026)

Modulating the strength-bulk balance in bamboo chemical thermomechanical pulp via lignin-carbohydrate interactions: Constructing carbon‑carbon and hydrogen bonds - Jian Jiao; Xiu Wang; Ting Jiao; Shanming Han; Hongbin Li; Yongjun Deng; Guigan Fang; Chen Su (Chemical Engineering Journal, 2026)

Self-powered photosynthetic microalgae hydrogel for bioelectric–oxygen–hydrogen–ATP and vesicular Nanomedicine–synergized osteoarthritis mitigation - Yu-Wen Tseng; Pei-Wei Weng; Hsien-Tsung Lu; Chia-Hung Liu; Yan-Ting Chen; Shen-Han Wu; Hieu Trung Nguyen; Andrew E.-Y. Chuang (Chemical Engineering Journal, 2026)

A ultralong-life and high-capacity Mg/Na hybrid-ion battery using four-leaf clover-shaped CuSe2/(Cu, Co)Se2 cathode pairing with triglyme electrolyte - Ting Zhou; Tianli Han; Fengming Ma; Cheng Wang; Yunmiao Fan; Xuehui Wang; Haojun Xu; Jiawei Long; Jinjin Li; Huigang Zhang; Jinyun Liu (Chemical Engineering Journal, 2026)

Visible-light activation of H2O2 by red-mud/biochar: 1O2 pathway for efficient tetracycline degradation - Yi Han; Ting Shi; Shuai Yang; Mingming Wu; Hongcheng Gao; Dejin Wang; Emeka E. Oguzie; Changyong Zhang (ENGINEERING Environment, 2026)

KDM3A Modulates Trastuzumab Resistance in HER2− Positive Breast Cancer Cells via the PI3K/AKT/ERK Pathway - Yuanxing Han; Jiayi Guo; Ting Yang; Xuewen Liu; Honghuo Yan; Yuanzhang Li; Juan Yao (Biochemical Genetics, 2026)

FTCSEM—A FORTRAN-based parallelized 1D CSEM forward and inversion program for arbitrary source-receiver geometry - Wei-ying Chen; Si-xu Han; Wan-ting Song; Yu-lian Zhu; Zheng Liu (Applied Geophysics, 2026)

Targeting programmed cell death: a novel therapeutic paradigm for cancer based on mode-of-death classification - Xi Qiao; Ting Ye; Tinggai Wu; Xu Han; Tiantian Sun; Haiqiang Wang; Junru Jia; Yuanyuan Dai; Ruohan Yun; Shuo Jiang; Yuming Qin; Zhenzhen Liu; et al. (Apoptosis, 2026)

Fast-response Phosphorescence Sensor for Dissolved Oxygen Detection Based on PtOEP/TiO2/CB@PFFE Sensing Film - Jia Xiao; Minmin Han; Ting Li; Baohua Yue; Liuming Yan (Journal of Fluorescence, 2026)

Nociceptive stimulation activates NR2B-mediated DISC1/GSK-3β and ERK/CREB signaling alleviates sevoflurane induced neurotoxicity in neonatal rats - Ting-Ting Yang; Zi-Wen Guo; Yu Peng; Wei Yu; Zhen-Qing Han; Guang-Qiang Gao; Chuan-Feng Fang; Hong Tian; Si-Hua Qi; Shu-Jun Zhang; Jia-Ren Liu (NeuroToxicology, 2026)

Food protein-protein interaction systems guided by aggregation kinetics: Trans-scale breakthroughs from kinetic regulation to functional customization - Zhiyuan Zheng; Qiri Mu; Duo Bai; Yuchao Han; Jingbo Liu; Ting Zhang; Renzhao Zhang; Zhaohui Yan; Xuanting Liu (Food Research International, 2026)

Effects of germplasm type and geographic origin on juice quality of sea buckthorn: A comparative study of physicochemical properties, functional activities, and flavor chemistry - Jingyi Ren; Ting Liu; Saige Zhang; Xingnan Wang; Wenzhi Lei; Yike Han; Guohao Tang; Mengtong Wang; Xiaoning Tu; Bin Zhang; Guangquan Liu; Zhenpeng Gao (Food Chemistry, 2026)

Modifying structural properties of rice bran protein by protein-glutaminase deamidation to fabricate a high-performance oleogelator - Lu Zhang; Xinyi Han; Jianyu Wang; Ting Wang; Ruiqiang Yang; Ganghua Li; Chong Zhang (Food Hydrocolloids, 2026)

Hydrogen sulfide maintains banana postharvest quality by antagonizing ethylene and enhancing antioxidant properties in Musa nana Lour - Xue-Ting Cheng; Yan-Hong Li; Yun Ge; Zhuo Han; Yi-Ang Feng; Ying-Zhi Zhang; Kang-Di Hu; Gai-Fang Yao; Pedro García-Caparros; Hua Zhang (Food Control, 2026)

Sustainable and durable pure water-fed CO2 electrolysis through cathode cation engineering - Ting-Wei Huang; Tsung-Han Tsai; Kuan-Hung Kuo; Jou-An Hsu; Ding-Huei Tsai; Wei-Ting Tu; Chang-An Chen; Hsin-Liang Kuo; Ming-Kang Tsai; Yung-Tin (Frank) Pan (Chemical Engineering Journal, 2026)

Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Microneedle-mediated delivery of hydroxypropyl-β-cyclodextrin-encapsulated Angelica sinensis (Danggui) essential oil for acne treatment: efficacy and mechanisms - Xiaoli Liu; Xiaojuan Li; Weijun He; Xiaoyu Han; Ting Xiao; Shiqi Guo; Yujie Jia; Liqun Lin; Ming Yang; Li Wang; Yuehong Xu (Drug Delivery and Translational Research, 2026)

Isolation of Rhizospheric Fungi from Crocus sativus L. Rhizosphere and their Effects on Host-Growth Promotion - Jing-Chao Xu; Xing-Guang Xie; Xin-Zhu Yu; Zi-hao Zhu; Xue-Wen Bi; Kun-miao Feng; Ying-jie Lu; Khalid Rahman; Bo Zhu; Lu-ping Qin; Zhen-zhen Zhang; Ting Han (Current Microbiology, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Porosity Inversion Using a Joint Dictionary and Spatial Structure with Simultaneous Constraints: An Application to Carbonate Fractured-Vuggy Reservoirs - Feng Ma; Ming Lei; Fei Xu; Han-peng Cai; Yu Liu; Ting Cheng; Yao-jun Wang; Guang-min Hu (Applied Geophysics, 2026)

New fossil moths (Lepidoptera: Micropterigidae) in middle Cretaceous Kachin amber from Myanmar - Ning Han; Xin-Ru Luo; Jia-Jia Wang; Chungkun Shih; Wei-Ting Zhang; Dong Ren (Palaeoworld, 2026)

Chronology and geochemistry of radiolarian chert from Zhongba, southern Xizang (Tibet): Implications for the evolution of the Neo-Tethys Ocean - Han Yan; Han-Ting Zhong; Zong-Qi Lin; Chen-Yu Wang; Ling-Xue Gao; Cai Wang; Ming-Cai Hou (Palaeoworld, 2026)

Thermochemical conversion of spent coffee grounds into dissolved organic matter for Fenton-like degradation - Kuan-Ting Lee; Pei-Jia Han (Journal of Environmental Chemical Engineering, 2026)

CO2 adsorption and separation from flue gas using a halogenated covalent triazine-based framework - Yu-Ting Han; Ying Zhang; Dong-Liang Zhong; Ke-Xin Yao; Jian-Jian Wang; Jin Yan (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

Basic amino acid-enriched egg white peptides for efficient repair of intestinal injury: Preparation, application, and mechanism analysis - Qingwen Han; Jingbo Liu; Shengrao Li; Mohan Zhang; Weiyi Ma; Yanguo Huan; Dongfang Wang; Yongqi Yu; Ting Zhang; Siwen Lyu (Food Research International, 2026)

Modulation of gut microbiota by tangerine peel polysaccharide: A promising strategy for obesity management via acetic acid production - Chao-Yue Kong; Zhan-Ming Li; Bing Han; Yu-Qin Mao; Hui-Ling Chen; Jia-Ting Huang; Li-Shun Wang (Food Research International, 2026)

Deciphering the mechanisms underlying cadmium tolerance in the endophytic fungus Trichoderma atroviride D16 - Xue-Wen Bi; Xing-Guang Xie; Wen-Jing Zhang; Rui-Di Zhang; Khalid Rahman; Xin-Zhu Yu; Cun-Yu Fan; Shu-Lang Ding; Yu-Qing Peng; Ting Han (Fungal Biology, 2026)

Biomimetic fabrication of cultured meat using 3D-printed microgrooved and meshed scaffolds with alternating muscle and adipose layers - Chi-Han Li; Chih-Ying Chi; Feng-Huei Lin; Chia-Ting Chang; I-Hsuan Yang (Food Hydrocolloids, 2026)

Using ethylene combined with green manuring to enhance rice productivity, economic benefit, and energy efficiency in double-rice paddy field - Jinxin Sun; Guopeng Zhou; Danna Chang; Rui Liu; Han Liu; Zhengbo Ma; Ting Liang; Jia Liu; Chunqin Zou; Weidong Cao (Field Crops Research, 2026)

A study on the association between early-pregnancy hair metal levels and gestational diabetes mellitus - Feng Tang; Jun Guo; Li-An-Sheng Wu; Xiao-Yuan Fan; Han-Wen Zhang; Noora Kartiosuo; Boris Novakovic; Ting-Li Han; Hua Zhang; Yin-Yin Xia; Philip Baker; Richard Saffery (Environmental Pollution, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

Hydroxypropyl cellulose-based photonic actuators coupling structural color and programmable deformation - Ting Wang; Yifeng Wang; Chunyu Ji; Qian Ding; Han Yang (Carbohydrate Polymers, 2026)

Valorization of oily sludge with coal gasification slag via catalytic pyrolysis - Lei Han; Hai-Jie Hu; Jia-Xuan Liu; Tao Yu; Jin-Ling Li; Lan-Ting Ma; Cheng-Tun Qu; Zhong-Wen Liu (Bioresource Technology, 2026)

The characteristics of the atmospheric boundary layer structure over the Cosmonaut Sea and Bellinsgauzen Sea during summer 2021 - Ting Qiu; Qinghua Yang; Bo Han; Xingya Xi; Zhongya Cai; Shijie Peng; Changwei Liu (Atmospheric Research, 2026)

Operational Performance of Aquavoltaics Under Different Stakeholder Cooperation Schemes: Evidence from White Shrimp Aquaculture in Taiwan - Bo-Ying Chen; Po-Lin Huang; Yen-Lung Hou; Farok Afero; Szu-Han Liu; Cheng-Ting Huang (Fishes, 2026)
Aquaculture faces rising climate-change risks, while photovoltaic power generation requires substantial land resources, underscoring the need for multifunctional land use in the energy transition. Aquavoltaics—combining aquaculture with solar power—has emerged, and its success depends on stakeholder cooperation. Using white shrimp aquaculture in Taiwan as a case study, this study examines four cooperation schemes—a sole-investment scheme, a photovoltaic-led leasing scheme, a landowner lease-back scheme, and a separated aquaculture and photovoltaic operation scheme—across six aquavoltaic types. Cost–benefit and data envelopment analyses assess the economic returns and operational efficiency of aquaculture operators and photovoltaic companies under each scheme. The results show that all schemes offer profit potential but differ in efficiency and income distribution. The landowner lease-back scheme is most efficient for aquaculture operators, while photovoltaic companies operate near the efficiency frontier in all schemes. The findings highlight that cooperation design shapes the economic feasibility, efficiency, and livelihood impact of aquavoltaic systems, providing a useful reference for future policy and model design.

Unraveling the aromatic essence of baked green tea using sensomics: insights from three representative cultivars - Yan Zhao; Chen-Yang Shao; Han Yan; Yue Zhang; Qun-Hua Peng; Zhi Lin; Xiao-Ting Zhai; Hai-Peng Lv; Yin Zhu (Food Chemistry, 2026)

Novel approach to binary protein construction via pulsed electric field-induced unfolding: Comprehensive enhancement of chickpea protein properties - Yongxin Teng; Xindong Xu; Boru Chen; Rui Wang; Ting Zhang; Xiangwei Zhu; Yonghui Li; Zhong Han; Xin-An Zeng (Food Hydrocolloids, 2026)

Potent dual-function of marine peptide N6NH2 and its D-enantiomer to combat MDR A. veronii infection in tilapia (GIFT, Oreochromis niloticus) - Ting Li; Na Yang; Da Teng; Ruoyu Mao; Ya Hao; Huihui Han; Yankang Wu; Xiumin Wang; Jianhua Wang (Fish & Shellfish Immunology, 2026)

Engineering a dynamic defect-mediated heterojunction anode for high-performance secondary batteries with liquid and solid-state electrolytes - Xiaofei Huang; Tianli Han; Ting Zhou; Yajun Zhu; Keke Wang; Fan Bu; Chenchen Zhang; Xuehui Wang; Jinyun Liu (Chemical Engineering Journal, 2026)

Fusing nanoprisms and embedded AI: a portable sensor for intelligent peroxide value monitoring in edible oils - Yu-Ting Xue; Xiao-Zhen Feng; Zhijun Huang; Yu-Zhu Zhao; Xin Chen; Moldir Rustem; Guo-Cheng Han; Zhencheng Chen; Heinz-Bernhard Kraatz (Chemical Engineering Journal, 2026)

Molecular Genetics and Probiotic Mechanisms of Saccharomyces cerevisiae var. boulardii - Tiew-Yik Ting; Wei-Jing Lee; Hoe-Han Goh (Probiotics and Antimicrobial Proteins, 2026)

Overexpression of MdMATE3 Promotes Citric Acid Secretion and Therefore Facilitates Phosphorus Uptake in Apple Plant - Kaiyu Wu; Yuchen Zhang; Xuewen Zhao; Ting Wu; Xuefeng Xu; Zhenhai Han; Changpeng Qiu (Journal of Plant Growth Regulation, 2026)

Research on methods for identifying fractures in carbonate reservoirs based on the R/S-FD method and Bayesian theory: a case study of the Tofutai area, Tarim Basin - Peng-Yuan Han; Wen-Long Ding; Hai-Long Ma; Zhen Wang; Ting-Feng Liu; Juan Zhang (Carbonates and Evaporites, 2026)

Effects of silver nanoparticles and nitrile fungicides on soil microbial community structure, metabolic functions, and resistance genes - Yiwang Wang; Ting Gao; Jiajia Liu; Shaoheng Bao; Fuli Wang; Ge Yao; Xiaoyan Lin; Shijie Jiang; Jinlong Lai; Penggang Han; Jiang Hui (Applied Soil Ecology, 2026)

Early maternal separation induced spatial memory deficits through hippocampal inflammation in piglets - Qi Han; Baochen Xie; Yuxi Shen; Ting Wei; Wenhui Zhang; YongJian Cui; Honggui Liu; Shuai Liu (Applied Animal Behaviour Science, 2026)

Principle of Dynamic Noise Compensation in UAV Aeromagnetic Gradiometer Systems - Hua Guo; Jin-peng Huang; Jian-chun Xu; Jia-ming Li; Wen-han Li; Qi-ting Luo; Qi Yu (Applied Geophysics, 2026)

A novel multimodal combining radiomics and tumor–stroma ratio (TSR) improves diagnosis of gastric cancer peritoneal metastasis - Lin Zhong; Ting Lin; Dong Hou; Hongyun Huang; Shihai Zhou; Yu Lin; Yue Yu; Liangquan Liu; Jing Luo; Fanghai Han; Lang Xie (Clinical & Experimental Metastasis, 2026)

Transgenerational Effects of Elevated Temperature on Life History and Lambda-Cyhalothrin Sensitivity in Cydia Pomonella - Kang-Wu Zheng; Zi-Han Wei; Zi-Nan Xia; Bo-Kun Wang; Ping Gao; Yu-Ting Li; Xue-Qing Yang (Neotropical Entomology, 2026)

A supply-flow-demand network framework for unraveling the compounded impacts of future climate and functional space on urban water-soil ecosystem services - Yu Wang; Junfei Chen; Tonghui Ding; Yufei Han; Xiaodong Yan; Jiayuan Guo; Qingqing Ban; Ting Cheng (Sustainable Cities and Society, 2026)

Application of machine learning in radiolarian taxonomy: A case study on Early Cretaceous Turbocapsula lineage - Xin-Yi Zhang; Han-Ting Zhong; Xin Li; Hui Chen; Shan Ye; Ming-Cai Hou; Chao Ma (Palaeoworld, 2026)

City-Facade: A city-level large-scale point cloud building facade dataset for semantic & instance segmentation - Yiping Chen; Jonathan Li; Ting Han; Huifang Feng; Jun Chen; Cheng Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Multifunctional nano-enabled films and coatings for food packaging: a review of advances in active protection and intelligent monitoring - Yi Liu; Huajuan Wang; Han Deng; Ting Min; Hongxun Wang; Yang Yi; Zhiyong Song; Min Zhou (Food Research International, 2026)

Core-shell Cu@Pt nanoparticles and L-cysteine synergistically boosted electrochemical detection for wide-range melatonin detection in biological and food samples - Jia-Qi Lyu; Jiang-Tao Xu; Hui-Ting Hu; Zhencheng Chen; Guo-Cheng Han; Xiao-Zhen Feng; Heinz-Bernhard Kraatz (Food Chemistry, 2026)

Associations of paraben exposures measured by repeated urinary biomarkers with sperm DNA damage and apoptosis - Xiu-Ting Li; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Ning Zhang; Long Ge; Han-Qin Ye; Pan-Pan Chen; et al. (Environmental Research, 2026)

Association between long-term exposure to fine particulate matter from sand dust storms and small airway dysfunction: A national cross-sectional study - Hailu Zhu; Xueyan Han; Zhaoyang Pan; Hanchao Cheng; Yicong Wang; Qi Wang; Ke Huang; Tianjia Guan; Ting Yang; Chen Wang (Environmental Research, 2026)

A DAMP- and antigen-capturing nanosponge designed as personalized cancer vaccine - Ting Meng; Weikai Sun; Chuanning Wang; Han Yang; Yafei Qi; Daqian Sun; Bingrun Song; Bingzhao Li; Aixin Song; Na Sun; Zhiliang Gao; Dexin Yu (Chemical Engineering Journal, 2026)

Artificial restoration improved the complexity of the soil microbial co-occurrence network and the resistance of microbial communities to environmental changes in degraded sandy grassland - Wentao Mi; Ru Meng; Weibo Ren; Ting Yuan; Yi Liu; Huijie Han; Jialu Liang; Jinqi Zhang (Agriculture, Ecosystems & Environment, 2026)

Mineral Association and Microbial Processing Jointly Prolong Carbon Turnover in Coastal Wetlands - Yuan Li; Chuancheng Fu; Peng Ren; Zhaoliang Song; Lingfang Ni; Ting Wang; Changxun Yu; Ji Chen; Laodong Guo; Iain P. Hartley; Ding He; Xiaoguang Ouyang; et al. (Global Change Biology, 2026)
Coastal margins are critical sites for carbon (C) sequestration, yet the mechanisms stabilizing preaged, allochthonous C (externally‐derived biospheric C) in these environments remain poorly understood. Specifically, the interplay between mineral association and microbial processing represents a significant knowledge gap. Here, we investigated C sequestration mechanisms in Chinese mangrove and saltmarsh soils by analyzing topsoils and cores across 36 sites spanning a 20‐degree latitudinal transect. We found that saltmarshes, characterized by high mineral accretion and lower relative autochthonous C accumulation, exhibited significantly longer soil organic C (SOC) turnover times than mangroves (topsoils: ~2200 vs. ~500 years, respectively). This difference corresponded to higher proportions of preaged (~50%) and petrogenic (rock‐derived; ~20%) SOC in saltmarshes. Linear mixed‐effects models (LMM) confirmed that proxies for mineral protection (e.g., Al/Si) and advanced decomposition (lignin oxidation) were robust, positive predictors of turnover time across the latitudinal gradient. Further structural equation modeling (SEM) indicated a depth‐dependent shift in drivers. In surface soils, microbial necromass accumulation was a significant predictor of C turnover (coefficient = 0.36). However, at depth (1 m), the degree of lignin degradation emerged as the primary predictor of multi‐millennial C persistence (coefficient = 0.45). These results suggest a joint regulation mechanism whereby microbial processing transforms organic matter into stable forms that are subsequently protected by minerals. This mechanism effectively sequesters old, allochthonous C, challenging the paradigm that blue C storage is dominated solely by recent biomass and necessitating a reevaluation of coastal C management frameworks.

Saline patch identification using a semi-supervised knowledge integration deep learning framework based solely on UAV RGB imagery - Zhen Li; Zhigang Sun; Ting Yang; Zhen Liu; Wentao Sun; Yixuan Zhang; Jundong Wang; Yajuan He; Zeqian Yang; Wei Han (Computers and Electronics in Agriculture, 2026)

Morphological and molecular evidence reveal the Sarotherodon melanotheron invasion off Taiwan, East Asia - Yen-Ting Lin; Yu-Hsiang Lin; You-Wei Shiu; Yu-San Han (Marine Pollution Bulletin, 2026)

Coupled polyphosphate storage and DOP mobilization along estuarine gradients in the Pearl River Estuary - Xian-Yang Zhang; Feng-Xian Han; Jian-Ting Li; Jia-Xue Wu; Song-Hui Lu; Lin-Jian Ou (Marine Pollution Bulletin, 2026)

Carbon quantum dots boost microbial biofilm−based hydrovoltaic electricity generation - Ting−Ting Chen; Zhi−Wu Yan; Feng−Ying Cai; Qiu−Xiang He; Han−Hui You; Christopher Rensing; Jian Lü; Shungui Zhou (Water Research, 2026)

Mechanistic insights into gas capture and diffusion during the CO2 separation of mixed matrix membranes using ZIF materials as nanofillers - Han-chong Liu; Hong-li Chen; Li-guang Wu; Ting Wang; Hua-li Chen; Cheng Hu (Process Safety and Environmental Protection, 2026)

Iridoid glycosides and phenolic glycosides from Gentiana rhodantha and their anti-inflammatory activities - Han-Fei Liu; Wan-Jun Pu; Ting Zhao; Xiao-Die Shu; Jun-Jie Lan; Chao Chen; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2026)

Deciphering the effects of cascade reservoirs on phytoplankton communities in a karst river: Importance of super-large reservoirs - Jiang Wu; Xiao-Nan Wu; Xiao-Hui Zhao; Xu Han; En-Hang Liang; Rui An; Jia-Ju Liu; Wei-Ling Sun; Nan Xu; Ting Wang (Journal of Environmental Management, 2026)

Efficient calcined lanthanum-doped magnesium-aluminum layered double hydroxides for advanced phosphate removal: performance and mechanism - Ting Wei; Junxing Han; Xiaoli Dai; Lirong Lv; Yue Shan; Tongzhou Xu; Jian Zhang; Zhongguo Zhang (Environmental Research, 2026)

A pH/glucose dual-responsive Janus dressing with optimized gradient modulus/tissue adhesion promotes diabetic wound healing by dynamic drug-payload release - Huabiao Ye; Ting Dong; Ruoxuan Li; Lihua Fang; Kaifang Xie; Guangting Han; Que Chen; Shan Chi; Jia-Horng Lin; Ching-Wen Lou (Chemical Engineering Journal, 2026)

Photothermal-pancaking synergy in interfacial absorption enables rapid purification of viscous oil-in-water emulsions - Ruoxuan Li; Chaofan Zhu; Ching-Wen Lou; Kaifang Xie; Jia-Horng Lin; Guangting Han; Que Chen; Ting Dong (Chemical Engineering Journal, 2026)

Photobiomodulation Reduces Fibrous Scar Formation After Spinal Cord Injury by Downregulating CXCL3 Expression in Macrophages - Zhihao Zhang; Hongwen Gu; Ting He; Yuanhang Zhao; Shilei Tang; Kangen Han; Yin Hu; Hongwei Wang; Hailong Yu (Molecular Neurobiology, 2026)

Shifts in epidemic patterns and age dynamics of RSV, IFV, and SARS-CoV-2 in Chinese children following COVID-19 non-pharmaceutical intervention relaxation, 2017 − 2024 - Yiguo Zhou; Jian-Bo Xia; Meimei Luo; Wan-Xue Zhang; Shan-Shan Zhang; Le Ao; Han Yang; Qin-Yi Ma; Juan Du; Yu-Ting Wang; Ninghua Huang; Xing-Wen Hu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Cardiopulmonary injury in hypoxia and selenium: A review - Lekang Han; Ting Huang; Zhongzhi Zhao; Zhancui Dang (Journal of Trace Elements in Medicine and Biology, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Photodegradation of sulfisoxazole during nitrite-sensitized photolysis - Xu Gao; Xiaoyu Li; Yaowu Xu; Xinyu Zhan; Ting Zhou; Bing Zhou; Xin Wang; Yuhang He; Chunyu Wang; Han Mao (Journal of Environmental Chemical Engineering, 2025)

Microbial mechanisms of biochar reducing methane emission in a rice-crayfish integrated system - Linjie Ma; Chengxin Zhang; Baoli Qin; Ting Yang; Rong Xu; Lingyu Zhu; Guangming Han; Leiming Wu; Siyu Li; Jianhua Bi; Shouhong Wang; Jiahong Zhang; et al. (Journal of Environmental Management, 2025)

Interactive effect of various fatty acids and the Maillard reaction of sesame meal enzymatic hydrolysates on aroma generation - Qing-qing Ruan; Bei-bei Hu; Kai-yue Su; Jun-ru Li; Wen-ting Yin; Zi-qi Han; Yu-xin Liu; Xiao-shuang Cai (Food Research International, 2025)

Human milk fat Substitutes alleviate dextran sulfate sodium induced cognitive deficits in mice by modulating brain fatty acid and ether Lipid metabolism - Yangzheng He; Linhui Zeng; Han Liao; Jing Li; Yong Sun; Hongyan Li; Ting Luo; Zeyuan Deng (Food Bioscience, 2025)

Tartary buckwheat-soy protein isolate composite gels: gelling, rheological, water-retention, and texture characteristics at different ratios - Xiao Han; Gen Ma; Lin Wang; Ting Cheng; Yangyang Guo; Liangzhen Jiang; Yan Wan; Xiaoqin Zheng; Changying Liu; Lianxin Peng; Gang Zhao; Xiulan Guo; et al. (Food Hydrocolloids, 2025)

Development of a marine probiotic bacterium producing nanobody and/or dsRNA against white spot syndrome virus (WSSV) - Mary Nia M. Santos; Fernand Fagutao; See-Yeun Ting; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

High-precision geochronology of the Early Cretaceous Jiufotang Formation: Temporal constraints on the late phase of the Jehol Biota - Yu-Ting Zhong; Magdalena H. Huyskens; Run-Jian Chu; Han-Qing Yang; Jian-Fang Hu; Ya-Qiong Wang; Shi-Xi Cai; Qiong Wu; Qiang Ma; Huai-Chun Wu; Qing-Zhu Yin; Yi-Gang Xu (Earth and Planetary Science Letters, 2025)

CuO/PVA-based ultra-low-volume oral H2S detection system to reveal tongue coating effects - Moumita Deb; Chang-Chuan Huang; Yen-Ming Lai; Chang-Ju Chu; Yu-Shan Lee; Chien-Ting Chen; William Lee; Hsin-Fei Meng; Li-Yin Chen; Olivier Soppera; Chao-Sung Lai; Ding-Han Wang; et al. (Chemical Engineering Journal, 2025)

An investigation of localized entropy driven cathode electrolyte interphase to a one-step complete deprotonation of ethylene carbonate on Ni-rich layered material of lithium-ion battery - Laurien Merinda; Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Chusnul Khotimah; Han-Pin Hsieh; Jeng-Kuei Chang; Shu-Chih Haw; Chih-Wen Pao; Jeng-Lung Chen; Qunjie Xu; et al. (Chemical Engineering Journal, 2025)

Chitosan hydrogel catalyst shifts PMS activation towards a singlet oxygen-dominated non-radical pathway for efficient pollutant degradation - Saili Chen; Jiajia Huang; Han−Liang Fang; Ting−Ting Chen; Xiaohong Pan; Zhi−Wu Yan; Yu−Hang Xu; Hai−Lei Cao; Jian Lü (Chemical Engineering Journal, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

Impact of climate change and vegetation greening on sediment transport in the Yarlung Tsangpo River - Yiyi Li; Ting Zhang; Yi Zhao; Ziqi Guo; Peng Han; Qiang Zhong; Liu Liu; Shuyue Mao; Yichu Wang; Dongfeng Li (CATENA, 2025)

Gut Microbiota Improve the Prediction of Stroke-Associated Pneumonia Risk and Outcomes in Acute Ischemic Stroke - Yi-si Lin; Jia-hao Chen; Wei-hao Zhuang; Jia-ni Huang; Yi-han Chen; Jie Zhang; Jia Li; Meng Huang; Jia-long Hou; Shuang-jie Qian; Zhi-bo Chen; Yan-lei Zhang; et al. (Translational Stroke Research, 2025)

Radixin in the nucleus accumbens core modulates amphetamine-induced locomotor activity based on context association - Wen Ting Cai; Myung Ji Kwak; Joonyeup Han; Haeun Rim; Lars Björn Riecken; Helen Morrison; Wha Young Kim; Jeong-Hoon Kim (Psychopharmacology, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Topographic differences in EEG microstates: distinguishing juvenile myoclonic epilepsy from frontal lobe epilepsy - Ying Li; Lidao Xu; Yibo Zhao; Mingxian Meng; Yanan Chen; Bin Wang; Beijia Cui; Jin Liu; Jiuyan Han; Na Wang; Ting Zhao; Lei Sun; et al. (Cognitive Neurodynamics, 2025)

A standard for geological evaluation of urban underground space resources in the Beijing plain - Han-han He; Cheng-shan Wang; Jing He; Yuan-xin Zhou; Lei Wang; Stuart Marsh; Chao Li; Tong-ming Fang; Fang-zhen Li; Sheng-li Cao; Jing Liu; Yi-ting Zhao (Bulletin of Engineering Geology and the Environment, 2025)

Revision of the Armoreye dory genus Zenion (Zeiformes: Zeniontidae) in the South China Sea, with a description of a new species - Yen‐Ting Lin; Chia‐Hao Chang; Yu‐San Han; Chien‐Hsiang Lin (Journal of Fish Biology, 2025)
This study describes a new species of armoreye dory, Zenion boops sp. nov., from Dongsha Island, Taiwan, as part of a comprehensive revision of the genus Zenion in the South China Sea. The new species is clearly distinguishable from its tropical congeners, Z. hololepis and Z. japonicum , based on a combination of distinct morphological features, meristic counts, otolith morphology and c oxidase subunit I ( COI ) gene sequences. Z. boops is characterized by a smooth second dorsal spine, a long first dorsal spine, 30–35% of second (longest) dorsal spine, a small and narrow notch at the symphysis of the maxilla, and a relatively large eye diameter, 55–61% of head length. Furthermore, otolith morphology and phylogenetic analyses based on partial sequences of the cytochrome COI gene reveal significant genetic divergence between this new species and its congeners. With the addition of Z. boops , the genus Zenion now includes four valid species. We also present an identification key for all Zenion species and provide detailed descriptions of their otoliths. Also, we provide data that show that Z . hololepis is restricted to the Atlantic Ocean.

Individual tree segmentation via contrastive learning and semantic priors in point clouds - Jin Ma; Ting Han; Chaolei Wang; Xiaohai Zhang; Xinchang Zhang; Wuming Zhang; Yiping Chen (Urban Forestry & Urban Greening, 2025)

Corrigendum to “the different impacts of ambient air pollution exposure on the risks of gestational hypertension and preeclampsia in twin pregnancies” [toxicology and applied pharmacology volume 503, October 2025, 117505] - Wei-Zhen Tang; Hong-Yu Xu; Qin-Yu Cai; Yun-Ren Pan; Hao-Wen Chen; Ya-Ting Jia; Tai-Hang Liu; Yong Heng Wang; Fei Han; Niya Zhou (Toxicology and Applied Pharmacology, 2025)

Reply to “Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China” - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Feasibility study of the integration of buoyancy energy storage systems in floating offshore wind: A case study in Taiwan - Ting-Li Lin; Shun-Han Yang (Ocean Engineering, 2025)

Exploring protein-mediated quality control mechanisms in Rice cooking behavior: from static protein content to dynamic architecture - Mengdi Chen; Han Geng; Dong Wang; Jinhong Gou; Mingqin Li; Ting Li; Xinxia Zhang; Juan Li; Li Wang (Food Chemistry, 2025)

Characterization of vB_SaRS_FS19–1, a newly isolated broad-host-range and virulent bacteriophage infecting Staphylococcus aureus and its application in foods - Xinyan Yao; Chaoxiang Jia; Ting Qin; Dai Peng; Linlin Huang; Yi Liu; Saiyu Zhang; Yingqian Han; Yanbin Yang; Heping Li; Hua Wu; Guoyu Yang; et al. (Food Chemistry, 2025)

A novel approach to sesame oil aroma generation: Synergy of enzyme-modified lipids and the Maillard reaction - Bei-bei Hu; Wen-ting Yin; Tong Yu; Zi-qi Han; Yu-xin Liu; Hua-min Liu; Xiao-shuang Cai; Zhuo-qing Zhai; Fan Zhang (Food Chemistry, 2025)

Biodegradation of aflatoxin B1 and ochratoxin A by Aspergillus sp. OA3, a novel fungal strain isolated from Fu brick tea - Yike Han; Ting Liu; Yanting Chen; Jingyi Ren; Xingnan Wang; Hongcai Li; Wenzhi Lei; Yuanye Liu; Ruisen Dai; Chunfeng Guo; Zhenpeng Gao (Food Bioscience, 2025)

Multi-trophic communities in river ecosystems: Insights into environmental drivers and assembly mechanisms for ecological management— a case study in the Minjiang River - Yu Xiang; Liwei Fu; Ting Cai; Han Zhang; Wenliang Xiang; Ruxin Yang; Mengli Chen (Environmental Research, 2025)

Short-term exposure of non-optimal temperature and lung function: The role of relative humidity - Hailu Zhu; Yicong Wang; Xueyan Han; Zhaoyang Pan; Qi Wang; Ke Huang; Tianjia Guan; Ting Yang; Chen Wang (Environmental Research, 2025)

Acidification boosts the photodynamic activity of anthocyanidin for enhanced sterilization - Zhenqing Guo; Yajie Wang; Xinqi Wang; Ting Du; Kaiyuan Su; Lin Yang; Yaru Han; Shuo Shi; Jianlong Wang; Wentao Zhang (Chemical Engineering Journal, 2025)

Robust fluorine-free static/dynamic anti-icing and photothermal de-icing superhydrophobic surface with multi-bioinspired structures and wettability - Wenliang Zhang; Dongsong Wei; Yafei Shi; Ting Lu; Zhen Zhang; Yuanpeng Wang; Shuyi Li; Ana Sofia Oliveira Henriques Moita; Zhiwu Han; Yan Liu (Chemical Engineering Journal, 2025)

Modulating the redox states in a 3D conductive MOF for sweat ascorbic acid monitoring - Wei-Qi Wang; Han Xie; Feng Cheng; Ting Zou; Ke-Qiang Xu; Amare Aregahegn Dubale; Wen-Hui Zhang; Ning Xu; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2025)

Lysine functionalization regulates the electronic structure and reaction microenvironment of Cu2O for efficient and stable nitrite electroreduction - Xiao-Hui Wang; Yi-Ting Yang; Yue-Han Qin; Fan Yang; Yu Chen; Shu-Ni Li (Chemical Engineering Journal, 2025)

Fs–LA–ICP–MS U–Pb dating of fluorite and its prospect for geological application - Yan-Wen Tang; Na Liu; Jun-Jie Han; Yan Liu; Wan-Ting Ge; Jian-Feng Gao; Ting-Guang Lan (Chemical Geology, 2025)

Urban cyclists’ exposure to PM2.5: A quantitative analysis using trajectory data and mobile monitoring - Ting Wang; Xiao Zhou; Han Wang; Xinmin Zhang; Wanyun Lu (Atmospheric Pollution Research, 2025)

Regulation of Necroptosis by Aspergillus fumigatus Exopolysaccharide in Human Macrophages Derived from THP-1 Cells: Involvement of the RIP1-RIP3-MLKL Signaling Axis - Wei Shen; Meng Wang; Ting Han; Yan Yao; Xinyi Ying; Yuyue Cui; Peng Du (Current Microbiology, 2025)

An in vivo NanoBiT-based pseudoviral biosensor for real-time monitoring of SARS-CoV-2 spike/hACE2 interactions and therapeutic screening - Cheng-Han Lin; Meng-Wei Lin; Xin-Rui Yang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chin-Hung Tsai; Chih-Sheng Lin (Analytica Chimica Acta, 2025)

Comparison of three 16S rRNA gene primer sets for the study of planktonic archaeal communities in the Antarctic Peninsula region - Zuoqi Wang; Yinxin Zeng; Miming Zhang; Yu Du; Wei Han; Ting Hu; Yongqiang Hu; Haitao Ding (Acta Oceanologica Sinica, 2025)

The different impacts of ambient air pollution exposure on the risks of gestational hypertension and preeclampsia in twin pregnancies - Wei-Zhen Tang; Hong-Yu Xu; Qin-Yu Cai; Yun-Ren Pan; Hao-Wen Chen; Ya-Ting Jia; Tai-Hang Liu; Yong Heng Wang; Fei Han; Niya Zhou (Toxicology and Applied Pharmacology, 2025)

Protective effects of nicotinamide mononucleotide on DNA damage and cell death in A549 cells and aging in C. elegans caused by hydrogen peroxide - Chuncao He; Xueying Sun; Ting Xu; Xiaoqiang Hu; Jinyi Han; Kexin Xu; Qin Song; Ting Duan; Jun Yang (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2025)

Perfluorohexanoic acid exhibits more potential for the proliferation, migration, and invasion of triple-negative breast cancer cells under the 3D culture model - Jing Han; Huan Wang; Sheng Wei; Yawen Chen; Ting Xu; Daqiang Yin (Journal of Hazardous Materials, 2025)

Ambient ozone exposure and acute blood oxygen desaturation: Role of airflow limitation - Jiarun Mi; Hongtao Niu; Wei Li; Junqi Li; Xueyan Han; Sinan Wu; Teng Wang; Ke Huang; Tianjia Guan; Ting Yang; Chen Wang (Journal of Hazardous Materials, 2025)

The ternary synergy of Fe, N and P enhances the membrane capacitive deionization performance of porous biochar - Houqi Zhou; Ting Xu; Chi Fei; Yilong Fan; Keying Tang; Chunyu Chen; Dianchun Ju; Han Ma; Zuoqiao Zhu; Rui Mao (Journal of Environmental Chemical Engineering, 2025)

Tribological properties of polydopamine modified microcapsules/polyimide based composites - Xiaoyi Wei; Zhongliang Yang; Lixiu Zhang; Han Lu; Zhenyu Yin; Ting Li (Chemical Engineering Journal, 2025)

Ag nanoparticles anchored on oxygen vacancy-rich alumina catalyst for efficient bacterial inactivation - Ting Wang; Fangyuan Gu; Leyang Xu; Wenqi Tang; Yanfeng Han; Yongjie Wang; Shi Yang; Weiying Wang; Xinlong Zhang; Tianshuo Zhao; Biao Ran; Chaopeng Fu; et al. (Chemical Engineering Journal, 2025)

Development of derivatization-enhanced EIEIO-driven glycosidic linkage sequencing (DEED-GL-Seq) strategy and its application to glycogen-sourced oligosaccharides profiling - Xin Zheng; Yufang Ma; Xinge Cui; Yi Wang; Jingjing Jiang; Ting Liu; Zhijun Zhang; Mingsheng Ma; Xiaohong Han; Cai Tie (Carbohydrate Polymers, 2025)

The Role of Gut-Brain Tryptophan Metabolism and Fatty Acid Peroxidation in the Effect of Sleep Deprivation on Anxiety and Depression in PCOS Mice - Ting Han; Shangjing Liu; Hao Liu; Xin Wang; Xiaojia Yang; ShanAn Chan; Sergey Tumanov; Richard D. Cannon; Yang Yang; Ting-Li Han (Molecular Neurobiology, 2025)

Influence of herbal extract blend supplementation on growth performance, liver and intestinal health, intestinal transcriptome, and resistance to Aeromonas veronii in Micropterus salmoides with optimized feeding intervals - Zi ying Zeng; Dong dong Yu; Yi Ting Shen; Xing han He; Shun Yang; Hui Fei (Animal Feed Science and Technology, 2025)

Aporphine alkaloids and flavonoids from the roots of Fissistigma retusum (H. Lév.) Rehder - Ya-Ting Xiao; Xue-Na Zhao; Han Li; Ying Ren; Yu-Hang Liu; Yu-Ming Liu (Natural Product Research, 2025)

Toxicological assessment of inorganic arsenic: Bioaccumulation and immunotoxicity in Acanthopagrus schlegelii - Zhen-Hao Liao; Bo-Ying Chen; Han-Yang Yeh; Huai-Ting Huang; Shih-Lun Yuan; Po-Tsang Lee; Huu-The Nguyen; Yeh-Fang Hu; Fan-Hua Nan (Chemosphere, 2025)

Prevalence and related factors of antenatal depression in 11 provinces and cities of China: a 100,000 population-based study - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Fungal diversity associated with cherry leaf spot in Yantai city, Shandong province, China - Yumeng Wang; Ting Liu; Chuang Han; Xiaoyan Yu; Xi Xu; Yuhan Guo; Xinying He; Wensheng Xiang; Xiangjing Wang; Junwei Zhao (Physiological and Molecular Plant Pathology, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Functional response and instar preference of Encarsia formosa (Hymenoptera: Aphelinidae) parasitizing Bemisia tabaci (Hemiptera: Aleyrodidae) at different densities and temperatures - Bo Zhang; Guo-Ting Yuan; Peng Han; Krutmuang Patcharin; Perumal Vivekanandhan; Jin-Long Zhang; Jiao Kong; Guo-Hua Chen; Xiao-Ming Zhang (Journal of Asia-Pacific Entomology, 2025)

Coffee mitigated cognitive impairments in sleep-deprived mice by regulating circadian rhythm, inflammation, oxidative stress, and intestinal ecology - Hui-Bin Jiang; Fen-Fen Wei; Wen-Ting Li; Zi-Han Lin; Chuang Zhu; Yan Wu; Ying Wang; Li-Hua Song (Food Bioscience, 2025)

Advanced low-temperature plasma-driven oxidation for mitigating pharmaceutical and personal care products in wastewater: Mechanisms, influencing factors, and reactor configurations - Yanhe Han; Haoyi Wang; Mengxiang Wei; Hao Yao; Ting Liu; Xuejiao Ma (Chemical Engineering Journal, 2025)

Synergistic degradation mechanism of roxithromycin by the combination of TiO2/graphene oxide/polypropylene fiber photocatalytic network and microalgae - Wei Gao; Xiangjie Pan; Junzhuang Wu; Ting Guan; Feng Cai; Jiangang Han; Yanwen Zhou; Jian Qiu; Wei Li (Chemical Engineering Journal, 2025)

Glycosylated protein-related microenvironmental features in breast cancer are associated with patient prognosis - Xiaoxiao Zhong; Jiaxuan Han; Huan Li; Xiangyu Shen; Bowen Yu; Ting Chen; Haobing Li; Jun Li; Jin Pang; Liyuan Qian; Wei Wu; Xiaoliang Tong; et al. (Mammalian Genome, 2025)

Berberine attenuates the expression of NLRP3 and downstream inflammasome effectors in diabetic retinopathy - Na Li; Ji-Lin Chen; Yi-Jian Sun; Jia-Fan Sun; Ting-Hua Wang; Amy Yi Hsan Saik; Alan Han-Kiat Ong (Journal of Natural Medicines, 2025)

Effects of fertilizers on arsenic accumulation in ratoon rice: implications for human health risks - Kai-Wei Juang; Han-Ting Hsu; Wan-Ting Chiao; Chien-Hui Syu; Bo-Ching Chen (Environmental Geochemistry and Health, 2025)

CAFM: a freeware for geochemical data processing and concentration–area fractal modeling and its application for identifying uranium anomalies of different genesis - Jun-Ting Qiu; Jiang-Kun Li; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Applied Geochemistry, 2025)

First and northernmost record of the invasive redhead cichlid (Vieja melanurus) in East Asia: evidence from Taipei City, Northern Taiwan - Yen-Ting Lin; Yu-Hsiang Lin; Jhao-Cian Hou; Hong-Yu Yang; Yu-San Han (Biological Invasions, 2025)

Cadmium induces autophagy via IRE1 signaling pathway activated by Ca2 + in GC-2spd cells - Yue Han; Juan Dai; Jinxin Cheng; Yan He; Chengkun Zhao; Rui Li; Yaqin Zhang; Ling Zhang; Ting Zhou; Yuqin Shi (Reproductive Toxicology, 2025)

Biaxially oriented polyethylene (BOPE) and exogenous H2S extend strawberry shelf-life by increasing antioxidant activity and inhibiting pigment accumulation - Ying-Chun Song; Yu-Qi Zhao; Chi-Ming Tang; Pedro Garcia-Caparros; Si-Yu Yang; Jia-Qi Yu; Xiu-Ting Hu; Kang-Di Hu; Zhuo Han; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2025)

Utilizing natural compounds as ligands to disrupt the binding of SARS-CoV-2 receptor-binding domain to angiotensin-converting enzyme 2, impeding viral infection - Jingyi Wu; Ting-Hsu Chen; Zi-han Shen; May-Jywan Tsai; Max K. Leong; Yan-qiang Huang; Ching-Feng Weng (Phytochemistry Letters, 2025)

PFHxA and PFHxS promote breast cancer progression in 3D culture: MEX3C-associated immune infiltration revealed by bioinformatics and machine learning - Huan Wang; Guangming Xie; Zhijin Zhang; Jing Han; Yue Zhang; Ting Xu; Daqiang Yin (Journal of Hazardous Materials, 2025)

Early-life long-term exposure to di(2-ethylhexyl) phthalate (DEHP) impairs pathogenic avoidance behavior associated with dopaminergic pathway in Caenorhabditis elegans - Ting-An Lin; Chun-Han Chang; Tzu-Ting Chang; Vivian Hsiu-Chuan Liao (Environmental Toxicology and Pharmacology, 2025)

A 3D perspective for understanding the mechanisms of urban heat island and urban morphology using multi-modal geospatial data and interpretable machine learning - Ting Han; Chenxi Du; Yijia Xie; Xinyan Xian; Xinchang Zhang; Bisheng Yang; Yiping Chen (Building and Environment, 2025)

Litter addition potentially enhances volatile organic compound emission from a freshwater wetland - Hua Fang; Ting Wu; Shutan Ma; Qina Jia; Fengyu Zan; Juan Zhao; Jintao Zhang; Zhi Yang; Hongling Xu; Han Jiang; Xinming Wang (Atmospheric Environment, 2025)

Mapping QTLs for adult-plant resistance to yellow rust in a hard winter wheat population Heyne × Lakin - Chunlian Li; Xiao-Ting Xu; Yibo Zhang; Shengjie Liu; Jianhui Wu; Dejun Han; Robert Bowden; John Fellers; Guihua Bai (Theoretical and Applied Genetics, 2025)

High-quality reference genome and population analysis of allotetraploid Elymus sibiricus provide insight into genome origin and environmental adaptations to the Qinghai-Tibetan Plateau - Xinrui Li; Changbing Zhang; Lili Wang; Gai Huang; Daxu Li; Changmian Ji; Zujun Yang; Minghong You; Lijun Yan; Lili Chen; Wenlong Gou; Xiong Lei; et al. (Science China Life Sciences, 2025)

SIMPLE: A One-Pot RPA-Cas12b Method for Single Nucleotide Variations Identification with an Expanded Scope and Clinical Applications - Kaiming Guo; Yongkang Lai; Yiru Han; Linlin Bai; Ting Wang; Shengzhou Wang; Ziqin Zhang; Dianwei Liu; Yanju Chen; Jiulong Zhao; Yanan Pang; Feng Qian; et al. (Phenomics, 2025)

Research progress on the bioactivity of platycodin D from Platycodon grandifloras - Ying Song; Xin Lv; Chuanbo Ding; Xinglong Liu; Yuanyuan Han; Shengyue Chen; Min Li; Ting Zhao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Characteristics of the fermented chicken products by Lactobacillus strains in different fermentation processes - Ting Jiang; Rameesha Anjum; Haiqian Zhang; Chuanhu Han; Peng Wu; Junwu Ji; Tao Zhang; Daodong Pan; Mingjuan Ou; Zhen Wu (Food Research International, 2025)

Photodynamically activated chlorogenic acid-based antimicrobial packaging films for cherry preservation - Ximei Han; Jiayi Chen; Qian Wang; Jie Zhang; Jiaqi Mi; Jianxing Feng; Ting Du; Jianlong Wang; Wentao Zhang (Food Chemistry, 2025)

Mechanism of concentration and enrichment of citrus peel pectin driven by multi-chamber electrophoresis and low temperature - Zhanwei Yang; Jin Wang; Hanquan Liu; Mei Wang; Han Liao; Xianbiao Liu; Yuancong Zhang; Ting Liu; Lecheng Shen; Hecheng Meng; Shujuan Yu; Xiaobing Guo (Food Hydrocolloids, 2025)

Interfacial charge transfer mediated by bridging and terminal hydroxyls on the (001) and (101) facets of TiO2 in the photocatalytic degradation of toluene - Jinze Lyu; Yaxin Zhao; Ziyi Zhong; Ting Zhang; Xinpu Han; Ji Li (Environmental Research, 2025)

Ecological impacts of treated effluent on multitrophic biodiversity and their interactions - Wei Xiong; Ting Chen; Xun Du; Lin Hou; Yiyong Chen; Jing-Long Han; Aibin Zhan (Environmental Research, 2025)

Erratum to “A SEM–FEM–SPH framework for physics-based source-to-slope simulation of earthquake-induced landslides” [Engineering Geology Volume 353, 2025, 108127] - Hui Jiang; Yi-Xiang Qiu; Jing-Jing Zhu; Jin-Ting Wang; Chu-Han Zhang; Xiu-Li Du (Engineering Geology, 2025)

Architecting spent coffee grounds for highly efficient solar water evaporation - Zhuoning Xu; Chunyu Ji; Ting Wang; Qian Ding; Yifeng Wang; Han Yang (Desalination, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

Sex effects on dynamic structure–function coupling of intrinsic brain network - Xi Zhang; Dandan Li; Yuting Yuan; Xuebing Han; Lan Yang; Jiayu Lu; Ting Li; Zhifeng Li; Bin Wang (Brain Imaging and Behavior, 2025)

Strategies, mechanism, and prospects for wood biomass-based intelligent food packaging materials - Jiarui Zhang; Yaxuan Wang; Ting Xu; Weirong Li; Qiang Dong; Meng Zhang; Junjie Qi; Han Zhang; Xuan Wang; Wei Liu; Liyu Zhu; Chuanling Si (Trends in Food Science & Technology, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

Cryptochromes (CRYs) in pepper: Genome-wide identification, evolution and functional analysis of the negative role of CaCRY1 under Phytophthora capsici infection - Fei Sun; Yue Chen; Ying Luo; Feng Yang; Ting Yu; Huibin Han; Youxin Yang; Yong Zhou (Plant Science, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Microbial communities and metabolite dynamics in the flowering fermentation of Fu brick Tea: Correlations with mycotoxin degradation - Yike Han; Xingnan Wang; Hongcai Li; Yuanye Liu; Mengzhen Han; Yanting Chen; Jingyi Ren; Ting Liu; Yan Liang; Xin Hu; Guimei Chen; Chunfeng Guo; et al. (Food Bioscience, 2025)

Arginine-terminated egg white peptide Leu-Phe-Arg (LFR) repairs intestinal barrier damage through the PI3K/AKT/mTOR/p70s6k signaling pathway: An analysis combined transcriptomics and proteomics - Siwen Lyu; Menghan Fu; Qi Yang; Qingwen Han; Shengrao Li; Yingnan Zeng; Jingbo Liu; Yiding Yu; Ting Zhang (Food Bioscience, 2025)

Metabolomics and volatilomics unravel the signature of pivotal bioactive metabolites in sea buckthorn juice and pomace under hydrolysis of cellulase and pectinase - Xingnan Wang; Jingyi Ren; Yanting Chen; Ting Liu; Hongcai Li; Wenzhi Lei; Yike Han; Shiqi Li; Xiaoning Tu; Bin Zhang; Guangquan Liu; Zhenpeng Gao (Food Bioscience, 2025)

A SEM–FEM–SPH framework for physics-based source-to-slope simulation of earthquake-induced landslides - Hui Jiang; Yi-Xiang Qiu; Jing-Jing Zhu; Jin-Ting Wang; Chu-Han Zhang; Xiu-Li Du (Engineering Geology, 2025)

Visible light regulates the activation pathway of periodate on Bi/Mo dual sites for efficient micropollutant degradation: The overlooked roles of metastable complex - Fuyang Liu; Qiqi Dong; Yong Ting; Zhengmao Li; Yanghui Hou; Jialiang Liang; Peng Han; Meiping Tong (Chemical Engineering Journal, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

The mouse resource at National Resource Center for Mutant Mice of China - Bingzhou Han; Dongshen Chen; Zhong Chen; Ting Wang; Kaiyuan Zi; Rui Feng; Xiaoliu Yang; Ling’en Li; Juan Liang; Xiang Gao (Mammalian Genome, 2025)

Lifespan extension by rapamycin in Brachionus dorcas (Rotifera) is dose and developmental stage dependent - Ting Liu; Han-Bing Dong; Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Yi-Long Xi (Hydrobiologia, 2025)

Protein Kinase C Epsilon Overexpression Protects the Heart Against Doxorubicin-Induced Cardiotoxicity Via Activating SIRT1 - Danyong Liu; Chunyan Wang; Yao Chen; Xiaolei Huang; Yajie Wen; Shan Duan; Yin Cai; Xia Li; Jianfeng He; Kaijia Han; Ting Li; Yuantao Li; et al. (Cardiovascular Toxicology, 2025)
Doxorubicin (DOX)-induced cardiotoxicity (DIC) is known to be associated with reduction of cardiac protein kinase C epsilon (PKC-ε). PKC-ε promotes cell survival and protects hearts against various stresses. However, it is unclear whether or not the reduction in cardiac PKC-ε expression plays a causal role in DIC and in particular the potential underlying mechanism whereby PKC-ε may protect against DIC. C57BL/6 mice (8–10-week-old) were either treated with DOX administered intraperitoneally for a duration of 4 weeks to produce cardiotoxicity, or untreated in which mice received the same volume of saline. In vitro, neonatal rat ventricle cardiomyocytes were exposed to DOX for 24 h in the absence or presence of adenovirus overexpressing PKC-ε. Cardiomyocytes in a subgroup were treated with sirtuin-1 (SIRT1) selective inhibitor Ex527. Four weeks after DOX, cardiac contractile function was decreased concomitant with increased serum CK-MB and LDH levels as well as increases in Bax-to-Bcl-2 ratio and Cleaved Caspase 3 proteins expression, while PKC-ε and Sirt1 protein expressions were significantly decreased. In vitro, DOX reduced cardiomyocyte PKC-ε and SIRT1 protein expression, decreased cardiomyocyte viability, and increased LDH release with concomitant increases in oxidative stress and apoptosis. These changes were attenuated by overexpression of PKC-ε. IP study showed that PKC-ε could directly or indirectly bind SIRT1 in cardiomyocytes, and the protect effects of PKC-ε were further canceled by SIRT1 inhibition. In conclusion, activating SIRT1 may represent a major mechanism whereby PKC-ε protects the heart against DOX-induced cell apoptosis and oxidative stress. Graphical Abstract Dox induces cardiotoxicity via inhibiting PKC-epsilon/Sirt1 signaling which can be reversed by PKC-epsilon overexpression.

Deep learning for predicting water saturation using rock physics analysis and geostatistics theory: A case study of the Psh8 in GFZ area, Ordos Basin - Yong-gang Wang; Ya-ting Wang; De-yong Zhao; Ke-han Cai; Wei-fang Liu; Yu-ting He (Applied Geophysics, 2025)

Sublethal and transgenerational effects of nitenpyram on Acyrthosiphon gossypii and its impacts on symbiotic bacteria - Yindi Wei; Wenjie Li; Ting Chen; Yue Su; Xu Han; Yongsheng Yao (Crop Protection, 2025)

Ethylene stimulates methane oxidation and inhibits methane production in green manure-rice systems - Jinxin Sun; Zhengbo Ma; Guopeng Zhou; Ting Liang; Rui Liu; Danna Chang; Han Liu; Jia Liu; Chunqin Zou; Weidong Cao (Journal of Environmental Management, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Rational design of alginate lyase ALYI1 for improving the antioxidant activity of the alginate oligosaccharides - Jin-Ping Huang; Jin-Xin Zhao; Ming-jing Zhang; Jiru Han; Ya-Tong Han; Xue-Ting Wang; Tian-Bao Wu; Jun-Nan He; Cai-Mei Chen; Yan-Xia Zhou (Food Chemistry, 2025)

One-step conversion of waste sawdust into bitter melon-like particles for efficient solar-driven water evaporation - Chunyu Ji; Ting Wang; Yifeng Wang; Qian Ding; Zhuoning Xu; Zhili Peng; Han Yang (Desalination, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

Rubrolithibacter danxiaensis gen. nov., sp. nov. isolated from red sandy conglomerate in the Danxia Mountain - Wen-Hui Lian; Huan-Huan He; Ying Wang; Zhuo-Huan Zheng; Fang Chen; Ting Zhou; Chao-Jian Hu; Jia-Rui Han; Lei Dong; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Enhancing grain moisture prediction in multiple crop seasons using domain adaptation AI - Ming-Der Yang; Yu-Chun Hsu; Tsai-Ting Liu; Han-Hui Huang (Computers and Electronics in Agriculture, 2025)

Deciphering unique enzymatic pathways in sulfonamide biotransformation by direct ammonia oxidizer Alcaligenes ammonioxydans HO-1 - Jia-Xin Zhang; Ting-Ting Wei; Di Min; Jun-Lu Lv; Dong-Feng Liu; Jie-Jie Chen; Yang-Yang Yu; Han-Qing Yu (Water Research, 2025)

Stalagmite multi-proxy records reveal spatial complexity of precipitation and monsoon variability in China over past 60 years - Yan-Xia Xue; Yao Wu; Chao-Jun Chen; Tao Fan; Huai Su; Han-Ying Li; Hai Cheng; Jian-Jun Yin; Jun-Yun Li; You-Feng Ning; Ting-Yong Li (Quaternary Science Reviews, 2025)

Bicyclic polyprenylated acylphloroglucinol-related meroterpenoids as potent DRAK2 inhibitors from Hypericum patulum - Jin-Chang Huang; Xin-Yu Jia; Yi-Fan Lv; Hong-Hong Xu; Ming Han; Qiang-Qiang Yu; Yu-Ting Lu; Hong-Xun Yang; Yang Yang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Faceted-nanorods morphologies V2O5 nanostructures for enhanced CO2 photocatalytic conversion to CH4 under UV irradiation - Chih-Chiang Wang; An-Ya Lo; Yi-Jen Huang; Han-Chang Shih; Fuh-Shien Shieu; Tzu-Hsien Tseng; He-Ting Tsai (Journal of Environmental Chemical Engineering, 2025)

Petrogenesis and age of granitoids associated with the Dongshan Cu polymetallic deposit, East Kunlun Orogenic Belt, NW China: Implications for the Middle to Late Triassic tectonic setting and Cu polymetallic mineralization - Yi-Chen Chen; Zheng-Jiang Ding; Jun-Wei Bo; Shi-Jiong Han; Ting-Ting Li; Pan Ji; Rong-Qiang Guo (Geochemistry, 2025)

Effect of lactic acid on short-chain fatty acids and hydrogen production during anaerobic fermentation of acidified food waste - Xudong Wang; Xujia Ming; Xiao Han; Yao Liu; Mengyu Chen; Ting Zhang; Xianguo Li; Dahai Zhang (Fuel, 2025)

Explosion suppressing effects of Mg(OH)2/NH4H2PO4 compound powders on the methane explosion and its microscopic mechanism about capturing intermediate products - Qiuhong Wang; Leilei Zhu; Jun Deng; Qingfeng Wang; Jing Han; Dong Zhao; Youjie Sheng; Ting Pan; Jianxiong Liu (Fuel, 2025)

Application and comparative analysis of Enterococcus faecium CGMCC 29309 and Lactobacillus delbrueckii subsp. bulgaricus CGMCC 1.60194 in the preparation of fermented soymilk - Chang-Cheng Li; Zi-Yu Li; Yu-Ting Feng; Yu-Han Tian; Zhen-Peng Gao; Chun-Feng Guo (Food Bioscience, 2025)

Impacts of forest expansion on microbial diversity and community assembly in fragmented mountain ecosystems - Wen-Hui Lian; Wen-Sheng Zhao; Jia-Rui Han; Chao-Jian Hu; Guo-Yuan Shi; Fang Chen; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Mukhtiar Ali; Lei Dong; Ting Zhou; et al. (Environmental Research, 2025)

Histaminergic Innervation of the Ventral Anterior Thalamic Nucleus Alleviates Motor Deficits in a 6-OHDA-Induced Rat Model of Parkinson’s Disease - Han-Ting Xu; Xiao-Ya Xi; Shuang Zhou; Yun-Yong Xie; Zhi-San Cui; Bei-Bei Zhang; Shu-Tao Xie; Hong-Zhao Li; Qi-Peng Zhang; Yang Pan; Xiao-Yang Zhang; Jing-Ning Zhu (Neuroscience Bulletin, 2025)
The ventral anterior (VA) nucleus of the thalamus is a major target of the basal ganglia and is closely associated with the pathogenesis of Parkinson’s disease (PD). Notably, the VA receives direct innervation from the hypothalamic histaminergic system. However, its role in PD remains unknown. Here, we assessed the contribution of histamine to VA neuronal activity and PD motor deficits. Functional magnetic resonance imaging showed reduced VA activity in PD patients. Optogenetic activation of VA neurons or histaminergic afferents significantly alleviated motor deficits in 6-OHDA-induced PD rats. Furthermore, histamine excited VA neurons via H1 and H2 receptors and their coupled hyperpolarization-activated cyclic nucleotide-gated channels, inward-rectifier K + channels, or Ca 2+ -activated K + channels. These results demonstrate that histaminergic afferents actively compensate for Parkinsonian motor deficits by biasing VA activity. These findings suggest that targeting VA histamine receptors and downstream ion channels may be a potential therapeutic strategy for PD motor dysfunction.

Microrna363-5p targets thrombospondin3 to regulate pathological cardiac remodeling - Yu-kun Ma; Xin-yi Han; Shu-huai Zan; Hui-ting Liu; Xue-yan Zhou; Dan-xue Zhao; Rui Xing; Peng Zhao (Molecular and Cellular Biochemistry, 2025)

From the Atlantic-Mediterranean to the Western Pacific: First record of potentially harmful invasive gilthead sea bream (Sparus aurata) in the Northern Taiwan - Yen-Ting Lin; Yu-San Han (Marine Pollution Bulletin, 2025)

Light-driven zinc oxide quantum dots control pear fire blight disease by inhibiting pathogen growth and modulating plant defense response - Lanlan Sun; Haodong Wang; Cancan Qian; Zhixu Hu; Zizheng Xie; Guoqiang Zhang; Xiaoqiang Han; Chunjuan Wang; Ting Ma; Desong Yang (Pesticide Biochemistry and Physiology, 2025)

Peptide neurotoxins affecting insect voltage-gated calcium channels and possessing insecticidal toxicity: Two ω-Atypitoxins from Calommata signata - Yang-yang Yan; Kan Wang; Jing-ting Wang; Qian-qian Han; Zhen Zhang; Na Yu; Ze-Wen Liu (Pesticide Biochemistry and Physiology, 2025)

The mechanism of selective dispersion between micro-fine titanaugite and ilmenite particles caused by acid surface pretreatment in pulp - Yusheng Du; Qingyou Meng; Chong Han; Zhitao Yuan; Lixia Li; Jiwei Lu; Ting Liu (Minerals Engineering, 2025)

Synchronous nitrogen and sulfur removal in sulfur-coated iron carbon micro-electrolytic fillers: Exploring the synergy between sulfur autotrophic denitrification and iron-carbon micro-electrolysis - Yanhe Han; Jing Wang; Ting Liu; Mengxiang Wei; Shizong Wang; Jingxuan Guo; Xuejiao Ma; Zaixing Li; Nannan Wang; Yimin Sang (Journal of Hazardous Materials, 2025)

The influence of PM2.5 exposure on SARS-CoV-2 infection via modulating the expression of angiotensin converting enzyme II - Meng-Wei Lin; Cheng-Han Lin; Jia-Rong Chang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chih-Sheng Lin (Journal of Hazardous Materials, 2025)

Preparation of Ti/RuO2-IrO2 electrodes and their application in broad-spectrum electrochemical detection of COD - Yanhe Han; Qingpeng Zhao; Ting Liu; Lina Liu; Xuejiao Ma; Nannan Wang (Journal of Environmental Management, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

S–Mo conversion stimulates soil electron transfer and hydrocarbon removal for nearly one year - Jialu Sun; Xiaojuan Yi; Yuewei Yang; Yun Zhang; Xin Yu; Side Yang; Xiaolin Zhang; Ting Han; Xinhong Peng; Xiaojing Li (Chemical Engineering Journal, 2025)

Heterogenic membrane-coated nanoparticles for targeted immunotherapy against osteosarcoma via p53-mediated ferroptosis and mTOR inhibition - Ting Lei; Zichao Jiang; Jiangyu Nan; Han Fan; Junxiao Yang; Yiyi Wang; Long Hua; Hu Qian; Yihe Hu (Chemical Engineering Journal, 2025)

Electron delocalization engineering via hierarchical modulation in single-atom catalysts for highly efficient electrochemical CO2 reduction - Xu Han; Hong Liu; Pengfei Cao; Weiqiang Tang; Chao Yue Zhang; Martí Biset-Peiró; Ke Xiao; Pengyi Tang; Marc Heggen; Miquel Vega-Paredes; Alba Garzón Manjón; Lirong Zheng; et al. (Chemical Engineering Journal, 2025)

ε-Polylysine-mediated assembly regulating the band gap of natural polyphenols for boosted photodynamic antimicrobial effect - Ximei Han; Qian Wang; Jiaqi Mi; Jie Zhang; Jianxing Feng; Ting Du; Linpin Luo; Chaoqun Zhang; Jianlong Wang; Wentao Zhang (Chemical Engineering Journal, 2025)

Dual physically crosslinked azobenzene liquid crystal elastomers programmable for multi-modal information encryption - Jia-Xin Yang; Xue-Li Zhang; Lu Yin; Jie Jiang; Ting Liu; Jing-Yu Liu; Zhi-Ting Xu; Hong-Yuan Bai; Hong-Wei Ma; Yue Zhao; Yang Li; Li Han (Chemical Engineering Journal, 2025)

Inhibition of the canonical Wnt/β-catenin pathway interferes with macropinocytosis to suppress pseudorabies virus proliferation - Chongyang Wang; Ting Wang; Qingrun He; Qili Hou; Liuyuan Duan; Ruochen Hu; Yu Han; Yongchun Yang; Houhui Song; Zengqi Yang (Veterinary Microbiology, 2025)

Atractylenolide III ameliorates DSS-induced colitis by improving intestinal epithelial barrier via suppressing the NF-κB-Mediated MLCK-pMLC signaling pathway - Ting-ting Dai; Wei Fang; Wen-tao Zhu; Zhi-li Han; Nian-xia Sun; Gang Yin; Dian-lei Wang (Food and Chemical Toxicology, 2025)

Ions and electrons dual transport channels regulated by nanocellulose for mitigating dendrite growth of zinc-ion batteries - Han Zhang; Meng Zhang; Ting Xu; Xuan Wang; Junjie Qi; Yaxuan Wang; Wei Liu; Liyu Zhu; Zhanhui Yuan; Chuanling Si (Chemical Engineering Journal, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Dorsal CA1 NECTIN3 Reduction Mediates Early-Life Stress-Induced Object Recognition Memory Deficits in Adolescent Female Mice - Yu-Nu Ma; Chen-Chen Zhang; Ya-Xin Sun; Xiao Liu; Xue-Xin Li; Han Wang; Ting Wang; Xiao-Dong Wang; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2025)

Characterizing immune responses of grey mullet (Mugil cephalus) to Nocardia seriolae ex vivo and in vivo - Ya-Ting Wang; Chien-Yueh Lee; Ching-Hung Chan; Liang-Chuan Lai; Mong-Hsun Tsai; Eric Y. Chuang; Li-Han Chen (Aquaculture International, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Taste receptor T1R3 regulates testosterone synthesis via the cAMP-PKA-SP1 pathway in testicular Leydig cells - Wenjiao Liu; Han wang; Qi Mu; Ting Gong (Theriogenology, 2025)

The functional regulation between extracellular vesicles and the DNA damage responses - Jinyi Han; Kexin Xu; Ting Xu; Qin Song; Ting Duan; Jun Yang (Mutation Research - Reviews in Mutation Research, 2025)

Iron‑carbon micro-electrolysis and anaerobic-aerobic activated sludge integrated process for treating landfill leachate: Process optimization, stability, and mechanism - Yanhe Han; Jingxuan Guo; Ting Liu; Nannan Wang; Zhimin Su; Shizong Wang; Xuejiao Ma; Jing Wang; Fan Zhao (Journal of Water Process Engineering, 2025)

Magnetic field inhibited the deterioration of frozen dough via promoting the interaction between starch and gluten - Ting-Shi He; Han Tao; Mei Liu (Journal of Cereal Science, 2025)

Antimicrobial efficacy of carvacrol-loaded curdlan hydrogels for enhancing shelf-life in seafood packaging applications - Hong-Ting Victor Lin; Yi-Chi Yu; Shu-Han Yu; Yu-Chieh Chou; Hsuan-Ju Lin; Shella Permatasari Santoso; Shin-Ping Lin (International Journal of Food Microbiology, 2025)

Photodynamic inactivation mediated by natural alizarin on bacteria for the safety of fresh-cut apples - Xiang Li; Zhenqing Guo; Yikai Song; Ting Du; Feiya Han; Shaochi Wang; Jianxing Feng; Jianlong Wang; Wentao Zhang (Food Research International, 2025)

Dynamic changes in the metabolome and microbiome during Citrus depressa Hayata liquid fermentation - Ta-Wei Liu; Benni Iskandar; Man-Hsiu Chu; Yun-Han Wang; Ting-An Huang; Su-Jung Hsu; Yves S.Y. Hsieh; Ching-Kuo Lee (Food Chemistry, 2025)

New fast imaging techniques for electrical source transient electromagnetic data: Approaches and application - Yu-lian Zhu; Wei-ying Chen; Wan-ting Song; Si-xu Han (Computers & Geosciences, 2025)

Functionalities and properties of conductive hydrogel with nanocellulose integration - Meng Zhang; Ting Chen; Ting Xu; Han Zhang; Xuan Wang; Junjie Qi; Qiang Dong; Liyu Zhu; Zhanhui Yuan; Chuanling Si (Chemical Engineering Journal, 2025)

Memristive behavior of ferrocene-functionalized polymer for artificial nociceptor application - Huiying Liu; Miao Zhang; Minghao Jiang; Su-Ting Han; Wai-Yeung Wong (Chemical Engineering Journal, 2025)

Early life long-term exposure to aflatoxin B1 induces aging and alters innate immunity associated with SKN-1/Nrf2 in Caenorhabditis elegans - Tzu-Ting Chang; Chun-Han Chang; Vivian Hsiu-Chuan Liao (Chemico-Biological Interactions, 2025)

Effects of Methyl Jasmonate on Physiological Characteristics and Drought Resistance of Alfalfa (Medicago sativa) and Ryegrass (Lolium perenne L.) - Ting Wei; Han Gao; Daizhong Yang; Gang Zhu; Chunping Zhang; Baocun Wang; Honglei Jia; Chao Zhang; Junkang Guo (Journal of Plant Growth Regulation, 2025)

Advancements in nanoscale delivery systems: optimizing intermolecular interactions for superior drug encapsulation and precision release - Enpeng Dong; Qingqing Huo; Jie Zhang; Hanghang Han; Ting Cai; Dongfei Liu (Drug Delivery and Translational Research, 2025)

Cadmium Exposure was Associated with Sex-Specific Thyroid Dysfunction: Consistent Evidence from Two Independent Cross-Sectional Studies Based on Urinary and Blood Cadmium Measurements - Ranqi Shao; Liqin Su; Peng Wang; Xu Han; Ting Wang; Jun Dai; Yi Gu; Jiao Luo; Lifang Deng; Jingping Liu (Biological Trace Element Research, 2025)

Changes in the small-molecule fingerprints of rice planted near an industrial explosion site in Taiwan - Wen-Ling Chen; Husan-Yu Tai; Chang-Chuan Chan; Hung-Chien Lin; Ting-Hsuan Hung; Mong-Hsun Tsai; Chia-Cheng Wei; Yu-San Han; Chuan-Chou Shen (Environmental Science and Pollution Research, 2024)

Early postnatal and concurrent exposure to metals and neurobehavioral outcomes at 5 years: Associations with individual environmental exposures and mixtures - Sui-Ling Liao; Shen-Hao Lai; Yuan-Ting Hsu; Li-Chen Chen; Ming-Han Tsai; Man-Chin Hua; Tsung-Chieh Yao; Kuan-Wen Su; Kuo-Wei Yeh; Chih-Yung Chiu; Shau-Ku Huang; Jing-Long Huang (NeuroToxicology, 2024)

Ammonia oxidation with bicarbonate as an electron acceptor: An energy-saving process to accumulate nitrite for potential anammox in wastewater - Jingang Huang; Shilin Wen; Binfang Shi; Yujian Wang; Chenglei Sun; Dong Zhang; Wei Han; Ting Lü; Xiaobin Xu; Haibo Wang (Journal of Water Process Engineering, 2024)

Di(2-ethylhexyl) phthalate disrupts circadian rhythm associated with changes in metabolites and cytochrome P450 gene expression in Caenorhabditis elegans - Pei-Ling Yen; Ting-An Lin; Chun-Han Chang; Chan-Wei Yu; Yu-Hsuan Kuo; Tzu-Ting Chang; Vivian Hsiu-Chuan Liao (Environmental Pollution, 2024)

Preparation of carboxylic cellulose nanofibrils via FeCl3-catalyzed maleic acid hydrolysis and application for self-supporting electrode - Xuan Wang; Ting Xu; Han Zhang; Junjie Qi; Yaxuan Wang; Meng Zhang; Wei Liu; Zhanhui Yuan; Chuanling Si (Chemical Engineering Journal, 2024)

In-situ immobilization of Fe PBA in the zeolite structure for efficient degradation of benzalkonium chloride: Towards compressed reaction site loss and promoted PMS utilization - Qing Zhong; Ting Zhang; Zhi Huang; Longhui Su; Yuwei Xue; Ran Gao; Han Feng; Junming Hong (Chemical Engineering Journal, 2024)

Interaction of biochar with extracellular polymers of resistant bacteria restrains Pb(II) adsorption onto their composite: Macro and micro scale investigations - Di Wang; Hansong Chen; Hui Han; Wenwen Yang; Qi Sun; Churong Cao; Kai Ning; Zhuochun Huang; Ting Wu (Bioresource Technology, 2024)

Exosomes-Shuttled lncRNA SNHG7 by Bone Marrow Mesenchymal Stem Cells Alleviates Osteoarthritis Through Targeting miR-485-5p/FSP1 Axis-Mediated Chondrocytes Ferroptosis and Inflammation - Yue Wang; Kaili Hu; Changdi Liao; Ting Han; Fenglin Jiang; Zixin Gao; Jinhua Yan (Tissue Engineering and Regenerative Medicine, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

Exploring the Updated Roles of Ferroptosis in Liver Diseases: Mechanisms, Regulators, and Therapeutic Implications - Ting Ge; Yang Wang; Yiwen Han; Xiaofeng Bao; Chunfeng Lu (Cell Biochemistry and Biophysics, 2024)

Impact of acid surface pretreatment on the hydrophobic agglomeration of micro-fine ilmenite and titanaugite in flotation - Yusheng Du; Qingyou Meng; Zhitao Yuan; Chong Han; Lixia Li; Jiwei Lu; Ting Liu (Minerals Engineering, 2024)

Hydrogen purification via hydrate-based methods: Insights into H2-CO2-CO hydrate structures, thermodynamics, and kinetics - Ying Teng; Yinlong Li; Ting Huang; Yiqi Chen; Pengfei Wang; Bin Wang; Senyou An; Yun Li; Songbai Han; Jinlong Zhu; Yuze Wang; Bin Chen; et al. (Gas Science and Engineering, 2024)

Effects of nitrile compounds on the structure and function of soil microbial communities as revealed by metagenomes - Ting Gao; Yiwang Wang; Jinlong Lai; Fuli Wang; Ge Yao; Shaoheng Bao; Jiajia Liu; Xiukun Wan; Chang Chen; Yunfei Zhang; Hui Jiang; Shijie Jiang; et al. (Environmental Research, 2024)

YAP O-GlcNAcylation contributes to corneal epithelial cell ferroptosis under cigarette smoke exposure - Meng-Yuan Zhang; Ting-Ting Wei; Cheng Han; Cheng-Ye Tan; Tian-Hua Xie; Jiping Cai; Yong Yao; Lingpeng Zhu (Environmental Pollution, 2024)

Exposure to organophosphate esters and early menopause: A population-based cross-sectional study - Ting Zhang; Ruxianguli Aimuzi; Xiaowei Lu; Bin Liu; Han Lu; Kai Luo; Junkai Yan (Environmental Pollution, 2024)

Introducing electron-rich thiophene bridges in hot exciton emitter for efficient non-doped near-infrared OLEDs with low turn-on voltages - Ruming Jiang; Zhangshan Liu; Yuanyuan Han; Jiawei Long; Ting Guo; Xia Lan; Mingguang Yu; Ting Fan; Haijun Ma; Yen Wei; Ben Zhong Tang; Zujin Zhao (Chemical Engineering Journal, 2024)

A fluorine-free bioinspired multifunctional slippery coating for ultra-long-term anticorrosion of Mg alloy, static/dynamic anti-icing, antibacterial and antifouling - Wenliang Zhang; Shuyi Li; Dongsong Wei; Yafei Shi; Ting Lu; Zhen Zhang; Zhiwu Han; Yan Liu (Chemical Engineering Journal, 2024)

Nanocellulose/metal-organic frameworks composites for advanced energy storage of electrodes and separators - Junjie Qi; Meng Zhang; Ting Xu; Kun Liu; Yaxuan Wang; Han Zhang; Xuan Wang; Zhanhui Yuan; Chuanling Si (Chemical Engineering Journal, 2024)

Zinc hexacyanoferrate with open framework for efficient aqueous cobalt ions storage - Wenbo Guo; Zening Wu; Shuyuan Zhao; Jichen Zhao; Xue Han; Boao Wanyan; Jiehua Wang; Lei Yan; Liyuan Zhang; Haoxiang Yu; Ting-Feng Yi; Jie Shu (Chemical Engineering Journal, 2024)

Strategies, techniques and applications for food authentication based on carbohydrates: A review - Li-feng Li; Xi Shi; Si-min Qi; Xue-ting Zhang; Hau-Yee Fung; Qian-ran Li; Quan-bin Han (Carbohydrate Polymers, 2024)

Effect of black soldier fly larvae frass addition on humus content during low temperature co-composting - Ruju Zhang; Yingpeng Zhang; Yonglan Xi; Jin Zhou; Ting Han; Qiuqin Ma; Cong Wang; Fei Zhu; Xiaomei Ye (Bioresource Technology, 2024)

GhMAC3e is involved in plant growth and defense response to Verticillium dahliae - Zhenghong Han; Yuanyuan Qiu; Ting Pan; Longjie Wang; Jing Wang; Kang Liu (Plant Cell Reports, 2024)

Early developmental levels of children with autism spectrum disorder with different adaptive behaviors: a retrospective analysis - Chao Song; Ting Han; Lifei Hu; Ning Shao; Zepeng Wang; Yan Jin; Tingting Chen; Zhiwei Zhu (Journal of Zhejiang University-SCIENCE B, 2024)

Photoelectron-transfer-effect grafting: Validation of a generalized strategy for fluorescence and photoelectrochemical dual-mode detection of hydrogen sulfide - Xiao-Jie Yu; Xiao-Yan Wan; Yu-Ting Shen; Deng-Bao Zhang; Xian-Jing Zhou; De-Man Han; Feng-Zao Chen (Analytica Chimica Acta, 2024)

Hepatic and metabolic outcomes induced by sub-chronic exposure to polystyrene microplastics in mice - Sheng-Han Lee; Ting-An Lin; Yuan-Horng Yan; Chu-Chun Chien; Tsun-Jen Cheng (Archives of Toxicology, 2024)

Mercaptopropionic acid-capped CdZnTe Quantum dots as Fluorescence Probe for Sensitive Detection of Cr(III) ions - Min Wu; Dongmei Zeng; Shuo Han; Minmin Zou; Ting Zhang; You Zhang (Journal of Fluorescence, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Discovering transformation products of pharmaceuticals in domestic wastewaters and receiving rivers by using non-target screening and machine learning approaches - Yu Han; Li-Xin Hu; Ting Liu; Liang-Li Dong; You-Sheng Liu; Jian-Liang Zhao; Guang-Guo Ying (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Potential powered EC-SERS for sensitive detection of acetamiprid - Ting Wu; Xuemei Tang; Wei Zeng; Yu Han; Sihang Zhang; Jing Wei; Long Wu (Journal of Food Engineering, 2024)

The disruptive effect on the bacterial cell wall explored of the ultrasmall particle-sized Ag nanoparticles supported with Zn Cu-based hybrid nanoagents - Shaobo Guo; Xu Liu; Huihui Chen; Yanming Qiao; Zhifeng Liu; Dan Zhang; Guo Ting; Xiaohui Ji; Hao Han; Tanlei Zhang (Journal of Environmental Chemical Engineering, 2024)

Characterization of phospholipidome in milk, yogurt and cream, and phospholipid differences related to various dairy processing methods - Yue-Han Liu; Ting-Ting Liu; Jing-Qi Niu; Xue-Song Zhang; Wei-Sheng Xu; Shuang Song; Zhu Wang (Food Chemistry, 2024)

Assessing health risks from bioaccessible PM2.5-bound toxic metals in Nanchang metro: Implications for metro workers and emissions control - Shan Huang; Minglei Han; Peixian Chen; Weiwei Feng; Guobo Li; Hongxiang Zhang; Honggen Peng; Ting Huang (Environmental Research, 2024)

Temperature effects on ion migration and energy consumption during brackish water electrodialysis desalination - Zekun Yang; Luyao Ren; Qing-Bai Chen; Yong Xu; Ting Han; Yang Gao; Jianyou Wang (Desalination, 2024)

The role of rhamnolipids in the growth and defense responses of passion fruit plants - Ting Yang; Jihu Li; Yongkai Mao; Han Wu; Mingjiang Lin; Lijuan Chen (Physiology and Molecular Biology of Plants, 2024)

Thalamic Nucleus Reuniens Glutamatergic Neurons Mediate Colorectal Visceral Pain in Mice via 5-HT2B Receptors - Di Li; Han Du; Shu-Ting Qu; Jing-Lai Wu; Yong-Chang Li; Qi-Ya Xu; Xia Chen; Xiao-Xuan Dai; Ji-Tian Xu; Qian Wang; Guang-Yin Xu (Neuroscience Bulletin, 2024)
Irritable bowel syndrome (IBS) is a common functional bowel disorder characterized by abdominal pain and visceral hypersensitivity. Reducing visceral hypersensitivity is the key to effectively relieving abdominal pain in IBS. Increasing evidence has confirmed that the thalamic nucleus reuniens (Re) and 5-hydroxytryptamine (5-HT) neurotransmitter system play an important role in the development of colorectal visceral pain, whereas the exact mechanisms remain largely unclear. In this study, we found that high expression of the 5-HT 2B receptors in the Re glutamatergic neurons promoted colorectal visceral pain. Specifically, we found that neonatal maternal deprivation (NMD) mice exhibited visceral hyperalgesia and enhanced spontaneous synaptic transmission in the Re brain region. Colorectal distension (CRD) stimulation induced a large amount of c-Fos expression in the Re brain region of NMD mice, predominantly in glutamatergic neurons. Furthermore, optogenetic manipulation of glutamatergic neuronal activity in the Re altered colorectal visceral pain responses in CON and NMD mice. In addition, we demonstrated that 5-HT 2B receptor expression on the Re glutamatergic neurons was upregulated and ultimately promoted colorectal visceral pain in NMD mice. These findings suggest a critical role of the 5HT 2B receptors on the Re glutamatergic neurons in the regulation of colorectal visceral pain.

Rice-crayfish integrated system enhances global warming potential via increasing methane emission mainly driven by continuous deep flooding - Linjie Ma; Chengxin Zhang; Baoli Qin; Jun Yang; Ting Yang; Rong Xu; Guangming Han; Shouhong Wang; Jiahong Zhang; Xiangming Kou (Applied Soil Ecology, 2024)

One new 12, 8-guaianolide sesquiterpene lactone with antihyperglycemic activity from the roots of Cichorium intybus - Xiu-hua Meng; Yin-an Pan; Han Lv; Xiao-qin Ding; De-quan Yin; Ya-nan Gai; Guan-ting Niu; Bing-ru Ren; Xiao-guo Qian; Jian Chen (Natural Product Research, 2024)

Non-target discovery and risk prediction of per- and polyfluoroalkyl substances (PFAS) and transformation products in wastewater treatment systems - Ting Liu; Li-Xin Hu; Yu Han; Sheng Xiao; Liang-Li Dong; Yuan-Yuan Yang; You-Sheng Liu; Jian-Liang Zhao; Guang-Guo Ying (Journal of Hazardous Materials, 2024)

Effects of polysaccharides on colonic targeting and colonic fermentation of ovalbumin-ferulic acid based emulsion - Hesheng Liu; Zhenzhen Huang; Ting Xin; Lihong Dong; Mei Deng; Lipeng Han; Fei Huang; Dongxiao Su (Food Chemistry, 2024)

High-rate pig manure substitution enhances comammox Nitrospira abundance and diversity in the Cinnamomum camphora coppice planting soils - Luyuan Sun; Jie Zhang; Jia Liu; Jiao Zhao; Ting Zhang; Fengyi Han; Zi-Yang He; Yongxin Lin (European Journal of Soil Biology, 2024)

The effects of the clean air actions on the Beautiful China initiative: The regional heterogeneity analysis - Han Wang; Junhao Chen; Wentao Lu; Jingqiao Zhang; Ting Cao; Yao Zhu; Haiyang Lv; Zheng Liu; Shulan Wang (Environmental Impact Assessment Review, 2024)

Visible light-responsive vitamin B2 functionalized ZnO with dual-mechanism bactericidal effects for perishable agrofood preservation - Jianxing Feng; Zhenqing Guo; Runli Li; Chaoqun Zhang; Ting Du; Xiang Li; Xuewei Yang; Junchen Zhuo; Yanmin Liang; Yaru Han; Jianlong Wang; Shuo Shi; et al. (Chemical Engineering Journal, 2024)

A systematic investigation of PVDF-HFP in perovskite solar cells for improved space mission reliability - Seoungjun Ahn; Wei-Hao Chiu; Wei-Chen Chu; Pei-Yu Chen; Ting-Han Lin; Kun-Mu Lee (Chemical Engineering Journal, 2024)

Constructing interfacial chemical interaction of dual-carbon protected cobalt diselenide anode for sodium storage - Xiaoying Liu; Dongdong Xue; Rui Ren; Ting Ou; Tao Sun; Yuchen Han; Fan Jin; Yannan Li; Yan Zhao; Jiangwei Zhang (Chemical Engineering Journal, 2024)

The impacts of photochemical loss on the source apportionment of ambient volatile organic compounds: A case study in Northern China - Jingqiao Zhang; Zheng Liu; Yajun Wu; Yao Zhu; Ting Cao; Deyin Ling; Han Wang; Shulan Wang (Atmospheric Environment, 2024)

Potential failure mechanism of a rock slope with weak intercalated layer and the reinforcement effect evaluation - Hai-Ning Liu; Su-Zhen Duan; Ting-Song Yan; Han-Dong Liu; Dong-Dong Li (Natural Hazards, 2024)

Exploring Research Trend and Hotspots on Oxidative Stress in Ischemic Stroke (2001–2022): Insights from Bibliometric - Nan Jiang; Ting Yang; Hongxia Han; Jing Shui; Miaomiao Hou; Wenyue Wei; Gajendra Kumar; Lijuan Song; Cungen Ma; Xinyi Li; Zhibin Ding (Molecular Neurobiology, 2024)

Abundance and health risk of bioaerosols in the coastal areas of Qingdao, China - Lingchong Yan; Ting Zhang; Shaohua Sun; Yongzhong Song; Chen Han; Yao Wang; Jianhua Qi; Xianguo Li; Dahai Zhang (Aerobiologia, 2024)

Performances of full-scale biological nitrogen pre-treatment process for drinking water source: Seasonal variations and microbial community - Hai-Hsuan Cheng; Yee Han Hew; Yi-Ju Wu; Tin-Yin Chen; Yi Ting Chiu; Li Ying Chen; Tsair-Fuh Lin; Liang-Ming Whang (Chemosphere, 2024)

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Effect of dietary krill oil levels on the regulation of ovary development in Pacific white shrimp (Litopenaeus vannamei) broodstock - Xiaolong Liang; Chang Xu; Ping Wang; Tong Chang; Xianming Xiao; Ting Li; Fenglu Han; Erchao Li (Aquaculture, 2024)

Late Pliocene Bauhinia s.l. (Cercidoideae, Fabaceae) fossils from Tengchong, Yunnan, southwestern China - Rui Cao; Zhi-hui Song; Zhuo-er Wang; Zhao-shuai Wang; Han-shi Li; Jing-Yu Wu; Su-Ting Ding (Review of Palaeobotany and Palynology, 2024)

Movement of ACC oxidase 3 mRNA from seeds to flesh promotes fruit ripening in apple - Ting Wang; Yi Zheng; Chen Xu; Yulin Deng; Xinyi Hao; Zicheng Chu; Ji Tian; Yi Wang; Xinzhong Zhang; Zhenhai Han; Ting Wu (Molecular Plant, 2024)

Complete genome sequence of a novel Pseudomonas sp. IT1137 isolated from Antarctic intertidal sediment showing potential for alkane degradation at low temperatures - Hui-Yan Ge; Yi-He Zhang; Yong-Qiang Hu; Wei Han; Yu Du; Ting Hu; Yin-Xin Zeng (Marine Genomics, 2024)

Recycling alginate-like extracellular polymers (ALE) from municipal sludge: Value-added products and external impact - Ming Cheng; Chen Shi; Bo-Han Zhao; Nan Zhang; Qing-Yue Shen; Li-Ting Hao; Xiang-Yang Wang (Chemical Engineering Journal, 2024)

Effects of Salt Content and Freeze-Thaw Conditions on Dynamic characteristics and its microscopic mechanism of Chloride Silty Clay - Yaqin Zhang; Ping Yang; Lin Li; Ting Zhang; Linliang Han (Cold Regions Science and Technology, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

Effects of Tetraselmis subcordiformis (Wille) Butcher with antimicrobial peptides as feed additives on gut microbial community and immunity of turbot (Scophthalmus maximus L.) - Bingkui Zhu; Fengjie Sun; Zhengquan Gao; Ting Yao; Subing Han; Hao Zhang; Yuyang Ma; Yuyong Wu; Ran Du; Chunxiao Meng; Yulin Cui (Journal of Applied Phycology, 2024)

Insights into sunlight-driven transformation of tetracycline by iron (hydr)oxides: The dominating role of self-generated hydrogen peroxide - Shiwen Li; Jianming Pang; Wei Han; Ting Chang; Lingen Luo; Xian Li; Jue Liu; Hefa Cheng (Water Research, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

Distribution characterization of MPs and DOM in ice-covered season in a saline-alkaline Lake in Daihai with an innovative analysis using 2DCOS and structural equation modelling - Ting Pan; Fang Yang; Haiqing Liao; Zhiming Han; Meichen Ji; Qianqian Wang; Hao Yang; Matti Leppäranta (Journal of Hydrology, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

Engineering hyperthermophilic pullulanase to efficiently utilize corn starch for production of maltooligosaccharides and glucose - Ting Xie; Li Zhou.; Laichuang Han; Cuiping You; Zhongmei Liu; Wenjing Cui; Zhongyi Cheng; Junling Guo; Zhemin Zhou (Food Chemistry, 2024)

Microscopic identification of foodborne bacterial pathogens based on deep learning method - Qiong Chen; Han Bao; Hui Li; Ting Wu; Xin Qi; Changqiang Zhu; Weilong Tan; Desheng Jia; Dongming Zhou; Yong Qi (Food Control, 2024)

Incorporating ε-polylysine hydrochloride, tea polyphenols, nisin, and ascorbic acid into edible coating solutions: Effect on oxidation and structure of marinated egg proteins - Jingbo Liu; Lu Han; Dongkun Cheng; Shengrao Li; Xiumei Chen; Yiding Yu; Deju Zhang; Ting Zhang (Food Control, 2024)

UV-filter benzophenones suppress human, pig, rat, and mouse 11β-hydroxysteroid dehydrogenase 1: Structure-activity relationship and in silico docking analysis - Ting Hao; Xin Zhao; Zhongyao Ji; Miaomiao Xia; Han Lu; Jianmin Sang; Shaowei Wang; Linxi Li; Ren-shan Ge; Qiqi Zhu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Antibiotic resistome in landfill leachate and impact on groundwater - Wei-Li Jia; Min Zhang; Fang-Zhou Gao; Hong Bai; Lu-Xi He; Liang-Ying He; Ting Liu; Yu Han; Guang-Guo Ying (Science of The Total Environment, 2024)

Partially knocking out NtPDK1a/1b/1c/1d simultaneously in Nicotiana tabacum using CRISPR/CAS9 technology results in auxin-related developmental defects - Qian-Wei Ren; Tian-Yao Liu; Hu-Jiao Lan; Zhen-Chao Li; Min-Jun Huang; Ya-Ting Zhao; Yu Chen; Li-Na Liao; Xiao-Han Ma; Jian-Zhong Liu (Plant Science, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Species selection as a key factor in the afforestation of coastal salt-affected lands: Insights from pot and field experiments - Tzu-Hao Su; Yang Shen; Yao-Yu Chiang; Yu-Ting Liu; Han-Ming You; Hung-Chih Lin; Kuan-Ning Kung; Yao-Moan Huang; Chih-Ming Lai (Journal of Environmental Management, 2024)

Chat3D: Interactive understanding 3D scene-level point clouds by chatting with foundation model for urban ecological construction - Yiping Chen; Shuai Zhang; Ting Han; Yumeng Du; Wuming Zhang; Jonathan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Emulsion stability enhancement against storage and environment stresses using complex plant protein and betanin - Qin Geng; Ting Hu; Jun Chen; Changhong Li; Ti Li; Xuemei He; Jialong Han; Chengmei Liu; Taotao Dai (Food Bioscience, 2024)

Effects of adding Bacillus subtilis natto NTU-18 in paste feed on growth, intestinal morphology, gastrointestinal microbiota diversity, immunity, and disease resistance of Anguilla japonica glass eels - Yen-Ting Lin; Yu-Chen Hung; Li-Han Chen; Kung-Ta Lee; Yu-San Han (Fish & Shellfish Immunology, 2024)

Condition assessment of stay cables using normalized sequence of vehicle-induced cable force peaks of stay cables on same side - Jin-Xin Li; Chun-Xu Qu; Ting-Hua Yi; Hong-Nan Li; Qiang Han (Engineering Structures, 2024)

From theory to practice: Dissociation of AsMA under reactive metal perturbations for the harmlessness and resourcefulness of copper slag - Xingyuan Wan; Kaixi Jiang; Ting'an Zhang; Kun Wang; Han Yang; Shengnan Lin (Chemical Engineering Journal, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

Metabolomic profiling of maternal plasma identifies inverse associations of acetate and urea with anti-SARS-CoV-2 antibody titers following COVID-19 vaccination during pregnancy - An-Shine Chao; Chiao-Yun Lin; Meng-Han Chiang; Kuan-Ying Lu; Cheng-Kun Tsai; Kuan-Ju Chen; Chih-Wei Chien; Ting-Shu Wu; Yao-Lung Chang; Angel Chao; Gigin Lin; Chih-Yung Chiu (Journal of Molecular Medicine, 2024)

Mining, screening, and validation of cold-resistance molecular markers in Vitis vinifera L. - Zhi-Lei Wang; Xing Han; Wen-Long Ma; Guo-Qian Xu; Ting-Ting Xue (Euphytica, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Morphological characteristics, genetic diversity, and ethnobotanical uses of Citrus hongheensis (Rutaceae), an endangered species - Feng-Juan Mou; Jian-Qin Li; Yu-Hong Gao; Yue-Yan Li; Ting-Yao Meng; Shun-Long Han (Plant Biosystems, 2024)

Discrete recoil control system modelling and optimal recoil damping of deepwater drilling riser systems - Bao-Lin Zhang; Yue-Ting Sun; Yan-Dong Zhao; Qing-Long Han; Xian-Ming Zhang; Zhihui Cai (Ocean Engineering, 2024)

A hydrological process-based neural network model for hourly runoff forecasting - Shuai Gao; Shuo Zhang; Yuefei Huang; Jingcheng Han; Ting Zhang; Guangqian Wang (Environmental Modelling & Software, 2024)

Condition monitoring for bridge cables using time-history area of cable forces under stochastic traffic flow - De-Long Li; Dong-Hui Yang; Ting-Hua Yi; Song-Han Zhang; Hong-Nan Li (Engineering Structures, 2024)

Isolation of Rhizobacteria from Crocus Sativus L. Rhizosphere and Their Effects on Host-Growth Promotion - Jing-Chao Xu; Xing-Guang Xie; Xue-Wen Bi; Jia-Hao Zhang; Zi-Hui Zhao; Khalid Rahman; Bo Zhu; Lu-Ping Qin; Ting Han (Journal of Plant Growth Regulation, 2024)

Decreased snow depth inhibits litter decomposition via changes in litter microbial biomass and enzyme activity - Ting Du; Li Zhang; Yulian Chen; Yu Zhang; Hemeng Zhu; Zhenfeng Xu; Bo Tan; Chengming You; Yang Liu; Lixia Wang; Sining Liu; Hongwei Xu; et al. (Science of The Total Environment, 2024)

Complete genome sequence of the novel Antarctic Oceanisphaera sp. IT1–181 that carried five plasmids - Yong-Qiang Hu; Yi-He Zhang; Wei Han; Ting Hu; Yu Du; Yin-Xin Zeng (Marine Genomics, 2024)

The interplay of Cxcl10+/Mmp14+ monocytes and Ccl3+ neutrophils proactively mediates silica-induced pulmonary fibrosis - Demin Cheng; Wenxiu Lian; Ting Wang; Sichuan Xi; Xinying Jia; Ziwei Li; Haojie Xiong; Yue Wang; Wenqing Sun; Siyun Zhou; Lan Peng; Lei Han; et al. (Journal of Hazardous Materials, 2024)

Motivating more people to engage in online green behavior: A multi-agent simulation study of Ant Forest - Lingyun Mi; Lulu Jiang; Ting Xu; Jiali Han; Yajie Zhu; Lijie Qiao; Wenshun Wang; Miaomiao Niu (Journal of Cleaner Production, 2024)

Sulfate-functionalized Fe-based MOF for removal of Pb(Ⅱ) and NO3- in industrial wastewater - Rui-Dong Wang; Wen-Qian Zhang; Hong-Bo Lv; Yan-Ting Chen; Lei Wang; Si-Han Zhou; Lin Du; Qi-Hua Zhao (Journal of Environmental Chemical Engineering, 2024)

In vitro and in vivo genome-based safety evaluation of Lacticaseibacillus rhamnosus LRa05 - Ting Chen; Yawen Shao; Yinan Zhang; Yunjiao Zhao; Mei Han; Zhonghui Gai (Food and Chemical Toxicology, 2024)

Demethoxylation of curcumin enhances its inhibition on human and rat 17β-hydroxysteroid dehydrogenase 3: QSAR structure-activity relationship and in silico docking analysis - Zhongyao Ji; Jianmin Sang; Hong Wang; Miaomiao Xia; Ting Hao; Liping Chen; Han Lu; Shaowei Wang; Ming Yao; Linxi Li; Ren-shan Ge (Food and Chemical Toxicology, 2024)

Tunable schiff-based networks with different bonding sites for enhanced photocatalytic activity under visible-light irradiation: The effects of steric hindrance - Han Wang; Piao Xu; Eydhah Almatrafi; Ziwei Wang; Chengyun Zhou; Ting Xiong; Hong Qin; Yangzhuo He; Hailan Yang; Zhuotong Zeng; Guangming Zeng (Environmental Research, 2024)

The angiogenesis-modulating effects of coumarin-derivatives - Han-Ting Huang; Ching-Yuan Huang; Chih-Jou Lee; Bo-Jie Sun; Zong-Wei Jhang; Chi-Chung Wen; Yun-Hsin Wang; Tao-Sheng Li; Ching-Yuh Chern; Yau-Hung Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Recent advances on covalent organic framework-based membranes for ion selective sieving and wastewater resource utilization - Yue Wang; Luyao Ren; Haoxue Wang; Jianyou Wang; Qing-bai Chen; Ting Han (Chemical Engineering Journal, 2024)

Interactive effects of soil erosion and mechanical compaction on soil DOC dynamics and CO2 emissions in sloping arable land - Huizhou Gao; Xiaojun Song; Xueping Wu; Naiyu Zhang; Ting Liang; Zhufeng Wang; Xun Yu; Chengjiao Duan; Zixuan Han; Shengping Li (CATENA, 2024)

Effects of tree density variations on outdoor heritage conservation: Numerical study of an ancient brick city wall with four orientations - Ting Zhang; Changchang Xia; Yan Ma; Ruohan Zhang; Shuai Han; Zhenyi Kong; Shuichi Hokoi; Yonghui Li (Building and Environment, 2024)

Oral Administration of Antimicrobial Peptide NZ2114 Through the Microalgal Bait Tetraselmis subcordiformis (Wille) Butcher for Improving the Immunity and Gut Health in Turbot (Scophthalmus maximus L.) - Ting Yao; Fengjie Sun; Bingkui Zhu; Subing Han; Hao Zhang; Chunxiao Meng; Zhengquan Gao; Yulin Cui (Marine Biotechnology, 2024)

Population pharmacokinetics and pharmacodynamics of efmarodocokin alfa (IL-22Fc) - Yanke Yu; Michael E. Rothenberg; Han Ting Ding; Ari Brekkan; Gizette Sperinde; Brandon Harder; Rong Zhang; Ryan Owen; Nastya Kassir; Annemarie N. Lekkerkerker (Journal of Pharmacokinetics and Pharmacodynamics, 2024)

Terrestrial dissolved organic matter inputs accompanied by dissolved oxygen depletion and declining pH exacerbate CO2 emissions from a major Chinese reservoir - Ting Zhang; Lei Zhou; Yongqiang Zhou; Yunlin Zhang; Jinxin Guo; Yicai Han; Yayan Zhang; Liang Hu; Kyoung-Soon Jang; Robert G.M. Spencer; Justin D Brookes; Jan Dolfing; et al. (Water Research, 2024)

Microplastics affect mosquito from aquatic to terrestrial lifestyles and are transferred to mammals through mosquito bites - Jian-hang Li; Xiao-hui Liu; Guo-rui Liang; He-ting Gao; Si-han Guo; Xin-yu Zhou; Dan Xing; Teng Zhao; Chun-xiao Li (Science of The Total Environment, 2024)

Mixed plantations do not necessarily provide higher ecosystem multifunctionality than monoculture plantations - Xu Li; Yue Liu; Guopeng Wu; Zhiyang Lie; Han Sheng; Luis Carlos Ramos Aguila; Muhammmad Sadiq Khan; Xujun Liu; Shuyidan Zhou; Ting Wu; Wenfang Xu; Juxiu Liu (Science of The Total Environment, 2024)

Illustrating China's journey to balance, circular, and secure potassium cycles in the last three decades - Yan-Fei Liu; Peng Wang; Dan-Yi Feng; Xiaojie Liu; Zhongkui Han; Tao Dai; Shou-Ting Zhang; Wei-Qiang Chen (Resources, Conservation and Recycling, 2024)

Insight into the differential toxicity of PFOA and PFBA based on a 3D-cultured MDA-MB-231 cell model - Huan Wang; Hongchang Zhang; Shuangqing Hu; Ting Xu; Yiheng Yang; Miao Cao; Sheng Wei; Yiqun Song; Jing Han; Daqiang Yin (Journal of Hazardous Materials, 2024)

New modifications of PBAT by a small amount of oxalic acid: Fast crystallization and enhanced degradation in all natural environments - Qingyang Luan; Han Hu; Xingyu Ouyang; Xiaoyu Jiang; Chen Lin; Hanxu Zhu; Ting Shi; Yi-Lei Zhao; Jinggang Wang; Jin Zhu (Journal of Hazardous Materials, 2024)

Modulation of pea protein isolate nanoparticles by interaction with OSA-corn starch: Enhancing the stability of the constructed Pickering emulsions - Xin-Yue Liu; Ting-Shi He; Chen-Chen Wang; Bao-Cai Xu; Ran Feng; Bao Zhang; Han Tao (Food Chemistry, 2024)

Nitrite determination in food using electrochemical sensor based on self-assembled MWCNTs/AuNPs/poly-melamine nanocomposite - En Han; Lei Li; Ting Gao; Yingying Pan; Jianrong Cai (Food Chemistry, 2024)

Assessing cardiovascular toxicity in zebrafish embryos exposed to copper nanoparticles - Bu-Yuan Hsiao; Jiun-Lin Horng; Ching-Hua Yu; Wen-Ting Lin; Yu-Han Wang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Synergistic polyploidization and long‐distance dispersal enable the global diversification of yellowcress herbs - Ting‐Shen Han; Chih‐Chieh Yu; Quan‐Jing Zheng; Seisuke Kimura; Renske E. Onstein; Yao‐Wu Xing (Global Ecology and Biogeography, 2024)
Aim Long‐distance dispersal (LDD) plays an important role in shaping the distribution of global biodiversity. Polyploidy could favour invasion and thereby facilitate LDD. However, how and to what extent polyploidy interacts with LDD remain unclear. Here, we test the putative role of polyploidy in the global dispersal of a cosmopolitan genus Rorippa . Location Global. Time Period Late Miocene to present. Major Taxa Studied Rorippa Scop., Brassicaceae. Methods We traced the biogeographical and speciation history for 17 diploids and 41 polyploids of Rorippa using variation from plastid genomes and multiple nuclear loci. The ploidy role in dispersal rate difference was demonstrated using trait‐dependent biogeographical modelling. Results LDD shaped the amphitropical disjunction of Rorippa , during which polyploids showed higher dispersal rates than those of diploids, with 5.6× increase under the best‐fitted model. Five diploids and 21 polyploids were identified as products of transoceanic speciation events. Polyploidy‐involved LDD was more common in terms of polyploidization following LDD than those preceding LDD. Main Conclusions We demonstrate that polyploidy would be not only a driver but also a responder of LDD in Rorippa , highlighting a synergistic relationship between them. Our results provide a framework to uncover the biogeographical consequences of polyploidization and the joint roles of polyploidy and LDD in shaping the distribution of biodiversity.

Simultaneous biogas upgrading and medium-chain fatty acids production using a dual membrane biofilm reactor - Kai-Kai Wu; Lei Zhao; Zi-Han Wang; Zhong-Fang Sun; Jie-Ting Wu; Chuan Chen; De-Feng Xing; Shan-Shan Yang; Ai-Jie Wang; Yi-Feng Zhang; Nan-Qi Ren (Water Research, 2024)

Inhibitory mechanism of esculetin on tyrosinase and browning of fresh-cut apple: New perspectives - Lin-Jun Wang; Qiu-Han Bai; Qiu-Xia Pan; Yi-Feng Wu; Ting-Ting Shao; Yi-Wen Guo; Wen-Shuang Wei; Yi-Ting Wen; Wei-Ming Chai (Postharvest Biology and Technology, 2024)

Opportunities for converting waste plastics into petrochemicals: Process design, multi-objective optimization, and omnidirectional techno-economic-society-environment assessment - Xiaobo Chen; Jinqing Zhang; Zhibo Zhang; Zihao Zhang; Xin Zhou; Yaqi Zheng; Ting Wang; Guoliang Li; Ruzhen Ma; Qi Han; Hao Yan; Yibin Liu; et al. (Journal of Cleaner Production, 2024)

Integrated analysis of transcriptome and metabolome reveals the regulatory mechanism of largemouth bass (Micropterus salmoides) in response to Nocardia seriolae infection - Fen Dong; Yu-Long Sun; Yuan-Xin Qian; Qiang Chen; Jia-Le He; Ji-Teng Wang; Tao Han; Xiu-Mei Zhang; Yu-Ting Deng (Fish & Shellfish Immunology, 2024)

Visible-light-driven photo-Fenton oxidation enhanced by Fe/Bi-nanocrystal phase transformation as a universal way for various organic pollutants mineralization - Tulai Sun; Zi-Yan Jin; Bin Deng; Gan He; Qiong-Yu Wang; Mian Hu; Zhangliang Han; Zhaoke Zheng; Jun Zhao; Jimmy Yun; Jia Zhao; Yihan Zhu; et al. (Chemical Engineering Journal, 2024)

Sources and secondary transformation potentials of aromatic hydrocarbons observed in a medium-sized city in yangtze river delta region: Emphasis on intermediate-volatility naphthalene - Hua Fang; Wenjing Wang; Hongling Xu; Yuzhe Huang; Han Jiang; Ting Wu; Jun Li; Shuping Zha; Jianxi Zhang; Ruicheng Zhou; Xinming Wang (Atmospheric Environment, 2024)

Slow-release nitrogen fertilizer reduces input without yield loss in a rice-crayfish integrated system - Linjie Ma; Chengxin Zhang; Rong Xu; Ting Yang; Guangming Han; Leiming Wu; Shouhong Wang; Jiahong Zhang; Qin Yuan; Xiangming Kou (Nutrient Cycling in Agroecosystems, 2024)

Applicability of rock damage model based on power law distribution - Han Cao; Dongyun Zhu; Ting Bao; Pinghe Sun; Jingze Li; Habiyakare Erneste (Acta Geophysica, 2024)

Combined effects of crowding stress and low salinity on GH/IGF axis, antioxidant response, and HPI axis in largemouth bass (Micropterus salmoides) larvae - Jia-Lang Zheng; Hai-Ting Zhang; Lu Gao; Xiao Chen; Qing-Ling Zhu; Tao Han (Aquaculture, 2024)

LED light spectra differently affected growth, antioxidant capacity, stress response, GH/IGF and HPI axis in largemouth bass (Micropterus salmoides) larvae - Jia-Lang Zheng; Lu Gao; Hai-Ting Zhang; Xiao Chen; Qing-Ling Zhu; Tao Han (Aquaculture, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Phytochemistry and health functions of Zanthoxylum bungeanum Maxim and Zanthoxylum schinifolium Sieb. et Zucc as pharma-foods: A systematic review - Wenyi Liang; Heying Yang; Haoxuan Lei; Zhaobao Xiang; Yaqian Duan; Hailiang Xin; Ting Han; Juan Su (Trends in Food Science & Technology, 2024)

Polyester conversion by homogeneous catalysis for separating and recycling ammonia from biogas - Zhangliang Han; Yubo Yan; Xiaobing Pang; Aoran Zhang; Zhong-Ting Hu; Gutian Wenren; Senchen Lan; Dezhi Sun (Science of The Total Environment, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Constructing carbon-based materials loaded with MOFs to realize efficient anaerobic digestion of rural organic waste - Xiaomei Ye; Zhaoyan Jia; Yang Liu; Chengcheng Wang; Chunhui Cao; Yingpeng Zhang; Ting Han; Li Wang; Ting Guo; Yonglan Xi (Fuel, 2024)

Highly active Co1-N3-O1 single-atom catalyst for boosting catalytic synthesis of unsaturated benzylamines and arylamines - Song Han; Ming-Shuai Sun; Wen-Ting Chen; Yan Zhou; Duan-Jian Tao (Chemical Engineering Journal, 2024)

Highly efficient solar water evaporation by wood through one-step in-situ synthesis of carbon dots - Chunyu Ji; Ting Wang; Yifeng Wang; Han Yang (Chemical Engineering Journal, 2024)

Boosting promote C2 products formation in electrochemical CO2 reduction reaction via phosphorus-enhanced proton feeding - Shitao Han; Wei Xia; Shuaiqiang Jia; Jiapeng Jiao; Ting Yao; Xue Dong; Min Wang; Jianxin Zhai; Jiahao Yang; Yijun Xie; Xueqing Xing; Haihong Wu; et al. (Chemical Engineering Journal, 2024)

Obtainment and Inoculation of Acinetobacter pittii Strain JJ-2, and Combined Action with Plants for Formaldehyde and CO2 Removal: A Research Study - Jiaochan Zhong; Silan Chen; Shujie Lin; Yinjuan Jia; Han Li; Ting Zhan; Jian Li (Current Microbiology, 2024)

Development of a highly sensitive aptamer-based electrochemical sensor for detecting saxitoxin based on K3Fe(CN)6 regulated silver nanoparticles - Wei Zeng; Xuemei Tang; Ting Wu; Bingjun Han; Long Wu (Analytica Chimica Acta, 2024)

A multiobjective differential evolution algorithm with subpopulation region solution selection for global and local Pareto optimal sets - Ting Zhou; Xuming Han; Limin Wang; Wensheng Gan; Yali Chu; Minghan Gao (Swarm and Evolutionary Computation, 2023)

Exogenous hydrogen supply improves in-situ biogas upgrading of sewage sludge: Performance and mechanisms - Zhong-Fang Sun; Lei Zhao; Jie-Ting Wu; Zi-Han Wang; Kai-Kai Wu; Chuan Chen; De-Feng Xing; Dong-Mei Liu; Shan-Shan Yang; Ai-jie Wang; Nan-Qi Ren (Chemical Engineering Journal, 2023)

Correction to: selection of reference genes for RT-qPCR analysis in developing chicken embryonic ovary - Yi Wang; Yu-Qing Zhang; Zi-Wei Wu; Ting Fang; Fang Wang; Han Zhao; Zhi-Qiang Du; Cai-Xia Yang (Molecular Biology Reports, 2023)

Centralized health management based on hot spring resort improves physical examination indicators and sleep quality in people at high risk of chronic diseases: a randomized controlled trial - Yu Chen; Fan Luo; Lingli Han; Qizhong Qin; Qing Zeng; Xiangjun Zhou; Ying Huang; Qiuyidi Gao; Wen Wang; Qiuling Shi; Qirui Wang; Zhaoxia Yu; et al. (International Journal of Biometeorology, 2023)

Associations between paraben exposure, thyroid capacity, homeostasis and pituitary thyrotropic function in the general Taiwanese: Taiwan Environmental Survey for Toxicants (TEST) 2013 - Po-Chin Huang; Hsin-Chang Chen; Shih-Hao Leung; Yu-Jung Lin; Han-Bin Huang; Wan-Ting Chang; Hsin-I. Huang; Jung-Wei Chang (Environmental Science and Pollution Research, 2023)

Altered functional brain networks in coronary heart disease: independent component analysis and graph theoretical analysis - Simin Lin; Puyeh Wu; Shaoyin Duan; Qianni Du; Shujia Guo; Zhishang Chen; Naiming Wu; Xiaoyan Chen; Ting Xie; Yi Han; Hengyu Zhao (Brain Structure and Function, 2023)

Novel GdTaO4 phase for efficient photocatalytic degradation of organic dye under visible light irradiation: An X-ray spectroscopic investigation - Alageshwaramoorthy Krishnaprasanth; Pandian Mannu; Seetha Mahalingam; Dhanaprabhu Pattappan; Asokan Kandasami; Yi-Ting Lai; Yoshitake Masuda; Han-Wei Chang; Mei-Yu Chen; Ping-Hung Yeh; Chung-Li Dong (Chemosphere, 2023)

Molecular insights into complexation between protein and silica: Spectroscopic and simulation investigations - Ting Jiang; Xiao-Fan Hu; Yan-Fang Guan; Jie-Jie Chen; Han-Qing Yu (Water Research, 2023)

Extreme precipitation stable isotopic compositions reveal unexpected summer monsoon incursions in the Qilian Mountains - Liangju Zhao; Xiying Dong; Xiaohong Liu; Ninglian Wang; Christopher J. Eastoe; Na Wei; Cong Xie; Hang Liu; Chuntan Han; Ting Hua; Lixin Wang (Science of The Total Environment, 2023)

Connecting link between a sediment source and its deep-sea sink: Ilan Shelf offshore northeastern Taiwan - Ho-Han Hsu; Char-Shine Liu; John D. Milliman; Tzu-Ting Chen; Jih-Hsin Chang; J. Paul Liu; Chih-Chieh Su; Mei-Chi Fan (Marine and Petroleum Geology, 2023)

The new strategy of using humic acid loaded biochar to enhance the anaerobic digestion of cow manure for methane production - Yang Liu; Jing Du; Xiaomei Ye; Kequan Chen; Qingbo Xiao; Zhiyang Zhang; Chunhui Cao; Ting Han; Xiangping Kong; Yonglan Xi (Journal of Cleaner Production, 2023)

Synergistic effect between electric field and Ce-doped catalysts to promote hydrogen production from ammonia decomposition - Xiaochao Wang; Zijian Zhang; Guangzhao Zhou; Yiran Zhang; Xuteng Zhao; Dong Han; Ting Chen; Zhen Huang; He Lin (Fuel, 2023)

Carbon and nitrogen fractions are more important than bacterial composition for carbon and nitrogen mineralization considering parent material and fertilization - Shaoqi Xue; Shiqi Xu; Wei Kou; Jiale Han; Ting Fan; Xia Zhang; Xudong Wang (European Journal of Soil Biology, 2023)

Ultrafast and facile construction of programmable, multidimensional wrinkled-patterned polyacrylamide/sodium alginate hydrogels for human skin-like tactile perception - Jianhua Huang; Gong Chen; Tianhang Han; Chenxin Yi; Yujia Zhang; Lang Ding; Tianshu Sun; Ting Jin; Shuai Zhou (Carbohydrate Polymers, 2023)

Insufficient SIRT1 in macrophages promotes oxidative stress and inflammation during scarring - Ting He; Xiaozhi Bai; Yan Li; Dongliang Zhang; Zhigang Xu; Xuekang Yang; Dahai Hu; Juntao Han (Journal of Molecular Medicine, 2023)

Capturing Cu2+ and recycling spent Cu-adsorbents as catalyst for eliminating Rhodamine B: reactivity and mechanism - Caiyun Han; Jing Xie; Qin Shi; Liying Liang; Ting Yang; Sufang He (Environmental Science and Pollution Research, 2023)

A rapid segmentation method for weed based on CDM and ExG index - Xiaowu Han; Han Wang; Ting Yuan; Kunlin Zou; Qianfeng Liao; Kai Deng; Zhiqin Zhang; Chunlong Zhang; Wei Li (Crop Protection, 2023)

SIRT1 reduction contributes to doxorubicin–induced oxidative stress and meiotic failure in mouse oocytes - Jun Han; Shuo Wang; Huarong Wang; Tuo Zhang; Ye Yang; Ting Zhao; Ziqi Chen; Guoliang Xia; Chao Wang (Toxicology and Applied Pharmacology, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

MdGRF11-MdARF19-2 module acts as a positive regulator of drought resistance in apple rootstock - Lizhong Jiang; Jiahong Lv; Keting Li; Longmei Zhai; Yue Wu; Ting Wu; Xinzhong Zhang; Zhenhai Han; Yi Wang (Plant Science, 2023)

The immunomodulatory effects of DNA-conjugated collagen scaffolds on bone healing - Jing-han Song; Jun-ting Gu; Gao-peng Dang; Zhi-ting Li; Chen Lei; Ling Li; Zhao Mu; Franklin R. Tay; Kai Jiao; Li-na Niu (Chemical Engineering Journal, 2023)

Hybridize magnesium-iron layered double hydroxide with biopolymers to develop multiple pathways for phosphate sorption and release: A potential slow release phosphorus fertilizer - Wen-Hui Li; Liang-Ching Hsu; Yu-Min Tzou; Yi-Chun Chen; Heng Yi Teah; Yu-Yu Kung; Han-Yu Chen; Yu-Ting Liu (Chemical Engineering Journal, 2023)

Adjusting Zn2+ diffusion kinetics and storage capability of MnOOH nanofibers for high-performance cathode of aqueous zinc-ion batteries - Lijuan Chen; Yaoyong Dong; Mengwei Han; Ting Song; Xuejun Zheng; Wenyuan He; Bei Long; Xiongwei Wu; Yong Pei; Xianyou Wang (Chemical Engineering Journal, 2023)

Imbalance of multiple neurotransmitter pathways leading to depression-like behavior and cognitive dysfunction in the triple transgenic mouse model of Alzheimer disease - Meng Zhang; Li-yuan Liu; Yong Xu; Wen-zhi Wang; Nian-zhuang Qiu; Fang-fang Zhang; Feng Zhang; Xiao-dan Wang; Wei Chen; Xiao-yan Xu; Yong-feng Gao; Mei-hua Chen; et al. (Metabolic Brain Disease, 2023)

A multi-sensor-based distributed real-time measurement system for glacier deformation - Han-chuan Dong; Shuang Liu; Li-li Pang; Zhi-gang Tao; Li-de Fang; Zhong-hua Zhang; Xiao-ting Li (Journal of Mountain Science, 2023)

Associations between environmental heavy metals exposure and preserved ratio impaired spirometry in the U.S. adults - Chen Chen; Shunan Zhang; Ting Yang; Chen Wang; Guiling Han (Environmental Science and Pollution Research, 2023)
We examined 9556 individuals aged 18 to 79 years who had information on spirometry testing and heavy metals and used multivariable logistic or linear regression to evaluate associations between serum levels of cadmium, lead, and mercury and PRISm and lung function in U.S. adults, which were conducted first in all participants, and then separately in never/former smokers and current smokers. The overall prevalence of PRISm was 7.02%. High levels of serum cadmium were significantly associated with PRISm in all individuals, no matter in never/former smokers (quartile 4 vs 1, the OR = 2.517, 95% CI = 1.376–4.604, p -trend = 0.0077) and current smokers (quartile 4 vs 1, the OR = 2.201, 95% CI = 1.265–3.830, p -trend = 0.0020). Serum lead and mercury were not significantly correlated with PRISm, regardless of smoking status. Serum cadmium was strongly correlated with lower FEV 1 /FVC, regardless of smoking status. Besides, serum cadmium was also significantly related to lower FVC % predicted in never/former smokers and lower FEV 1 % predicted in current smokers. Serum lead was strongly correlated with lower FVC % predicted and FEV 1 /FVC in all individuals and never/former smokers. And serum mercury was significantly associated with decrements in FVC % predicted in all individuals and current smokers. These findings demonstrate that serum cadmium is associated with a higher risk of PRISm and lower lung function, with the most significant effect on FEV 1 /FVC in particular. Our results also indicate that exposure to lead and mercury negatively affects lung function in never/former smokers and current smokers, respectively.

Newcastle disease virus forms inclusion bodies with features of liquid-liquid phase separation - Chongyang Wang; Liuyuan Duan; Ting Wang; Wenbin Wang; Yu Han; Ruochen Hu; Qili Hou; Haijin Liu; Juan Wang; Xinglong Wang; Sa Xiao; Ruyi Dang; et al. (Veterinary Microbiology, 2023)

Genome-wide analysis of the MdZR gene family revealed MdZR2.2-induced salt and drought stress tolerance in apple rootstock - Keting Li; Longmei Zhai; Sitong Fu; Ting Wu; Xinzhong Zhang; Xuefeng Xu; Zhenhai Han; Yi Wang (Plant Science, 2023)

C21 steroids from the roots of Marsdenia tenacissima - Jin-Ling Liu; Hong-Tao Xu; Dan-Dan Mu; Xiao Han; Ting-Ting Du; Yong-li Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

Petrogenesis and tectonic implications of the early Paleozoic granites in the Lincang granitic batholith, southwestern China: Constraints from geochronology, geochemistry and Hf isotopes - Qian R. Xiao; Qiang Wang; Zhong Y. Liu; Fu H. Xiong; Lei Fan; Han Zhao; Ting T. Gong (Ore and Energy Resource Geology, 2023)

Responses of compositions, functions, and assembly processes of bacterial and microeukaryotic communities to long-range voyages in simulated ballast water - Xiaolan Lu; Baoyi Lv; Yangchun Han; Wen Tian; Ting Jiang; Guorong Zhu; Tingxuan An (Marine Environmental Research, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Prenatal exposure to PM2.5 and its constituents with children's BMI Z-score in the first three years: A birth cohort study - Shuang Zhou; Tiantian Li; Na Han; Kai Zhang; Yi Zhang; Qin Li; Yuelong Ji; Jue Liu; Hui Wang; Jianlin Hu; Ting Liu; Hein Raat; et al. (Environmental Research, 2023)

Structural analysis of shield machine cutting monopile using p-y curve based finite element method - Ting Li; Bo Liu; Yanhui Han; Chunqing Fu; Yanding Sun (Computers and Geotechnics, 2023)

Novel smart coaxial electrospinning textiles for efficient thermal interface management and electromagnetic compatibility in electronics - Shaokun Song; Hong Ai; Linda Lv; Yi Guo; Ting Han; Lijie Dong (Chemical Engineering Journal, 2023)

Mechanisms of Epichloë bromicola to Promote Plant Growth and Its Potential Application for Coix lacryma-jobi L. Cultivation - Xing-Guang Xie; Wei-Lan Lu; Kun-Miao Feng; Cheng-Jian Zheng; Yang Yang; Min Jia; Yi-Sang Wu; Yan-Zhang Shi; Ting Han; Lu-Ping Qin (Current Microbiology, 2023)

Knockdown of klotho Leads to Cell Movement Impairment during Zebrafish Gastrulation - Heng-Chih Pan; Kang-Chieh Lo; Yun-Hsin Wang; Han-Ting Huang; Shu-Chun Cheng; Chiao-Yin Sun; Yau-Hung Chen (Fishes, 2023)
(1) Background: Klotho is a multifunctional protein, but its biophysiological roles during fish early development are unclear. (2) Methods: We carried out anti-sense Klotho morpholino injection and whole-mount in situ hybridization experiments in this study. (3) Results: Our results showed that in the Klotho MO1-injected group, embryos displayed longitudinal shapes and swelling yolks compared to those of the un-injected groups. Their length/width ratio by 9 hpf for the uninfected group is 1 ± 0.1; but for 0.1 mM-, 0.2 mM-, and 0.5 mM-MO-injected are 1.1 ± 0.1, 1.2 ± 0.1, and 1.3 ± 0.1, respectively, suggesting that the klotho knockdown-induced length/width ratio changes are in a dose-dependent manner. Whole-mount in situ hybridization showed that several cell migration-related gene expressions, including goosecoid, floating head, bone morphogenetic protein 4, and even-skipped-liked 1 were affected in the Klotho MO-injected embryos. (4) Conclusions: We suggest that knockdown of klotho leads to cell movement impairment during zebrafish gastrulation.

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

Development of a novel ultrasound- and biocrosslinking-enhanced immobilization strategy with application to food enzymes - Juan Han; Ting Zhang; Zhuoyue Zhou; Houjin Zhang (Food Chemistry, 2023)

Contribution of different class 2 integron elements to fitness costs in multi-drug resistant Escherichia coli and evaluation of their adaptability in “farm-to-table” environments - Han Jiang; Xue Jiao; Ting Yu; Wen Wang; Hui Cheng; Guangrong Huang; Jiehong Fang (Food Microbiology, 2023)

Anomaly diagnosis of stay cables based on vehicle-induced cable force sums - De-Long Li; Dong-Hui Yang; Ting-Hua Yi; Song-Han Zhang; Wen-Jie Li; Chong Li (Engineering Structures, 2023)

Performance of heavy metal-immobilizing bacteria combined with biochar on remediation of cadmium and lead co-contaminated soil - Ting Wei; Han Gao; Fengqiu An; Xiulian Ma; Li Hua; Junkang Guo (Environmental Geochemistry and Health, 2023)

Risk analysis of people evacuation and its path optimization during tunnel fires using virtual reality experiments - Xiaochun Zhang; Linjie Chen; Junhao Jiang; Yixin Ji; Shuyang Han; Ting Zhu; Wenbin Xu; Fei Tang (Tunnelling and Underground Space Technology, 2023)

Nitric oxide induces defense responses in apple fruit against black spot disease caused by Alternaria alternata - Jie Han; Yingying Fan; Shicui Li; Binxin Jia; Jin Yang; Aibin Shen; Ting Dai; Jing An; Fengjuan Liu; Cheng Wang (South African Journal of Botany, 2023)

Ergostane-type sterols and sesquiterpenes with anti-neuroinflammatory activity from a Nigrograna species associated with Clematis shensiensis - Liang-Liang Zhai; Ting-Ting Jiang; Rong Zhang; Jian-Nan Li; Yi-Jie Zhai; Qiang Zhang; Ding Li; Wen-Bo Han (Phytochemistry, 2023)

A sustainable layered nanofiber/sheet aerogels enabling repeated life cycles for effective oil/water separation - Ting Dong; Huabiao Ye; Wenhui Wang; Yuanming Zhang; Guangting Han; Fudi Peng; Ching-Wen Lou; Shan Chi; Yanming Liu; Cui Liu; Jia-Horng Lin (Journal of Hazardous Materials, 2023)

The bound polyphenols of foxtail millet (Setaria italica) inner shell inhibit breast cancer by promoting lipid accumulation-induced autophagic death - Li-chao Zhang; Ya-ning Liu; Xiao-qin La; Shuai-tao Li; Li-na Wen; Ting Liu; Han-qing Li; Ai-ping Li; Haitao Wu; Chang-xin Wu; Zhuo-yu Li (Food and Chemical Toxicology, 2023)

Tumor microenvironment as a bioreactor for Au&Fe3O4-DNA complex synthesis and targeted cancer therapy - Yi Han Wang; Ke Huang; Zhao Jian Qin; Hong Jie Xiong; Teng Fei Liu; Ting Ya Wang; Xiang Dong Lai; Xiao Hui Liu; Hui Jiang; Xue Mei Wang (Chemical Engineering Journal, 2023)

Correction: Regulation of PPARγ/CPT-1 expression ameliorates cochlear hair cell injury by regulating cellular lipid metabolism and oxidative stress - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Ting Zhang; Baiya Li; Xiaoyan Ma; Qun Wu; Xudong Ma (Molecular Genetics and Genomics, 2023)

The catalytic oxidation process of atrazine by ozone microbubbles: Bubble formation, ozone mass transfer and hydroxyl radical generation - Ting Liu; Bin Zhang; Wenqian Li; Boda Li; Ziwen Han; Yanjie Zhang; An Ding; Shutao Wang; Jun Ma; Xu He (Chemosphere, 2023)

Regulation of Hippo/YAP signaling pathway ameliorates cochlear hair cell injury by regulating ferroptosis - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Xiaoyan Ma; Ting Zhang; Baiya Li; Xudong Ma (Tissue and Cell, 2023)

Effects of nano metal oxide particles on denitrifying phosphorus removal system: Potential stress mechanism and recovery strategy - Yang Sun; Ting Han; Wenxin Lu; Yingqi Wang; Deyi Jiang; Haq Nawaz Abbasi; Zechong Guo; Shuai Zhang; Bing Li; Xingang Wang; Hongliang Dai (Science of The Total Environment, 2023)

Recent development of sustainable self-healable electronic skin applications, a review with insight - Jean-Sébastien Benas; Fang-Cheng Liang; Manikandan Venkatesan; Zhen-Li Yan; Wei-Cheng Chen; Su-Ting Han; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Hydrothermal characteristics of the Mienhua submarine volcano in the southernmost Okinawa trough - Tzu-Ting Chen; Ho-Han Hsu; Chih-Chieh Su; Char-Shine Liu; Yunshuen Wang; Song-Chuen Chen; Emmy T. Y. Chang; Feng-Hsin Hsu; Liang-Fu Lin; Jih-Hsin Chang; Jyun-Nai Wu; Ta-Wei Hsu; et al. (Marine Geophysical Research, 2023)

GSH-Dependent PTMs of Proteins Differ Significantly Between Ontogenetic Phases of Apple Trees - Jing Yang; Qingbo Zheng; Yi Wang; Ting Wu; Wei Li; Changpeng Qiu; Xuefeng Xu; Xi Zhang; Zhenhai Han; Xinzhong Zhang (Journal of Plant Growth Regulation, 2023)

Endophytic fungus Trichoderma atroviride D16 increases tanshinone accumulation in Salvia miltiorrhiza plantlets by enhancing abscisic acid and salicylic acid signaling - Xing-Guang Xie; Ke-Xin Sheng; Wei-Lan Lu; Hao-Ran Wang; Khalid Rahman; Kun-Miao Feng; Ting Han (Symbiosis, 2023)

Ex vitro rooting of minicutting of Carica papaya L. single shoot from tissue culture - Yu-Ting Chen; Tun-Han Yang; Tsong-Ann Yu (In Vitro Cellular & Developmental Biology - Plant, 2023)

Target-independent hybridization chain reaction-fluorescence resonance energy transfer for sensitive assay of ctDNA based on Cas12a - Xuelan Wu; Ting Ju; Zeyang Li; Jingwen Li; Xingwei Zhai; Kun Han (Analytica Chimica Acta, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

A two-stage distributionally robust optimization model for geothermal-hydrogen integrated energy system operation considering multiple uncertainties - Ting Wang; Huiyu Han; Yuwei Wang (Environment, Development and Sustainability, 2023)

Review: Role and regulatory mechanism of inhibin in animal reproductive system - Yuqing Han; Ting Jiang; Jun'an Shi; Anfang Liu; Lingbin Liu (Theriogenology, 2023)

An Anterior Cingulate Cortex-to-Midbrain Projection Controls Chronic Itch in Mice - Ting-Ting Zhang; Su-Shan Guo; Hui-Ying Wang; Qi Jing; Xin Yi; Zi-Han Hu; Xin-Ren Yu; Tian-Le Xu; Ming-Gang Liu; Xuan Zhao (Neuroscience Bulletin, 2023)
Itch is an unpleasant sensation that provokes the desire to scratch. While acute itch serves as a protective system to warn the body of external irritating agents, chronic itch is a debilitating but poorly-treated clinical disease leading to repetitive scratching and skin lesions. However, the neural mechanisms underlying the pathophysiology of chronic itch remain mysterious. Here, we identified a cell type-dependent role of the anterior cingulate cortex (ACC) in controlling chronic itch-related excessive scratching behaviors in mice. Moreover, we delineated a neural circuit originating from excitatory neurons of the ACC to the ventral tegmental area (VTA) that was critically involved in chronic itch. Furthermore, we demonstrate that the ACC→VTA circuit also selectively modulated histaminergic acute itch. Finally, the ACC neurons were shown to predominantly innervate the non-dopaminergic neurons of the VTA. Taken together, our findings uncover a cortex–midbrain circuit for chronic itch-evoked scratching behaviors and shed novel insights on therapeutic intervention.

Analysis of temporal and spatial variation characteristics of midlatitude summer nighttime anomaly in low and middle solar activity period - Jiandi Feng; Kaixin Wang; Wang Li; Baomin Han; Zhenzhen Zhao; Ting Zhang; Di Meng (Advances in Space Research, 2023)

In utero exposure to perfluoroalkyl substances and early childhood BMI trajectories: A mediation analysis with neonatal metabolic profiles - Xiaojing Zeng; Ting Chen; Yidan Cui; Jian Zhao; Qian Chen; Zhangsheng Yu; Yongjun Zhang; Lianshu Han; Yan Chen; Jun Zhang (Science of The Total Environment, 2023)

Structural variation (SV)-based pan-genome and GWAS reveal the impacts of SVs on the speciation and diversification of allotetraploid cottons - Shangkun Jin; Zegang Han; Yan Hu; Zhanfeng Si; Fan Dai; Lu He; Yu Cheng; Yiqian Li; Ting Zhao; Lei Fang; Tianzhen Zhang (Molecular Plant, 2023)

Complete genome sequence of one novel marine Pseudomonas sp. BSw22131 growing with dimethylsulfoniopropionate (DMSP) as the sole carbon source - Ting Hu; Yin-Xin Zeng; Yi-He Zhang; Yu Du; Wei Han; Hui-Rong Li; Wei Luo (Marine Genomics, 2023)

Effect of ferulic acid covalent conjugation on the functional properties and antigenicity of β-lactoglobulin - Yu-Ting Xue; Ya-Ning Han; Yan Wang; Ying-Hua Zhang; Yu-Qi Yin; Bo-Hao Liu; Han-Lin Zhang; Xin-Huai Zhao (Food Chemistry, 2023)

Matthew effect photoimmunotheranostics enabled by proton-driven nanoconverter - Jingjing Wang; Wei Zhang; Dachong Gu; Chunmei Chen; Wei Tang; Yi Ouyang; Xiaohong Liu; Shi-Yu Lu; Wei Zhang; Xingcai Zhang; Yulong Han; Jie Hu; et al. (Chemical Engineering Journal, 2023)

High-titer production of myo-inositol by a co-immobilized four-enzyme cocktail in biomimetic mineralized microcapsules - Pingping Han; Chun You; Yunjie Li; Ting Shi; Hong Wu; Yi-Heng P. Job Zhang (Chemical Engineering Journal, 2023)

Silica-nickel catalyst interfaces promote highly efficient CO2 electroreduction to CO with a wide potential range - Yijun Xie; Wei Xia; Shuaiqiang Jia; Shitao Han; Ting Yao; Minghui Fang; Dawei Zhou; Xueqing Xing; Haihong Wu; Mingyuan He; Buxing Han (Chemical Engineering Journal, 2023)

Profiles and key drivers of bacteria/phage co-mediated antibiotic resistance genes during swine manure composting amended with humic acid - Meiling Shi; Zixuan Zhao; Xiaojuan Wang; Huakang Li; Jie Gu; Zilin Song; Ting Hu; Yifan Sun; Han Wang (Bioresource Technology, 2023)

Multi-species weed density assessment based on semantic segmentation neural network - Kunlin Zou; Han Wang; Ting Yuan; Chunlong Zhang (Precision Agriculture, 2023)

Selection of reference genes for RT-qPCR analysis in developing chicken embryonic ovary - Yi Wang; Yu-Qing Zhang; Zi-Wei Wu; Ting Fang; Fang Wang; Han Zhao; Zhi-Qiang Du; Cai-Xia Yang (Molecular Biology Reports, 2023)

Energy metabolism response induced by microplastic for marine dinoflagellate Karenia mikimotoi - Ting Zhao; Liju Tan; Xiaotian Han; Xiaofeng Ma; Kun Lin; Jiangtao Wang (Science of The Total Environment, 2023)

Rapid saline-alkali sensitivity testing using hydrogel/gold nanoparticles-modified screen-printed electrodes - Ting Zhang; Juan Han; Houjin Zhang (Science of The Total Environment, 2023)

Genome-wide identification of WOX family members in nine Rosaceae species and a functional analysis of MdWOX13-1 in drought resistance - Jiahong Lv; Yi Feng; Lizhong Jiang; Guibin Zhang; Ting Wu; Xinzhong Zhang; Xuefeng Xu; Yi Wang; Zhenhai Han (Plant Science, 2023)

Facile synthesis of novel helical imprinted fibers based on zucchini-derived microcoils for efficient recognition of target protein in biological sample - Xinya Xu; Yundong Xie; Pengqi Guo; Yongheng Shi; Meng Sun; Jing Zhou; Chuan Wang; Chaojun Han; Jiping Liu; Ting Li (Food Chemistry, 2023)

Carnosic acid attenuated cytochrome c release through the mitochondrial structural protein Mic60 by PINK1 in SH-SY5Y cells - Chia-Yuan Lin; Yi-Chen Huang; Chi-Rei Wu; Han-Ting Wu; Ru-Huei Fu; Chia-Wen Tsai (Food and Chemical Toxicology, 2023)

Assessing the impact of rockfall on a bridge by using hybrid DEM/FEM analysis: A case study in Central Taiwan - Terry Y.P. Yuen; Meng-Chia Weng; Yu-Yao Fu; Guan-Ting Lu; Wen-Jie Shiu; Cheng-An Lu; Chun-Yuan Liu; Chia-Chi Chiu; Tzu-Han Wen (Engineering Geology, 2023)

Excavation Stress Path Induced Fracturing Mechanism of Hard Rock in Deep Tunnel - Liangjie Gu; Xia-Ting Feng; Rui Kong; Chengxiang Yang; Qiang Han; Yuelin Xia (Rock Mechanics and Rock Engineering, 2023)

Regulation of PPARγ/CPT-1 expression ameliorates cochlear hair cell injury by regulating cellular lipid metabolism and oxidative stress - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Ting Zhang; Baiya Li; Xiaoyan Ma; Qun Wu; Xudong Ma (Molecular Genetics and Genomics, 2023)

Correlates of Rhizosphere Soil Properties, Fungal Community Composition, and Active Secondary Metabolites in Cornus officinalis in Different Regions of China - Haoqiang Sun; Binkai Han; Xiaolin Yang; Changfen He; Ke Zhao; Ting Wang; Shujing An; Xiaochang Xue; Jiefang Kang (Journal of Soil Science and Plant Nutrition, 2023)

Effects of H2O2 acclimation on the growth, polysaccharide production and tolerance performance of Nostoc flagelliforme - Shu-ting Liu; Shuai Wang; Na Han; Meng-yuan Li; Jian Li; Yan-ru Li; Shi-ru Jia; Pei-pei Han (Algal Research, 2023)

Analysis of ionospheric TEC response to solar and geomagnetic activities at different solar activity stages - Jiandi Feng; Yibin Zhang; Wang Li; Baomin Han; Zhenzhen Zhao; Ting Zhang; Ruijing Huang (Advances in Space Research, 2023)

Bacterial resistance to antibacterial agents: Mechanisms, control strategies, and implications for global health - Ting Li; Zhenlong Wang; Jianhua Guo; Cesar de la Fuente-Nunez; Jinquan Wang; Bing Han; Hui Tao; Jie Liu; Xiumin Wang (Science of The Total Environment, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Calcium isotope systematics of altered oceanic crust at IODP site 1256: Insights into the hydrothermal alteration - Ling-Zhi Hu; Jin-Ting Kang; Yu-Han Qi; Yong-Jun Gao; Xiao-Yun Nan; Jian Huang; Fang Huang (Lithos, 2023)

Photothermal and Concus Finn capillary assisted superhydrophobic fibrous network enabling instant viscous oil transport for crude oil cleanup - Ting Dong; Yanhui Liu; Na Tian; Yuanming Zhang; Guangting Han; Fudi Peng; Ching-Wen Lou; Shan Chi; Yanming Liu; Cui Liu; Jia-Horng Lin (Journal of Hazardous Materials, 2023)

Hydrometallurgy recovery of copper, aluminum and silver from spent solar panels - Qi Han; Yidi Gao; Ting Su; Jiabao Qin; Chi Wang; Zhan Qu; Xianze Wang (Journal of Environmental Chemical Engineering, 2023)

Nonlinear rheological behavior and quantitative proteomic analysis of pea protein isolates at the air-water interface - Qian Shen; Yilun Luo; Wei Zheng; Ting Xiong; Fei Han; Jingnan Zuo; Jun Dai; Bin Li; Yijie Chen (Food Hydrocolloids, 2023)

New insight into soluble extracellular metabolites during sludge bulking process based on excitation-emission matrix spectroscopy and ultrahigh-performance liquid chromatography-mass spectrometry - Zong Li; Shujuan Cun; Ganghua Han; Xiaoxiao Guo; Bingxin Liu; Ting Huang; Deyin Hou; Ruyin Liu; Xinchun Liu (Environmental Research, 2023)

The prevalence of potential pathogens in ballast water and sediments of oceangoing vessels and implications for management - Baoyi Lv; Guorong Zhu; Wen Tian; Chong Guo; Xiaolan Lu; Yangchun Han; Tingxuan An; Yuxue Cui; Ting Jiang (Environmental Research, 2023)

Corrigendum to “Combined dynamic structure-pile-soil interaction analysis considering inertial and kinematic effects” [Comput. Geotech. 125 (2020) 103671] - Jiunn-Shyang Chiou; Wen-Yi Hung; Yi-Ting Lee; Zong-Han Young (Computers and Geotechnics, 2023)

Regulating desolvation and homogenized ion flux towards highly reversible dendrite-free zinc anode - Xin Qi; Fuli Xie; Yu-Ting Xu; Hai Xu; Cheng-Lin Sun; Sheng-Han Wang; Jian-Yong Hu; Xiao-Feng Wang (Chemical Engineering Journal, 2023)

Nuclear-localized CTEN is a novel transcriptional regulator and promotes cancer cell migration through its downstream target CDC27 - Yi-Xuan Wang; Chun-Yang Huang; Hsiao-Ju Chiu; Po-Han Huang; Hung-Ting Chien; Si-Han Jwo; Yi-Chun Liao (Journal of Physiology and Biochemistry, 2023)

Construction, Characterization, and Application of an Ammonium Transporter (AmtB) Deletion Mutant of the Nitrogen-Fixing Bacterium Kosakonia radicincitans GXGL-4A in Cucumis sativus L. Seedlings - Yu-Qing Bao; Meng-Ting Zhang; Bao-Yun Feng; Wulale Jieensi; Yu Xu; Lu-Rong Xu; Ying-Ying Han; Yun-Peng Chen (Current Microbiology, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

β-catenin facilitates fowl adenovirus serotype 4 replication through enhancing virus-induced autophagy - Ting Wang; Chongyang Wang; Jinjie Han; Xiaolan Hou; Ruochen Hu; Wenchi Chang; Lizhen Wang; Xuefeng Qi; Jingyu Wang (Veterinary Microbiology, 2023)

Seasonal variation and ecological risk assessment of Pharmaceuticals and Personal Care Products (PPCPs) in a typical semi-enclosed bay — The Bohai Bay in northern China - Kun Lin; Rui Wang; Tongzhu Han; Liju Tan; Xue Yang; Mengmeng Wan; Yanshan Chen; Ting Zhao; Shan Jiang; Jiangtao Wang (Science of The Total Environment, 2023)

The growth-regulating factor PdbGRF1 positively regulates the salt stress response in Populus davidiana × P. bolleana - Zhong-Yuan Liu; Ya-Ting Han; Chun-Yao Wang; Xiao-Jin Lei; Yuan-Yuan Wang; Wen-Fang Dong; Qing-Jun Xie; Yu-Jie Fu; Cai-Qiu Gao (Plant Science, 2023)

Observer-based dynamic optimal recoil controller design for deepwater drilling riser systems - Wei Zhang; Bao-Lin Zhang; Qing-Long Han; Yue-Ting Sun; Yan Ji; Dawei Zhang; Xian-Ming Zhang (Ocean Engineering, 2023)

Higher blood selenium level is associated with lower risk of hyperhomocysteinemia in the elderly - Ting Wang; Liqin Su; Xi Chen; Sisi Wang; Xu Han; Yibin Cheng; Shaobin Lin; Liang Ding; Jingyi Liu; Chen Chen; Frederick W. Unverzagt; Ann M. Hake; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Cross-biome soil viruses as an important reservoir of virulence genes - Li Bi; Li-Li Han; Shuai Du; Dan-Ting Yu; Ji-Zheng He; Li-Mei Zhang; Hang-Wei Hu (Journal of Hazardous Materials, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

A novel slag composite for the adsorption of heavy metals: Preparation, characterization and mechanisms - Mengyu Ma; Ting Wang; Xuan Ke; Yanchang Liu; Yunjie Song; Xiaojie Shang; Jia Li; Qingwen Han (Environmental Research, 2023)

An improved model assessing variation characteristics of pore structure of sandy soil thawing from extremely low temperature using NMR technique - Bo Liu; Yanqing He; Yanhui Han; Ting Li; Dongyang Li; Rong Gao (Cold Regions Science and Technology, 2023)

Osteomodulin protects dental pulp stem cells from cisplatin-induced apoptosis in vitro - Ting Dong; Wen-zhen Lin; Xiao-han Zhu; Ke-yong Yuan; Li-li Hou; Zheng-wei Huang (Stem Cell Reviews and Reports, 2023)

The Nucleus Accumbens CRH–CRHR1 System Mediates Early-Life Stress-Induced Sleep Disturbance and Dendritic Atrophy in the Adult Mouse - Ting Wang; Yu-Nu Ma; Chen-Chen Zhang; Xiao Liu; Ya-Xin Sun; Hong-Li Wang; Han Wang; Yu-Heng Zhong; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2023)

Humulus lupulus L. extract and its active constituent xanthohumol attenuate oxidative stress and nerve injury induced by iron overload via activating AKT/GSK3β and Nrf2/NQO1 pathways - Sun Xiao-Lei; Xia Tian-Shuang; Jiang Yi-Ping; Wang Na-Ni; Xu Ling-Chuan; Han Ting; Xin Hai-Liang (Journal of Natural Medicines, 2023)

A new global TEC empirical model based on fusing multi-source data - Jiandi Feng; Ting Zhang; Wang Li; Zhenzhen Zhao; Baomin Han; Kaixin Wang (GPS Solutions, 2023)

A single QTL harboring multiple genetic variations leads to complicated phenotypic segregation in apple flesh firmness and crispness - Xianglong Yang; Bei Wu; Jing Liu; Zhongyan Zhang; Xuan Wang; Haie Zhang; Xuejun Ren; Xi Zhang; Yi Wang; Ting Wu; Xuefeng Xu; Zhenhai Han; et al. (Plant Cell Reports, 2022)

Photoacclimation caused by high frequency flashing light assists Chlorella sp. M-12 wastewater treatment and biomass accumulation in dark color biogas slurry - Chaorui Chen; Fan Tao; Ting Han; Fengzheng Gao; Taili Dong; Weizhong Jiang; Haifeng Lu; Yuanhui Zhang; Baoming Li (Journal of Applied Phycology, 2022)

Information standardization for typical toxic and harmful algae in China’s coastal waters—a case study of Karenia mikimotoi - Ting Zhao; Huidi Cao; Yanfen Jia; Xiaotian Han; Tian Yan; Rencheng Yu (Journal of Oceanology and Limnology, 2022)

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

Importance of surface charge of soot nanoparticles in determining inhalation toxicity in mice - Ta-Chih Hsiao; Chia-Li Han; Tzu-Ting Yang; Yueh-Lun Lee; Yu-Fang Shen; Yu-Teng Jheng; Chii-Hong Lee; Jer-Hwa Chang; Kian Fan Chung; Han-Pin Kuo; Hsiao-Chi Chuang (Environmental Science and Pollution Research, 2022)

The spatial distribution and characterization of phosphorus and nitrogen in a water-carrying lake: a case study of Lake Jiaogang, China - Tianlun Han; Kang Zhou; Jiuling Li; Ting Chen; Xueting Xu; Shuai Zhang; Jianying Chao; Ming Kong (Environmental Science and Pollution Research, 2022)

Degradation mechanism of BPA under VUV irradiation: efficiency contribution and DFT calculations - Ting-Ting Cao; Han Cui; Dan-Dan Zhou; Xin Ren; Chong-Wei Cui (Environmental Science and Pollution Research, 2022)

Stress Distribution of Four-Unit Implant-Supported Fixed Partial Prosthesis with Different Numbers and Positions of Fixtures in Maxilla Anterior Region-3D FEA - Kai-Chun Cheng; Pao-Hsin Liu; Han-Sheng Chen; Ting-Hsun Lan (Journal of Medical and Biological Engineering, 2022)

Construction of double tube granular sludge microbial fuel cell and its characteristics and mechanism of azo dye degradation - Xiaorui Li; Hongliang Dai; Ting Han; Zechong Guo; Hui Li; Xingang Wang; Haq Nawaz Abbasi (Environmental Science and Pollution Research, 2022)

Effect of Different Absorption Enhancers on the Nasal Absorption of Nalmefene Hydrochloride - Ting Zhang; Meng Li; Xiaolu Han; Guangjun Nie; Aiping Zheng (AAPS PharmSciTech, 2022)

Potential integration of wastewater treatment and natural pigment production by Phaeodactylum tricornutum: microalgal growth, nutrient removal, and fucoxanthin accumulation - Jinshun Jiang; Jianke Huang; Han Zhang; Zhen Zhang; Yi Du; Zheng Cheng; Bo Feng; Ting Yao; Aihua Zhang; Zhe Zhao (Journal of Applied Phycology, 2022)

Desmopressin therapy in children and adults: pharmacological considerations and clinical implications - Xinyi Chin; Shao Wei Teo; Soo Ting Lim; Yong Hong Ng; How Chuan Han; Fabian Yap (European Journal of Clinical Pharmacology, 2022)

Multivariate morphological brain signatures enable individualized prediction of dispositional need for closure - Xinling Chen; Zhenhua Xu; Ting Li; Li Wang; Peiyi Li; Han Xu; Chunliang Feng; Chao Liu (Brain Imaging and Behavior, 2022)

One new piperazinedione isolated from a mangrove-derived fungus Aspergillus niger JX-5 - Meng Bai; Yue Wang; Ting Liu; Yu-Xing Lian; Qi-Qi Bai; Xiao-Ping Song; Chang-Ri Han; Cai-Juan Zheng; Guang-Ying Chen (Natural Product Research, 2022)

Genome-based reclassification of the genus Meiothermus along with the proposal of a new genus Allomeiothermus gen. nov - Jian-Yu Jiao; Zheng-Han Lian; Ze-Tao Liu; Lan Liu; Meng-Meng Li; Ai-Ping Lv; Wen-Dong Xian; Ting Zhou; Zhitang Lyu; Nimaichand Salam; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Hypothermal Effects on Energy Supply for Ionocytes in Gills of Freshwater- and Seawater-Acclimated Milkfish, Chanos chanos - Chia-Hao Chang; Chia-Jui Liu; Wei-Jie Lu; Li-Yang Wu; Kuang-Jie Lai; Yu-Ting Lin; Tsung-Han Lee (Frontiers in Marine Science, 2022)
The milkfish, Chanos chanos , is an important aquaculture species that can be cultured in freshwater (FW) and seawater (SW) ponds because of its high euryhalinity. In winter, cold snap leading to high mortality of this tropical species is a critical issue for the aquaculture industry in Taiwan. Under hypothermal stress, however, changes in energy supply for osmoregulation of this euryhaline species is intriguing. In this study, we used an antibody against glycogen phosphorylase (GP) to identify glycogen-rich (GR) cells distributed adjacent to the mitochondria-rich (MR) ionocytes in milkfish gills. Glucose transporter 1 (GLUT1), which plays a major role in energy supply, was also identified and localized in GR cells. Moreover, the expression of indicators of aerobic metabolism and energy production, citrate synthase (CS) and cytochrome c oxidase (COX), were analyzed in gills of FW- and SW-acclimated milkfish to reveal different strategies of energy utilization under hypothermal stress. When exposed to a low-temperature environment, SW individuals used branchial glycogen and lactate to match the energy demands of aerobic metabolism in ionocytes, and elevated aerobic capacity to support and maintain normal functions in gills. However, branchial glycogen mainly localized in the GR cells of FW milkfish was not utilized under hypothermal stress. Meanwhile, a similar level of branchial COX activity and COXIV protein abundance at low temperatures between FW and SW milkfish indicated similar energy requirements in gills. This suggested that another source, but not branchial glycogen, maintained the energy demand in FW milkfish. The present study illustrated differential energy supply strategies in gills between SW- and FW-acclimated milkfish for osmoregulation under low temperatures.

Rapid and sensitive detection of Karenia mikimotoi by loop-mediated isothermal amplification combined with a lateral flow dipstick - Xiaotian Han; Ting Zhao; Tian Yan; Rencheng Yu (Environmental Science and Pollution Research, 2022)

The significance of riparian communities in the energy flow of subtropical stream ecosystems - Yi-Chang Liao; An-Cheng Lin; Han-Ni Tsai; Yu-Ting Yen; Chyng-Shyan Tzeng; Man-Miao Yang; Hsing-Juh Lin (Aquatic Sciences, 2022)

Unexpected role of electron‐transfer hub in direct degradation of pollutants by exoelectrogenic bacteria - Ting‐Ting Zhu; Zhou‐Hua Cheng; Sheng‐Song Yu; Wen‐Wei Li; Dong‐Feng Liu; Han‐Qing Yu (Environmental Microbiology, 2022)
Summary Exoelectrogenic bacteria (EEB) are capable of anaerobic respiration with diverse extracellular electron acceptors including insoluble minerals, electrodes and flavins, but the detailed electron transfer pathways and reaction mechanisms remain elusive. Here, we discover that CymA, which is usually considered to solely serve as an inner‐membrane electron transfer hub in Shewanella oneidensis MR‐1 (a model EEB), might also function as a reductase for direct reducing diverse nitroaromatic compounds (e.g. 2,4‐dichloronitrobenzene) and azo dyes. Such a process can be accelerated by dosing anthraquinone‐2,6‐disulfonate. The CymA‐based reduction pathways in S . oneidensis MR‐1 for different contaminants could be functionally reconstructed and strengthened in Escherichia coli . The direct reduction of lowly polar contaminants by quinol oxidases like CymA homologues might be universal in diverse microbes. This work offers new insights into the pollutant reduction mechanisms of EEB and unveils a new function of CymA to act as a terminal reductase.

Baicalin attenuates amyloid β oligomers induced memory deficits and mitochondria fragmentation through regulation of PDE-PKA-Drp1 signalling - Hai-Yang Yu; Ye Zhu; Xin-Li Zhang; Lei Wang; Yan-Meng Zhou; Fang-Fang Zhang; Han-Ting Zhang; Xiao-Min Zhao (Psychopharmacology, 2022)

Subacute cadmium exposure modulates Th1 polarization to trigger ER stress-induced porcine hepatocyte apoptosis via regulation of miR-369-TNFα axis - Dongxu Han; Nuan Song; Wei Wang; Ting Chen; Zhiying Miao (Environmental Science and Pollution Research, 2022)

Experimental Study of the Mechanical Characteristics of Jinping Marble Under Multi-stage True Triaxial Compression Testing - Gang Wang; Xia-Ting Feng; Chengxiang Yang; Qiang Han; Rui Kong (Rock Mechanics and Rock Engineering, 2022)

Extracellular matrix stiffness controls VEGF165 secretion and neuroblastoma angiogenesis via the YAP/RUNX2/SRSF1 axis - Min Bao; Yi Chen; Ji-Ting Liu; Han Bao; Wen-Bin Wang; Ying-Xin Qi; Fan Lv (Angiogenesis, 2022)

Comparative phylogeography of Acanthocalyx (Caprifoliaceae) reveals distinct genetic structures in the Himalaya–Hengduan Mountains - Qi-Yong Mu; Chih-Chieh Yu; Yan Wang; Ting-Shen Han; Hui Wang; Wen-Na Ding; Qiu-Yue Zhang; Shook Ling Low; Quan-Jing Zheng; Chuan Peng; Zheng-Yan Hu; Yao-Wu Xing (Alpine Botany, 2022)

miRNA–mRNA Integrative Analysis Reveals the Roles of miRNAs in Hypoxia-Altered Embryonic Development- and Sex Determination-Related Genes of Medaka Fish - Keng Po Lai; Nathan Yi Kan Tam; Yuelong Chen; Chi Tim Leung; Xiao Lin; Chau Fong Tsang; Yin Cheung Kwok; William Ka Fai Tse; Shuk Han Cheng; Ting Fung Chan; Richard Yuen Chong Kong (Frontiers in Marine Science, 2022)
Recent studies have shown hypoxia to be an endocrine disruptor that impairs sex differentiation and reproductive function, leading to male-biased F1 populations in fish. However, the molecular mechanisms through which hypoxia alters fish sex differentiation and therefore sex ratios remain poorly understood. In order to understand the potential role of miRNAs in mediating hypoxia-altered sex determination and differentiation in fish, we conducted small RNA sequencing and transcriptome sequencing on marine medaka ( Oryzias melastigma ) embryos that were exposed to hypoxia (2.0 ± 0.2 mg O 2 L – 1) for 40 h (encompassing a critical window of sex determination). We identified dysregulated miRNAs and mRNAs in the hypoxia-exposed embryo, and bioinformatic analysis of the integrative small RNA sequencing and transcriptome sequencing results revealed hypoxia to cause alterations of genes related to embryonic development through miRNA regulation. Importantly, we have identified miRNA-mRNA pairs that were reported to play roles in gonad development (novel miR-145-col9a3 and novel miRNA-94- arid5b), in sex hormone response (novel miRNA-210-ca2, novel miRNA-106-nr2f2, nbr-miR-29c-nr4a1, and ola-miR-92b-akr1d1), and in sex characteristic development (novel miRNA-145-mns1, nle-miR-20-sord, and ipu-miR-219b-abcc8). Our findings highlighted the possible roles of miRNA–mRNA in regulation of embryonic development and sex determination in response to hypoxic stress.

Current Dependent Dispersal Characteristics of Japanese Glass Eel around Taiwan - Kuan-Mei Hsiung; Yen-Ting Lin; Yu-San Han (Journal of Marine Science and Engineering, 2022)
Japanese eel larvae are passively transported to the East Asian Continental Shelf by the North Equatorial Current, Kuroshio and Kuroshio intrusion currents, and coastal currents. Previous studies have investigated the dispersal characteristics and pathways of Japanese glass eels. However, there are still limitations in these studies. According to long-term (2010–2020) catch data from the Fisheries Agency in Taiwan, the distribution and time series of glass eels recruitment to Taiwan are closely related to the surrounding ocean currents. Recruitment begins in eastern Taiwan via the mainstream Kuroshio and in southern Taiwan via the Taiwan Strait Warm Current. In central Taiwan, recruitment occurs from southern Taiwan, as well as from mainland China via the southern branch of the China Coast Current (CCC). The latest recruitment occurred in northern Taiwan and mainly comprised glass eels from mainland China via the northern branch of the CCC. A stronger monsoon during the La Niña phase could affect the recruitment time series in northern and eastern Taiwan. This study suggests that the recruitment directionality of glass eels is an indicator of the flow field of ocean/coastal currents and elucidates the dispersal characteristics of glass eels in the waters around Taiwan.

Williamsia soli sp. nov., an actinobacterium isolated from soil at a thermal power plant in Yantai, China - Ming-Jing Zhang; Xue-Han Li; Li-Yang Peng; Shuai-Ting Yun; Zhuo-Cheng Liu; Yan-Xia Zhou (Archives of Microbiology, 2022)

Evaluation of the Crack Propagation Capacity of Hard Rock Based on Stress-Induced Deformation Anisotropy and the Propagation Angle of Volumetric Strain - Qiang Han; Xia-Ting Feng; Chengxiang Yang; Rui Kong; Jun Zhao; Yan Zhang (Rock Mechanics and Rock Engineering, 2021)

Three new diterpenoids from Euphorbia peplus - Yan-Ni Chen; Qing-Yun Lu; Dong-Mei Li; Ying-Yao Li; Xue-Xue Pu; Bo-Ting Li; Xiao-Han Tang; Hong-Yu Tang; Shuai Liu; Lei Yang; Yu Zhang; Ying-Tong Di; et al. (Natural Product Research, 2021)

Estimating dynamic population served by wastewater treatment plants using location-based services data - Han Yu; Xue-Ting Shao; Si-Yu Liu; Wei Pei; Xiang-Peng Kong; Zhuang Wang; De-Gao Wang (Environmental Geochemistry and Health, 2021)

Echinicola salinicaeni sp. nov., a novel bacterium isolated from saltern mud - Han Zhao; Chun-Yi Song; Rui Yin; Yan-Jun Yi; Shuai-Ting Yun; Ying-Xiu Li; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2021)

A network pharmacology study with molecular docking to investigate the possibility of licorice against posttraumatic stress disorder - Zhi-Kun Qiu; Zhi-Ting Liu; Jia-Li Pang; Han-Biao Wu; Xu Liu; Ze-Min Yang; Xiong Li; Ji-Sheng Chen (Metabolic Brain Disease, 2021)

γ-Aminobutyric Acid Participates in the Adult-Phase Adventitious Rooting Recalcitrance - Xu Li; Xiaozhao Xu; Fei Shen; Wei Li; Changpeng Qiu; Ting Wu; Yi Wang; Xuefeng Xu; Zhenhai Han; Xinzhong Zhang (Journal of Plant Growth Regulation, 2021)
In many tree species especially the rooting-recalcitrant woody perennials, the adventitious root (AR) in the juvenile phase can be easily induced by exogenous auxin, but AR formation becomes recalcitrant in the adult phase. Also, it is reported that the γ-aminobutyric acid (GABA) inhibits primary root growth in Arabidopsis and the AR formation in poplar ( Populus ssp). So far, how GABA affects or is affected by the ontogenetic phase or auxin remains unclear. Here, we used an apple rootstock, Malus xiaojinensis, and tobacco ( Nicotiana benthamiana ) to investigate this question. We first analyzed the content of GABA, the activity of GABA synthetic enzyme GAD, and the expression of the coding gene MxGADs, respectively, in leafy cuttings of juvenile and adult phase. Next, the effect of exogenous GABA on AR formation was examined in in vitro shoots of M. xiaojinensis and tobacco. Interestingly, significant and consistent increases in GABA concentration, GAD activity, and expression of MxGAD genes in response to exogenous indole butyric acid (IBA) were detected in adult-phase cuttings, but not in juvenile-phase cuttings. Exogenous GABA application inhibited the AR formation by delaying rooting time and reducing root number and the total root length in in vitro shoots of both M. xiaojinensis and tobacco. The expression of MxPIN members increased in response to IBA application, but these changes were restrained by the addition of GABA. These results indicate that both the loss of juvenility and IBA are required to trigger GABA accumulation. GABA may affect the AR formation as a co-actor by inhibiting polar auxin transport. Together, these findings facilitate the understanding of the regulatory network among GABA, juvenility, and auxin signaling on the AR formation.

Evaluating the efficacy of osthole and matrine for control of Sorghum purple spot - Yubo Sun; Yue Chen; Ting Liu; Yingying Wang; Yong Wang; Lirong Han; Zhiqing Ma; Juntao Feng (Journal of Plant Diseases and Protection, 2021)

Adverse effects of short-term personal exposure to fine particulate matter on the lung function of patients with chronic obstructive pulmonary disease and asthma: a longitudinal panel study in Beijing, China - Ruirui Duan; Hongtao Niu; Tao Yu; Ke Huang; Han Cui; Chen Chen; Ting Yang; Chen Wang (Environmental Science and Pollution Research, 2021)

The lincRNA XH123 is involved in cotton cold-stress regulation - Zeyi Cao; Ting Zhao; Luyao Wang; Jin Han; Jinwen Chen; Yupeng Hao; Xueying Guan (Plant Molecular Biology, 2021)

Research on Analysis of Evaluation Influence Factors of Air Quality Opinions Sentiment Value and Quantification Method - Ji Min; Han Yunxiu; Sun Yong; Jin Fengxiang; Li Ting (Water, Air, & Soil Pollution, 2021)

Devonian-Carboniferous boundary in China - Wenkun Qie; Yuanlin Sun; Wen Guo; Ting Nie; Bo Chen; Junjun Song; Kun Liang; Baoan Yin; Shupeng Han; Junying Chang; Xiangdong Wang (Palaeobiodiversity and Palaeoenvironments, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

The Knowledge and Attitude Towards Advance Care Planning Among Chinese Patients with Advanced Cancer - Xiao-Ting Hou; Yu-Han Lu; Hong Yang; Ren-Xiu Guo; Yun Wang; Li-Hong Wen; Ya-Ru Zhang; Hong-Yu Sun (Journal of Cancer Education, 2021)

Intraspecific recurrent selection in V. vinifera: an effective method for breeding of high quality, disease-, cold-, and drought -resistant grapes - Zhi-Lei Wang; Ting-Ting Xue; Fei-Fei Gao; Liang Zhang; Xing Han; Ying Wang; Miao Hui; Dong Wu; Hua Li; Hua Wang (Euphytica, 2021)

Pigment profile and gene analysis revealed the reasons of petal color difference of crabapples - Ting Shen; Meiling Han; Qianrui Liu; Chen Yang; Jiaxin Meng; Houhua Li (Brazilian Journal of Botany, 2021)

Large Deformation Control of Deep Roadways in Fractured Hard Rock Based on Cracking-Restraint Method - Yue-Mao Zhao; Xia-Ting Feng; Quan Jiang; Yong Han; Yang-Yi Zhou; Hui-Gao Guo; Yong-Yuan Kou; Ying-En Shi (Rock Mechanics and Rock Engineering, 2021)

Cytological and morphology characteristics of natural microsporogenesis within Camellia oleifera - Xiaoyu Zhang; Hailang Tong; Zhiqiang Han; Long Huang; Jing Tian; Zhixing Fu; Yunyi Wu; Ting Wang; Deyi Yuan (Physiology and Molecular Biology of Plants, 2021)

Regulating CH4, N2O, and NO emissions from an alkaline paddy field under rice–wheat rotation with controlled release N fertilizer - Ting Lan; Heng Zhang; Yong Han; Ouping Deng; Xiaoyan Tang; Ling Luo; Jian Zeng; Guangdeng Chen; Changquan Wang; Xuesong Gao (Environmental Science and Pollution Research, 2021)

EmhR is an indole‐sensing transcriptional regulator responsible for the indole‐induced antibiotic tolerance in Pseudomonas fluorescens - Jian‐Ting Han; Di‐Yin Li; Meng‐Yuan Zhang; Xiao‐Quan Yu; Xiang‐Xue Jia; Hang Xu; Xu Yan; Wen‐Juan Jia; Shaomin Niu; Megan L. Kempher; Xuanyu Tao; Yong‐Xing He (Environmental Microbiology, 2021)
Summary Indole is well known as an interspecies signalling molecule to modulate bacterial physiology; however, it is not clear how the indole signal is perceived and responded to by plant growth promoting rhizobacteria (PGPR) in the rhizosphere. Here, we demonstrated that indole enhanced the antibiotic tolerance of Pseudomonas fluorescens 2P24, a PGPR well known for its biocontrol capacity. Proteomic analysis revealed that indole influenced the expression of multiple genes including the emhABC operon encoding a major multidrug efflux pump. The expression of emhABC was regulated by a TetR‐family transcription factor EmhR, which was demonstrated to be an indole‐responsive regulator. Molecular dynamics simulation showed that indole allosterically affected the distance between the two DNA‐recognizing helices within the EmhR dimer, leading to diminished EmhR–DNA interaction. It was further revealed the EmhR ortholog in Pseudomonas syringae was also responsible for indole‐induced antibiotic tolerance, suggesting this EmhR‐dependent, indole‐induced antibiotic tolerance is likely to be conserved among Pseudomonas species. Taken together, our results elucidated the molecular mechanism of indole‐induced antibiotic tolerance in Pseudomonas species and had important implications on how rhizobacteria sense and respond to indole in the rhizosphere.

Evaluation Method of Rock Brittleness under True Triaxial Stress States Based on Pre-peak Deformation Characteristic and Post-peak Energy Evolution - Yan Zhang; Xia-Ting Feng; Chengxiang Yang; Qiang Han; Zhaofeng Wang; Rui Kong (Rock Mechanics and Rock Engineering, 2021)

Neuroprotective Effects of Molecular Hydrogen: A Critical Review - Wei Chen; Han-Ting Zhang; Shu-Cun Qin (Neuroscience Bulletin, 2021)

Bioinformatics analysis of WRKY transcription factors in grape and their potential roles prediction in sugar and abscisic acid signaling pathway - Ting Huang; Jinli Yang; Dan Yu; Xiaoyu Han; Xiuqin Wang (Journal of Plant Biochemistry and Biotechnology, 2021)

Curcumin protects thymus against D-galactose-induced senescence in mice - Jie-han Li; Ting-ting Wei; Li Guo; Jia-hui Cao; Yuan-kang Feng; Shu-ning Guo; Guo-hong Liu; Yi Ding; Yu-rong Chai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

The application of an absorbent-amended microalgal-bacterial system for enhancing hydrothermal liquefaction wastewater treatment and resource recovery - Ting Han; Mengzi Wang; Haifeng Lu; Yuanhui Zhang; Guangming Zhang; Baoming Li; Wei Cao (Journal of Applied Phycology, 2021)

Compound heterozygous mutation of the ASXL3 gene causes autosomal recessive congenital heart disease - Fang Fu; Ru Li; Ting-ying Lei; Dan Wang; Xin Yang; Jin Han; Min Pan; Li Zhen; Jian Li; Fa-tao Li; Xiang-yi Jing; Dong-zhi Li; et al. (Human Genetics, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Dapagliflozin suppresses ER stress and protects doxorubicin-induced cardiotoxicity in breast cancer patients - Wei-Ting Chang; Yu-Wen Lin; Chung-Han Ho; Zhih-Cherng Chen; Ping-Yen Liu; Jhih-Yuan Shih (Archives of Toxicology, 2021)

Diversity and potential biogeochemical impacts of viruses in bulk and rhizosphere soils - Li Bi; Dan‐Ting Yu; Shuai Du; Li‐Mei Zhang; Li‐Yu Zhang; Chuan‐Fa Wu; Chao Xiong; Li‐Li Han; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Viruses can affect microbial dynamics, metabolism and biogeochemical cycles in aquatic ecosystems. However, viral diversity and functions in agricultural soils are poorly known, especially in the rhizosphere. We used virome analysis of eight rhizosphere and bulk soils to study viral diversity and potential biogeochemical impacts in an agro‐ecosystem. The order Caudovirales was the predominant viral type in agricultural soils, with Siphoviridae being the most abundant family. Phylogenetic analysis of the terminase large subunit of Caudovirales identified high viral diversity and three novel groups. Viral community composition differed significantly between bulk and rhizosphere soils. Soil pH was the main environmental driver of the viral community structure. Remarkably, abundant auxiliary carbohydrate‐active enzyme (CAZyme) genes were detected in viromes, including glycoside hydrolases, carbohydrate esterases and carbohydrate‐binding modules. These results demonstrate that virus‐encoded putative auxiliary metabolic genes or metabolic genes that may change bacterial metabolism and indirectly contribute to biogeochemical cycling, especially carbon cycling, in agricultural soil.

Improving the Diagnostic Ability of the Sleep Apnea Screening System Based on Oximetry by Using Physical Activity Data - Cheng-Han Wu; Jui-Hsuan Lee; Terry B. J. Kuo; Chun-Ting Lai; Lieber P. H. Li; Cheryl C. H. Yang (Journal of Medical and Biological Engineering, 2020)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Phosphodiesterase 2 inhibitor Hcyb1 reverses corticosterone-induced neurotoxicity and depression-like behavior - Meng-Jia Zhu; Jing Shi; Yong Chen; Guobing Huang; Xiong-Wei Zhu; Sam Zhang; Xian-Feng Huang; Guo-Qiang Song; Han-Ting Zhang; Heng-Ming Ke; James M. O’Donnell; Li-Qun Wang; et al. (Psychopharmacology, 2020)

The effect of blastomere loss during frozen embryo transfer on the transcriptome of offspring’s umbilical cord blood - Yan-Ting Wu; Ze-Han Dong; Cheng Li; Dai-Zhan Zhou; Jun-Yu Zhang; Yan Wu; Jing-Jing Xu; Yu Wang; Xiao-Qun Ye; Jian-Zhong Sheng; Li Wang; He-Feng Huang (Molecular Biology Reports, 2020)

Structure and Function of Bacterial Microbiota in Eucommia ulmoides Bark - Chunbo Dong; Ting Yao; Zhiyuan Zhang; Wanhao Chen; Jiangdong Liang; Yanfeng Han; Jianzhong Huang; Sunil K. Deshmukh; Zongqi Liang (Current Microbiology, 2020)

Differences in anti-inflammatory properties of water soluble and insoluble bioactive polysaccharides in lipopolysaccharide-stimulated RAW264.7 macrophages - Chun-Han Su; Yun-Ting Tseng; Kai-Yin Lo; Ming-Nan Lai; Lean-Teik Ng (Glycoconjugate Journal, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

A sensitive and rapid bacterial antibiotic susceptibility test method by surface enhanced Raman spectroscopy - Shijie Fu; Xiwen Wang; Ting Wang; Zhiping Li; Deming Han; Chunsheng Yu; Cui Yang; Han Qu; Hang Chi; Yutian Wang; Song Li; Baihui Tian; et al. (Brazilian Journal of Microbiology, 2020)

Microbial characteristics of culturable fungi and bacteria in aerosol particles of a coastal region - Yao Wang; Jianhua Qi; Chen Han; Ting Zhang; Dahai Zhang (Aerobiologia, 2020)

Neo-debromoaplysiatoxin C, with new structural rearrangement, derived from debromoaplysiatoxin - Yang-Hua Tang; Ting-Ting Liang; Ting-Ting Fan; Lawrence Jordan Keen; Xiao-Dan Zhang; Lin Xu; Qi Zhao; Rong Zeng; Bing-Nan Han (Natural Product Research, 2020)

Discovery of numerous pingos and comet-shaped depressions offshore southwestern Taiwan - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Ingo Klaucke; Ho-Han Hsu; Chih-Chieh Su; Roberto Gwiazda; David W. Caress (Geo-Marine Letters, 2020)

Functional characterisation of fatty acyl desaturase, Fads2, and elongase, Elovl5, in the Boddart's goggle‐eyed goby Boleophthalmus boddarti (Gobiidae) suggests an incapacity for long‐chain polyunsaturated fatty acid biosynthesis - Han‐Jie Soo; Ka Kei Sam; Joey Chong; Nyok‐Sean Lau; Seng Yeat Ting; Meng‐Kiat Kuah; Sim Yee Kwang; Manogoran Ranjani; Alexander Chong Shu‐Chien (Journal of Fish Biology, 2020)
The biosynthesis of long‐chain polyunsaturated fatty acids (LC‐PUFA), a process to convert C18 polyunsaturated fatty acids into eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA) or arachidonic acid (ARA), requires the concerted activities of two enzymes, the fatty acyl desaturase (Fads) and elongase (Elovl). This study highlights the cloning, functional characterisation and tissue expression pattern of a Fads and an Elovl from the Boddart's goggle‐eyed goby ( Boleophthalmus boddarti ), a mudskipper species widely distributed in the Indo‐Pacific region. Phylogenetic analysis revealed that the cloned fads and elovl are clustered with other teleost orthologs, respectively. The investigation of the genome of several mudskipper species, namely Boleophthalmus pectinirostris , Periophthalmus schlosseri and Periophthalmus magnuspinnatus, revealed a single Fads2 and two elongases, Elovl5 and Elovl4 for each respective species. A heterologous yeast assay indicated that the B. boddarti Fads2 possessed low desaturation activity on C18 PUFA and no desaturation on C20 and C22 PUFA substrates. In comparison, the Elovl5 showed a wide range of substrate specificity, with a capacity to elongate C18, C20 and C22 PUFA substrates. An amino acid residue that affects the capacity to elongate C22:5n‐3 was identified in the B. boddarti Elovl5. Both genes are highly expressed in brain tissue. Among all tissues, DHA is highly concentrated in neuron‐rich tissues, whereas EPA is highly deposited in gills. Taken together, the results showed that due to the inability to perform desaturation steps, B. boddarti is unable to biosynthesise LC‐PUFA, relying on dietary intake to acquire these nutrients.

Acute physiological responses to combined blood flow restriction and low-level laser - Yi-Ching Chen; Yu-Han Su; Yen-Ting Lin; Chien-Chun Huang; Ing-Shiou Hwang (European Journal of Applied Physiology, 2020)

Structural-morphological and sedimentary features of forearc slope off Miyagi, NE Japan: implications for development of forearc basins and plumbing systems - Jih-Hsin Chang; Jin-Oh Park; Tzu-Ting Chen; Asuka Yamaguchi; Tetsuro Tsuru; Yuji Sano; Ho-Han Hsu; Kotaro Shirai; Takanori Kagoshima; Kentaro Tanaka; Chiori Tamura (Geo-Marine Letters, 2020)

Correction to: endoplasmic reticulum stress may activate NLRP3 inflammasomes via TXNIP in preeclampsia - Yong Yang; Jianxin Li; Ting-Li Han; Xianbo Zhou; Hongbo Qi; Philip N. Baker; Wei Zhou; Hua Zhang (Cell and Tissue Research, 2020)

microRNA-499a promotes the progression and chemoresistance of cervical cancer cells by targeting SOX6 - Yibing Chen; Yucen Song; Yanjun Mi; Huan Jin; Jun Cao; Haolong Li; Liping Han; Ting Huang; Xiaofei Zhang; Shumin Ren; Qian Ma; Zhengzhi Zou (Apoptosis, 2020)

Sea-Land Segmentation Using Deep Learning Techniques for Landsat-8 OLI Imagery - Ting Yang; Shenlu Jiang; Zhonghua Hong; Yun Zhang; Yanling Han; Ruyan Zhou; Jing Wang; Shuhu Yang; Xiaohua Tong; Tae-yong Kuc (Marine Geodesy, 2020)

Computational comparison of bone cement and poly aryl-ether-ether-ketone spacer in single-segment posterior lumbar interbody fusion: a pilot study - Chih-Wei Chang; Yu-Hsuan Chung; Chia-Jung Chang; Yen-Nien Chen; Chun-Ting Li; Chih-Han Chang; Yao-Te Peng (Physical and Engineering Sciences in Medicine, 2020)

Sources and ore-forming fluid pathways of carbonate-hosted Pb–Zn deposits in Southwest China: implications of Pb–Zn–S–Cd isotopic compositions - Chong Xu; Hong Zhong; Rui-Zhong Hu; Han-Jie Wen; Wei-Guang Zhu; Zhong-Jie Bai; Hai-Feng Fan; Fang-Fang Li; Ting Zhou (Mineralium Deposita, 2020)

Analysis of flavonoids and anthocyanin biosynthesis-related genes expression reveals the mechanism of petal color fading of Malus hupehensis (Rosaceae) - Meiling Han; Chen Yang; Jing Zhou; Jiabin Zhu; Jiaxin Meng; Ting Shen; Zhuanxia Xin; Houhua Li (Brazilian Journal of Botany, 2020)

Endoplasmic reticulum stress may activate NLRP3 inflammasomes via TXNIP in preeclampsia - Yong Yang; Jianxin Li; Ting-Li Han; Xianbo Zhou; Hongbo Qi; Philip N. Baker; Wei Zhou; Hua Zhang (Cell and Tissue Research, 2020)

Carboxymethylation and acetylation of the polysaccharide from Cordyceps militaris and their α-glucosidase inhibitory activities - Yuan-Yuan Ren; Peng-Peng Sun; Ying-Ping Ji; Xiao-Ting Wang; Shu-Han Dai; Zhen-Yuan Zhu (Natural Product Research, 2020)

Soil respiration in an irrigated oasis agroecosystem: linking environmental controls with plant activities on hourly, daily and monthly timescales - Ting Ma; Gaofeng Zhu; Jinzhu Ma; Kun Zhang; Shangtao Wang; Tuo Han; Shasha Shang (Plant and Soil, 2020)

Removal performance and mechanisms of Cr(VI) by an in-situ self-improvement of mesoporous biochar derived from chicken bone - Ting Yang; Caiyun Han; Jie Tang; Yongming Luo (Environmental Science and Pollution Research, 2020)

A Three-Dimensional Failure Criterion for Hard Rocks Under True Triaxial Compression - Xia-Ting Feng; Rui Kong; Chengxiang Yang; Xiwei Zhang; Zhaofeng Wang; Qiang Han; Gang Wang (Rock Mechanics and Rock Engineering, 2020)

Sensitivity analysis and estimation using a hierarchical Bayesian method for the parameters of the FvCB biochemical photosynthetic model - Tuo Han; Gaofeng Zhu; Jinzhu Ma; Shangtao Wang; Kun Zhang; Xiaowen Liu; Ting Ma; Shasha Shang; Chunlin Huang (Photosynthesis Research, 2020)

Adjuvant therapy with Astragalus membranaceus for post-stroke fatigue: a systematic review - Li Xu; Xiao-Yan Xu; Xue-Qin Hou; Fu-Gang Wang; Shan Gao; Han-Ting Zhang (Metabolic Brain Disease, 2020)

Energy metabolism involved in fertility of the wheat TCMS line YS3038 - Yucui Han; Yujie Gao; Yue Zhao; Dazhong Zhang; Chao Zhao; Fang Xin; Ting Zhu; Mingyang Jian; Qin Ding; Lingjian Ma (Planta, 2019)

The Rho kinase inhibitor fasudil attenuates Aβ1–42-induced apoptosis via the ASK1/JNK signal pathway in primary cultures of hippocampal neurons - Ye Gao; Yuqing Yan; Qingli Fang; Nianping Zhang; Gajendra Kumar; Jihong Zhang; Li-Juan Song; Jiezhong Yu; Linhu Zhao; Han-Ting Zhang; Cun-Gen Ma (Metabolic Brain Disease, 2019)

Construction of a Lactobacillus plantarum Strain Expressing the Capsid Protein of Porcine Circovirus Type 2d (PCV2d) as an Oral Vaccine - Yi-Han Tseng; Cheng-Chu Hsieh; Tsun-Yung Kuo; Je-Ruei Liu; Ting-Yu Hsu; Shu-Chen Hsieh (Indian Journal of Microbiology, 2019)

Epigenetic modification enhances ergot alkaloid production of Claviceps purpurea - Jing-Jing Chen; Meng-Yao Han; Ting Gong; Yun-Ming Qiao; Jin-Ling Yang; Ping Zhu (Biotechnology Letters, 2019)

Relevance of number and physiological status of conspecifics in preventing stress-induced decreases in newly proliferated cells and neuroblasts - Li-Han Sun; Wen-Yu Tzeng; Yi-Han Liao; Wen-Ting Deng; Chianfang G. Cherng; Lung Yu (Psychopharmacology, 2019)

Acute and Chronic Exposure of Toluene Induces Genotoxicity in Different Regions of the Brain in Normal and Allergic Mouse Models - Ting-Ying Laio; Chih-Chun Chen; Han-Hsing Tsou; Tsung-Yun Liu; Hsiang-Tsui Wang (Neurotoxicity Research, 2019)

Magnetic polymer–supported adsorbent with two functional adsorption sites for phosphate removal - Ting Li; Pengwei Huang; Taiwan Liao; Jia Guo; Xiang Yu; Boping Han; Liang Peng; Yi Zhu; Yuanming Zhang (Environmental Science and Pollution Research, 2019)

Effects of deficit irrigation combined with rainwater harvesting planting system on the water use efficiency and maize (Zea mays L.) yield in a semiarid area - Peng Zhang; Ting Wei; Yuling Li; Yan Zhang; Tie Cai; Xiaolong Ren; Qingfang Han; Zhikuan Jia (Irrigation Science, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

3D-QSAR, molecular docking, and new compound design of pyrimidine derivatives as Src small molecule inhibitors - Jun-wei Wang; Ya-ting Deng; Han Chu; Juan Wang; Yong Hu; Zhi-hua Lin (Medicinal Chemistry Research, 2019)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

Measurement of urinary arsenic profiles and DNA hypomethylation in a case–control study of urothelial carcinoma - Chi-Jung Chung; Hui-Ling Lee; Chao-Hsiang Chang; Han Chang; Chiu-Shong Liu; Wei-Ting Jung; Huei-Ju Liu; Saou-Hsing Liou; Mu-Chi Chung; Yu-Mei Hsueh (Archives of Toxicology, 2019)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Dynamics of oxytetracycline and resistance genes in soil under long-term intensive compost fertilization in Northern China - Ming Wu; Hui Han; Xiangnan Zheng; Mohan Bai; Ting Xu; Guo-chun Ding; Ji Li (Environmental Science and Pollution Research, 2019)

Neural Differentiation of Mouse Neural Stem Cells as a Tool to Assess Developmental Neurotoxicity of Drinking Water in Taihu Lake - Yang Zhou; Yu Fu; Zhendong Bai; Peixin Li; Bo Zhao; Yuehua Han; Ting Xu; Ningyan Zhang; Lin Lin; Jian Cheng; Jun Zhang; Jing Zhang (Biological Trace Element Research, 2019)

The effect of caffeine on cerebral metabolism during alpha-chloralose anesthesia differs from isoflurane anesthesia in the rat brain - Shin-Lei Peng; Han Chiu; Chun-Yi Wu; Chiun-Wei Huang; Yi-Hsiu Chung; Cheng-Ting Shih; Wu-Chung Shen (Psychopharmacology, 2019)

GIS-based landslide susceptibility mapping using hybrid integration approaches of fractal dimension with index of entropy and support vector machine - Ting-yu Zhang; Ling Han; Heng Zhang; Yong-hua Zhao; Xi-an Li; Lei Zhao (Journal of Mountain Science, 2019)

Epidemiological trends and virological traits of hepatitis B virus infection in pregnant women and neonates - Ting-Ting Peng; Qiu-E Cai; Min Yang; Shao-Ping Chen; Feng Chen; Miao Wang; Ling Peng; Gary Wong; Chen-Guang Shen; Wen-Bing Cheng; Sai-Yun Liu; Ya-Bai Peng; et al. (Archives of Virology, 2019)

The antitoxin MqsA homologue in Pseudomonas fluorescens 2P24 has a rewired regulatory circuit through evolution - Yong Wang; Si‐Ping Zhang; Meng‐Yuan Zhang; Megan L. Kempher; Ding‐Ding Guo; Jian‐Ting Han; Xuanyu Tao; Yi Wu; Li‐Qun Zhang; Yong‐Xing He (Environmental Microbiology, 2019)
Summary The mqsRA operon encodes a toxin–antitoxin pair that was characterized to participate in biofilm and persister cell formation in Escherichia coli . Notably, the antitoxin MqsA possesses a C‐terminal DNA‐binding domain that recognizes the [5’‐AACCT(N) 2‐4 AGGTT‐3′] motif and acts as a transcriptional regulator controlling multiple genes including the general stress response regulator RpoS. However, it is unknown how the transcriptional circuits of MqsA homologues have changed in bacteria over evolutionary time. Here, we found mqsA in Pseudomonas fluorescens ( PfmqsA ) is acquired through horizontal gene transfer and binds to a slightly different motif [5′‐TACCCT(N) 3 AGGGTA‐3′], which exists upstream of the PfmqsRA operon. Interestingly, an adjacent GntR‐type transcriptional regulator, which was termed AgtR, is under negative control of PfMqsA. It was further demonstrated that PfMqsA reduces production of biofilm components through AgtR, which directly regulates the pga and fap operons involved in the synthesis of extracellular polymeric substances. Moreover, through quantitative proteomics analysis, we showed AgtR is a highly pleiotropic regulator that influences up to 252 genes related to diverse processes including chemotaxis, oxidative phosphorylation and carbon and nitrogen metabolism. Taken together, our findings suggest the rewired regulatory circuit of PfMqsA influences diverse physiological aspects of P. fluorescens 2P24 via the newly characterized AgtR.

Downregulation of the auxin transporter gene SlPIN8 results in pollen abortion in tomato - Zengyu Gan; Yi Feng; Ting Wu; Yi Wang; Xuefeng Xu; Xinzhong Zhang; Zhenhai Han (Plant Molecular Biology, 2019)

Therapeutic potentials of the Rho kinase inhibitor Fasudil in experimental autoimmune encephalomyelitis and the related mechanisms - Yuqing Yan; Jiezhong Yu; Ye Gao; Gajendra Kumar; Minfang Guo; Yijin Zhao; Qingli Fang; Huiyu Zhang; Jingwen Yu; Yuqiang Jiang; Han-Ting Zhang; Cun-Gen Ma (Metabolic Brain Disease, 2019)

Characteristics of single atmospheric particles in a heavily polluted urban area of China: size distributions and mixing states - Li Li; Qiyuan Wang; Xu Zhang; Yuanyuan She; Jiamao Zhou; Yang Chen; Ping Wang; Suixin Liu; Ting Zhang; Wenting Dai; Yongming Han; Junji Cao (Environmental Science and Pollution Research, 2019)

Characterizations and mechanisms for synthesis of chitosan-coated Na–X zeolite from fly ash and As(V) adsorption study - Caiyun Han; Ting Yang; Hang Liu; Liu Yang; Yongming Luo (Environmental Science and Pollution Research, 2019)

In situ resuspension rate monitoring method in the littoral zone with multi-ecotypes of a shallow wind-disturbed lake - Chuang Qi; Xiao-guang Xu; Kuan Shi; Li-min Zhang; Yang Zhou; Hui Lin; Xin-ting Wu; Guo-xiang Wang; Han Meng (Environmental Science and Pollution Research, 2019)

Paleogeomorphology restoration and the controlling effects of paleogeomorphology on karst reservoirs: a case study of an ordovician-aged section in Tahe oilfield, Tarim Basin, China - Changcheng Han; Chengyan Lin; Ting Wei; Chunmei Dong; Lihua Ren; Xianguo Zhang; Li Dong; Xu Zhao (Carbonates and Evaporites, 2019)

Two new secondary metabolites from a mangrove-derived fungus Cladosporium sp. JJM22 - Jia-Ting Wu; Cai-Juan Zheng; Bin Zhang; Xue-Ming Zhou; Qi Zhou; Guang-Ying Chen; Zhuo-Er Zeng; Jin-Long Xie; Chang-Ri Han; Ji-Xing Lyu (Natural Product Research, 2019)

Viral metagenomics analysis and eight novel viral genomes identified from the Dushanzi mud volcanic soil in Xinjiang, China - Dan-Ting Yu; Ji-Zheng He; Li-Mei Zhang; Li-Li Han (Journal of Soils and Sediments, 2019)

A Critical Time-Window for the Selective Induction of Hippocampal Memory Consolidation by a Brief Episode of Slow-Wave Sleep - Yi Lu; Zheng-Gang Zhu; Qing-Qing Ma; Yun-Ting Su; Yong Han; Xiaodong Wang; Shumin Duan; Yan-Qin Yu (Neuroscience Bulletin, 2018)

Immobilization of Calcined Layered Double Hydroxide into Alginate Hydrogel Beads for PNP and PAP Removal: Kinetics, Isotherms, Thermodynamics, and Mechanism - Ranran Shan; Yuan He; Ting Zi; Guiyan Wang; Xiuyu Liu; Zhe Han; Tao Zhang; Ying Zhu (Water, Air, & Soil Pollution, 2018)

Histamine Excites Striatal Dopamine D1 and D2 Receptor-Expressing Neurons via Postsynaptic H1 and H2 Receptors - Qian-Xing Zhuang; Han-Ting Xu; Xu-Juan Lu; Bin Li; Wing-Ho Yung; Jian-Jun Wang; Jing-Ning Zhu (Molecular Neurobiology, 2018)

A corn straw-based diet increases release of inflammatory cytokines in peripheral blood mononuclear cells of dairy cows - Yan-yi Che; Xiao-jing Xia; Bo-ping He; Yuan-yuan Gao; Wen-bo Ren; Hong-tao Liu; Jian-fang Liu; Ting-hao Huang; Wen-yu Han; Lian-cheng Lei (Journal of Zhejiang University-SCIENCE B, 2018)

Bioactive furanocoumarins from the stems and leaves of Clausena hainanensis - Yan-Lei Ma; Chao Zhang; Wan-Hui Zhao; Shi Shi; Dan-Nv He; Pan Zhang; Xiao-Hong Liu; Ting-Ting Han; Yan-Hui Fu; Yan-Ping Liu (Natural Product Research, 2018)

Docking study and antiosteoporosis effects of a dibenzylbutane lignan isolated from Litsea cubeba targeting Cathepsin K and MEK1 - Wei Peng; Hui Shen; Bing Lin; Ping Han; Changhui Li; Qiaoyan Zhang; Bingzhu Ye; Khalid Rahman; Hailiang Xin; Luping Qin; Ting Han (Medicinal Chemistry Research, 2018)

Inhibition of phosphodiesterase 2 by Bay 60-7550 decreases ethanol intake and preference in mice - Jing Shi; Huaxia Liu; Jianchun Pan; Jie Chen; Nianping Zhang; Kaiping Liu; Ning Fei; James M. O’Donnell; Han-Ting Zhang; Ying Xu (Psychopharmacology, 2018)

Negative regulation of MAVS-mediated innate immune response by ASC - Yue Han; Xiang He; Congwen Wei; Ting Song; Ling Zou; Zihui Li; Jiazhou Ye; Lunan Qi; Lequn Li; Hui Zhong; Feixiang Wu (Molecular and Cellular Biochemistry, 2018)

Dietary patterns with fresh fruits and vegetables consumption and quality of sleep among older adults in mainland China - Yen-Han Lee; Yen-Chang Chang; Yi-Ting Lee; Mack Shelley; Ching-Ti Liu (Sleep and Biological Rhythms, 2018)

Novel antidepressant effects of Paeonol alleviate neuronal injury with concomitant alterations in BDNF, Rac1 and RhoA levels in chronic unpredictable mild stress rats - Xiu-Ling Zhu; Jing-Jing Chen; Fei Han; Chuan Pan; Ting-Ting Zhuang; Ya-Fei Cai; Ya-Ping Lu (Psychopharmacology, 2018)

Cyclic nucleotide phosphodiesterases: potential therapeutic targets for alcohol use disorder - Rui-Ting Wen; Fang-Fang Zhang; Han-Ting Zhang (Psychopharmacology, 2018)

D-Cycloserine Ameliorates Autism-Like Deficits by Removing GluA2-Containing AMPA Receptors in a Valproic Acid-Induced Rat Model - Han-Fang Wu; Po See Chen; Ya-Ting Hsu; Chi-Wei Lee; Tzu-Feng Wang; Yi-Ju Chen; Hui-Ching Lin (Molecular Neurobiology, 2018)

Alteration of SlYABBY2b gene expression impairs tomato ovary locule number and endogenous gibberellin content - Hui Li; Mei-hua Sun; Ming-fang Qi; Jiao Xing; Tao Xu; Han-ting Liu; Tian-lai Li (Journal of Zhejiang University-SCIENCE B, 2018)

Preparation of Modified Konjac Glucomannan Nanoparticles and their Application as Vaccine Adjuvants to Promote Ovalbumin-Induced Immune Response in Mice - Na Chen; Pei Zhu; Ting Du; Kai Han; Dang Wang; Jianfeng Ye; Shaobo Xiao; Xiaozhou Ye; Yun Wang (Pharmaceutical Research, 2018)

Characterization of industrial odor sources in Binhai New Area of Tianjin, China - Bo Han; Ya-ting Liu; Jian-hui Wu; Yin-chang Feng (Environmental Science and Pollution Research, 2018)

Methylation of secreted frizzled-related protein 1 (SFRP1) promoter downregulates Wnt/β-catenin activity in keloids - Jiaqi Liu; Huayu Zhu; Hongtao Wang; Jun Li; Fu Han; Yang Liu; Wanfu Zhang; Ting He; Na Li; Zhao Zheng; Dahai Hu (Journal of Molecular Histology, 2018)

MdPIN1b encodes a putative auxin efflux carrier and has different expression patterns in BC and M9 apple rootstocks - Zengyu Gan; Yi Wang; Ting Wu; Xuefeng Xu; Xinzhong Zhang; Zhenhai Han (Plant Molecular Biology, 2018)

Down-regulation of Noggin and miR-138 coordinately promote osteogenesis of mesenchymal stem cells - Xing-Kun Sun; Jin Zhou; Lei Zhang; Tian Ma; Yu-Han Wang; Yan-Mei Yang; Yan-Ting Tang; Hong Li; Li-Jun Wang (Journal of Molecular Histology, 2017)

Isolation and characterization of 44 SNP markers in Pseudogyrincheilus procheilus - Ting Liu; Shikai Li; Wei Wang; Bize Han; Xing Yang (Conservation Genetics Resources, 2017)

Complete chloroplast genome sequence of Pedicularis cheilanthifolia, an alpine plant in China - Ruiting Zhang; Jiao Wang; Kai Han; Ting Ren; Shuyun Zeng; Edward Biffin; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

Characterization of the complete chloroplast genome of the Cortusa matthioli subsp. pekinensis (Primulaceae) - Jiao Wang; Ruiting Zhang; Ting Ren; Kai Han; Shuyun Zeng; Edward Biffin; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

20(S)-25-methoxyl-dammarane-3β, 12β, 20-triol negatively regulates activation of STAT3 and ERK pathways and exhibits anti-cancer effects in HepG2 cells - Hui-Han Ai; Zi-Long Zhou; Lu-Guo Sun; Mei-Ting Yang; Wei Li; Chun-Lei Yu; Zhen-Bo Song; Yan-Xin Huang; Yin Wu; Lei Liu; Xiao-Guang Yang; Yu-Qing Zhao; et al. (Apoptosis, 2017)

Attenuation of ethanol abstinence-induced anxiety- and depressive-like behavior by the phosphodiesterase-4 inhibitor rolipram in rodents - Mei-Fang Gong; Rui-Ting Wen; Ying Xu; Jian-Chun Pan; Ning Fei; Yan-Meng Zhou; Jiang-Ping Xu; Jian-Hui Liang; Han-Ting Zhang (Psychopharmacology, 2017)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Sequential combination of docetaxel with a SHP-1 agonist enhanced suppression of p-STAT3 signaling and apoptosis in triple negative breast cancer cells - Chun-Yu Liu; Kuen-Feng Chen; Tzu-I Chao; Pei-Yi Chu; Chun-Teng Huang; Tzu-Ting Huang; Hsiu-Ping Yang; Wan-Lun Wang; Chia-Han Lee; Ka-Yi Lau; Wen-Chun Tsai; Jung-Chen Su; et al. (Journal of Molecular Medicine, 2017)

The phosphodiesterase-4 inhibitor roflumilast decreases ethanol consumption in C57BL/6J mice - Xin Liu; Pi-Da Hao; Ming-Feng Yang; Jing-Yi Sun; Lei-Lei Mao; Cun-Dong Fan; Zong-Yong Zhang; Da-Wei Li; Xiao-Yi Yang; Bao-Liang Sun; Han-Ting Zhang (Psychopharmacology, 2017)

Study of the Binding between Camptothecin Analogs and FTO by Spectroscopy and Molecular Docking - Ting Ren; Zechun Wang; Lijiao Zhang; Ning Wang; Xinxin Han; Ruiyong Wang; Junbiao Chang (Journal of Fluorescence, 2017)

Characterization of the complete chloroplast genome sequence of Lysionotus pauciflorus (Gesneriaceae) - Ting Ren; Wei Zheng; Kai Han; Shuyun Zeng; Jianhua Zhao; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

Erratum to: Lentiviral-Mediated Netrin-1 Overexpression Improves Motor and Sensory Functions in SCT Rats Associated with SYP and GAP-43 Expressions - Xue Fei Han; Yuan Zhang; Liu Lin Xiong; Yang Xu; Piao Zhang; Qing Jie Xia; Ting Hua Wang; Ying Chun Ba (Molecular Neurobiology, 2017)

Antidepressant-Like and Anxiolytic-Like Effects of ZBD-2, a Novel Ligand for the Translocator Protein (18 kDa) - Dong-sheng Wang; Jing Han; Shuo Li; Ting Sun; Yan-yan Guo; Wen-bo Kang; Zhen Tian; Jian-ning Zhao; Gang Liu; Shui-bing Liu; Ming-gao Zhao (NeuroMolecular Medicine, 2017)

Unique community structure of viruses in a glacier soil of the Tianshan Mountains, China - Li-Li Han; Dan-Ting Yu; Li-Mei Zhang; Jun-Tao Wang; Ji-Zheng He (Journal of Soils and Sediments, 2017)

Development of high-density interspecific genetic maps for the identification of QTLs conferring resistance to Valsa ceratosperma in apple - Yi Tan; Song Lv; Xinying Liu; Ting Gao; Tianhong Li; Yi Wang; Ting Wu; Xinzhong Zhang; Yuepeng Han; Schuyler S. Korban; Zhenhai Han (Euphytica, 2017)

Detection of genotoxic effects of drinking water disinfection by-products using Vicia faba bioassay - Yu Hu; Li Tan; Shao-Hui Zhang; Yu-Ting Zuo; Xue Han; Na Liu; Wen-Qing Lu; Ai-Lin Liu (Environmental Science and Pollution Research, 2017)

Adenovirus-mediated shRNA interference against HSV-1 replication in vitro - Bo Song; Xinjing Liu; Qingzhi Wang; Rui Zhang; Ting Yang; Zhiqiang Han; Yuming Xu (Journal of NeuroVirology, 2016)

Influence of Large Syncline on In Situ Stress Field: A Case Study of the Kaiping Coalfield, China - Jun Han; Hongwei Zhang; Bin Liang; Hai Rong; Tianwei Lan; Yuanzheng Liu; Ting Ren (Rock Mechanics and Rock Engineering, 2016)

Electrospun fibrous silk fibroin/poly(L-lactic acid) scaffold for cartilage tissue engineering - Weiwei Liu; Zhengqiang Li; Lu Zheng; Xiaoyan Zhang; Peng Liu; Ting Yang; Bing Han (Tissue Engineering and Regenerative Medicine, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Depot-specific effects of treadmill running and rutin on white adipose tissue function in diet-induced obese mice - Neng Chen; Ting Lei; Lili Xin; Lingmei Zhou; Jinbo Cheng; Liqiang Qin; Shufen Han; Zhongxiao Wan (Journal of Physiology and Biochemistry, 2016)

Discovery of the New Plant Growth-Regulating Compound LYXLF2 Based on Manipulating the Halogenase in Amycolatopsis orientalis - Li Xu; Ting Han; Mei Ge; Li Zhu; XiuPing Qian (Current Microbiology, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Yi-Hsien Cheng; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Chun Ming How; Yi-Ting Tseng; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Dynamics of Dissolved Oxygen and the Affecting Factors in Sediment of Polluted Urban Rivers under Aeration Treatment - Bo Liu; Wen-lin Wang; Rui-ming Han; Ming Sheng; Lin-lin Ye; Xu Du; Xin-ting Wu; Guo-xiang Wang (Water, Air, & Soil Pollution, 2016)

Characterization and utilization of microsatellites in the Coffea canephora genome to assess genetic association between wild species in Kenya and cultivated coffee - Collins Ogutu; Ting Fang; Lin Yan; Lu Wang; Lifang Huang; Xiaoyang Wang; Baiquan Ma; Xianbao Deng; Albert Owiti; Aggrey Nyende; Yuepeng Han (Tree Genetics & Genomes, 2016)

The importance of GC-MS date processing and analysis strategies suitable for plant and environmental metabolomics - Kai P. Law; Ting-Li Han (Environmental Science and Pollution Research, 2016)

Echinocystic acid reduces reserpine-induced pain/depression dyad in mice - Shuo Li; Jing Han; Dong-sheng Wang; Bin Feng; Ya-ting Deng; Xin-shang Wang; Qi Yang; Ming-gao Zhao (Metabolic Brain Disease, 2016)

Arsenic speciation in rice and risk assessment of inorganic arsenic in Taiwan population - Hsiu-Ling Chen; Ching-Chang Lee; Winn-Jung Huang; Han-Ting Huang; Yi-Chen Wu; Ya-Chen Hsu; Yi-Ting Kao (Environmental Science and Pollution Research, 2016)

Construction of a high density linkage map and its application in the identification of QTLs for soluble sugar and organic acid components in apple - Baiquan Ma; Shuang Zhao; Benhong Wu; Dongmei Wang; Qian Peng; Albert Owiti; Ting Fang; Liao Liao; Collins Ogutu; Schuyler S. Korban; Shaohua Li; Yuepeng Han (Tree Genetics & Genomes, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Highly stable rice-straw-derived charcoal in 3700-year-old ancient paddy soil: evidence for an effective pathway toward carbon sequestration - Mengxiong Wu; Min Yang; Xingguo Han; Ting Zhong; Yunfei Zheng; Pin Ding; Weixiang Wu (Environmental Science and Pollution Research, 2016)

The diapycnal mixing in the upper Pacific estimated from GTSPP observations - Zeng’an Deng; Guanghao Wei; Ting Yu; Hongyu Wei; Linchong Kang; Luyao Han (Acta Oceanologica Sinica, 2016)

NK cell-based cancer immunotherapy: from basic biology to clinical application - Yang Li; Jie Yin; Ting Li; Shan Huang; Han Yan; JianMei Leavenworth; Xi Wang (Science China Life Sciences, 2015)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Impact of short-term climate variation and hydrology change on thermal structure and water quality of a canyon-shaped, stratified reservoir - Wei-Xing Ma; Ting-Lin Huang; Xuan Li; Hai-Han Zhang; Tuo Ju (Environmental Science and Pollution Research, 2015)

Candidate gene prediction via quantitative trait locus analysis of fruit shape index traits in apple - Ke Cao; Yuansheng Chang; Rui Sun; Fei Shen; Ting Wu; Yi Wang; Xinzhong Zhang; Zhenhai Han (Euphytica, 2015)

Role of lenticels and microcracks on susceptibility of apple fruit to Botryosphaeria dothidea - Yeqing Guan; Ruifeng Chang; Guojian Liu; Yi Wang; Ting Wu; Zhenhai Han; Xinzhong Zhang (European Journal of Plant Pathology, 2015)

The expression level of anthocyanidin synthase determines the anthocyanin content of crabapple (Malus sp.) petals - Jie Zhang; Zhen-yun Han; Ji Tian; Xi Zhang; Ting-ting Song; Yun-cong Yao (Acta Physiologiae Plantarum, 2015)

Development of a dot blot macroarray and its use in gene expression marker-assisted selection for iron deficiency tolerant apple rootstocks - Mingtao Zhu; Ran Wang; Penghao Kong; Xinzhong Zhang; Yi Wang; Ting Wu; Wensuo Jia; Zhenhai Han (Euphytica, 2015)

Denitrification and its product composition in typical Chinese paddy soils - Ting Lan; Yong Han; Zucong Cai (Biology and Fertility of Soils, 2015)

Polymorphonuclear Neutrophil in Brain Parenchyma After Experimental Intracerebral Hemorrhage - Xiurong Zhao; Guanghua Sun; Han Zhang; Shun-Ming Ting; Shen Song; Nicole Gonzales; Jaroslaw Aronowski (Translational Stroke Research, 2014)

The lose of juvenility elicits adventitious rooting recalcitrance in apple rootstocks - Zufei Xiao; Na Ji; Xinzhong Zhang; Yanzhen Zhang; Yi Wang; Ting Wu; Xuefeng Xu; Zhenhai Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Antidepressant-like effects of the phosphodiesterase-4 inhibitor etazolate and phosphodiesterase-5 inhibitor sildenafil via cyclic AMP or cyclic GMP signaling in mice - Chuang Wang; Jianrui Zhang; Yang Lu; Peipei Lin; Tonghe Pan; Xin Zhao; Aiming Liu; Qinwen Wang; Wenhua Zhou; Han-Ting Zhang (Metabolic Brain Disease, 2014)

Gibberella moniliformis AH13 with Antitumor Activity, an Endophytic Fungus Strain Producing Triolein Isolated from Adlay (Coix lacryma-jobi: Poaceae) - Min Jia; Qian-Liang Ming; Qiao-Yan Zhang; Yu Chen; Nuo Cheng; Wen-wen Wu; Ting Han; Lu-Ping Qin (Current Microbiology, 2014)

The toxicity of cerium nitrate to Elodea canadensis: subcellular distribution, chemical forms and physiological effects - Wei Yue Chu; San Juan Cai; Yong Yang Fu; Fei Fei Li; Ting Xu; Han Qiu; Qin Song Xu (Acta Physiologiae Plantarum, 2014)

Mice deficient in phosphodiesterase-4A display anxiogenic-like behavior - Rolf T. Hansen; Marco Conti; Han-Ting Zhang (Psychopharmacology, 2014)

Temperature dependence of gross N transformation rates in two Chinese paddy soils under aerobic condition - Ting Lan; Yong Han; Marco Roelcke; Rolf Nieder; Zucong Cai (Biology and Fertility of Soils, 2014)

Transcriptomic analysis demonstrates the early responses of local ethylene and redox signaling to low iron stress in Malus xiaojinensis - Shaojia Wang; Binbin Lu; Ting Wu; Xinzhong Zhang; Xuefeng Xu; Zhenhai Han; Yi Wang (Tree Genetics & Genomes, 2014)

Description of Niveispirillum fermenti gen. nov., sp. nov., isolated from a fermentor in Taiwan, transfer of Azospirillum irakense (1989) as Niveispirillum irakense comb. nov., and reclassification of Azospirillum amazonense (1983) as Nitrospirillum amazonense gen. nov - Shih-Yao Lin; Asif Hameed; Fo-Ting Shen; You-Cheng Liu; Yi-Han Hsu; Mariyam Shahina; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2014)

Reflection and Transmission of Plane Waves at a Water–Porous Sediment Interface with a Double-Porosity Substrate - Dan-Dan Lyu; Jin-Ting Wang; Feng Jin; Chu-Han Zhang (Transport in Porous Media, 2014)

Src contributes to IL6-induced vascular endothelial growth factor-C expression in lymphatic endothelial cells - Yu-Han Huang; Hung-Yu Yang; Ya-Fen Hsu; Pei-Ting Chiu; George Ou; Ming-Jen Hsu (Angiogenesis, 2014)

Identification and characterization of the microRNA transcriptome of a moth orchid Phalaenopsis aphrodite - Ya-Ting Chao; Chun-Lin Su; Wen-Han Jean; Wan-Chieh Chen; Yao-Chien Alex Chang; Ming-Che Shih (Plant Molecular Biology, 2014)

The role of Gracilaria lemaneiformis in eliminating the dissolved inorganic carbon released from calcification and respiration process of Chlamys farreri - Zeng Jie Jiang; Jian Guang Fang; Ting Ting Han; Yu Ze Mao; Jia Qi Li; Mei Rong Du (Journal of Applied Phycology, 2014)

Bioaccumulation, subcellular, and molecular localization and damage to physiology and ultrastructure in Nymphoides peltata (Gmel.) O. Kuntze exposed to yttrium - Yongyang Fu; Feifei Li; Ting Xu; Sanjuan Cai; Weiyue Chu; Han Qiu; Sha Sha; Guangyu Cheng; Qinsong Xu (Environmental Science and Pollution Research, 2014)

Functional Characterization of the agtABCD and agtSR Operons for 4-Aminobutyrate and 5-Aminovalerate Uptake and Regulation in Pseudomonas aeruginosa PAO1 - Han Ting Chou; Jeng-Yi Li; Chung-Dar Lu (Current Microbiology, 2014)

Processes leading to N2O and NO emissions from two different Chinese soils under different soil moisture contents - Ting Lan; Yong Han; Marco Roelcke; Rolf Nieder; Zucong Cai (Plant and Soil, 2013)

CTLA-4 polymorphisms and systemic lupus erythematosus (SLE): a meta-analysis - Jin-Xia Zhai; Li-Wei Zou; Zhao-Xiang Zhang; Wen-Jing Fan; Han-Yong Wang; Ting Liu; Zheng Ren; Rui-Xue Dai; Dongqing Ye (Molecular Biology Reports, 2013)

Advances in monoclonal antibody application in myocarditis - Li-na Han; Shuang He; Yu-tang Wang; Li-ming Yang; Si-yu Liu; Ting Zhang (Journal of Zhejiang University-SCIENCE B, 2013)

Secretory/releasing proteome-based identification of plasma biomarkers in HBV-associated hepatocellular carcinoma - Lei Yang; WeiQi Rong; Ting Xiao; Ying Zhang; Bin Xu; Yu Liu; LiMing Wang; Fan Wu; Jun Qi; XiuYing Zhao; HongXia Wang; NaiJun Han; et al. (Science China Life Sciences, 2013)

Simultaneous removal of cadmium and sulfamethoxazole from aqueous solution by rice straw biochar - Xuan Han; Cheng-feng Liang; Ting-qiang Li; Kai Wang; Hua-gang Huang; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Multi-angle Indicators System of Non-point Pollution Source Assessment in Rural Areas: A Case Study Near Taihu Lake - Lei Huang; Jie Ban; Yu Ting Han; Jie Yang; Jun Bi (Environmental Management, 2013)

Analysis of the genetic effects of prolactin gene polymorphisms on chicken egg production - Hui-Fang Li; Jing-Ting Shu; Yu-Feng Du; Yan-Ju Shan; Kuan-Wei Chen; Xue-Yu Zhang; Wei Han; Wen-Juan Xu (Molecular Biology Reports, 2013)

Geographic and Tissue Influences on Endophytic Fungal Communities of Taxus chinensis var. mairei in China - Lingshang Wu; Ting Han; Wenchao Li; Min Jia; Liming Xue; Khalid Rahman; Luping Qin (Current Microbiology, 2013)

Piperphentonamine (PPTA) attenuated cerebral ischemia-induced memory deficits via neuroprotection associated with anti-apoptotic activity - Juan Bin; Qian Wang; Ye-Ye Zhuo; Jiang-Ping Xu; Han-Ting Zhang (Metabolic Brain Disease, 2012)

Combretastatin A-4 derivatives: synthesis and evaluation of 2,4,5-triaryl-1H-imidazoles as potential agents against H1299 (non-small cell lung cancer cell) - Chih-Hua Tseng; Chi-Yi Li; Chien-Chih Chiu; Huei-Ting Hu; Chein-Hwa Han; Yeh-Long Chen; Cherng-Chyi Tzeng (Molecular Diversity, 2012)

Cloning and Characterization of MxVHA-c, a Vacuolar H+-ATPase Subunit C Gene Related to Fe Efficiency from Malus xiaojinensis - Qian Zhang; Yi Wang; Xin Zhong Zhang; Li Li Yin; Ting Wu; Xue Feng Xu; Wen Suo Jia; Zhen Hai Han (Plant Molecular Biology Reporter, 2012)

Meta-analysis of MCP-1 promoter −2518 A/G polymorphism and SLE susceptibility - Ting Liu; Jin-Xia Zhai; Han-Yong Wang; Xing-Hua Wang; Li-Wei Zou; Wen-jing Fan; Dong-Qing Ye (Molecular Biology Reports, 2012)

Cadmium accumulation in different pakchoi cultivars and screening for pollution-safe cultivars - Ying Chen; Ting-qiang Li; Xuan Han; Zhe-li Ding; Xiao-e Yang; Ye-fei Jin (Journal of Zhejiang University-SCIENCE B, 2012)

Comparing removal of trace organic compounds and assimilable organic carbon (AOC) at advanced and traditional water treatment plants - Jie-Chung Lou; Chung-Yi Lin; Jia-Yun Han; Wei-Biu Tseng; Kai-Lin Hsu; Ting-Wei Chang (Environmental Monitoring and Assessment, 2012)

The monitoring results of electromagnetic radiation of 110-kV high-voltage lines in one urban location in Chongqing P.R. China - Qi-zhong Qin; Yu Chen; Ting-ting Fu; Li Ding; Ling-li Han; Jian-chao Li (Environmental Monitoring and Assessment, 2012)

Effect of long-term administration of dietary β-1,3-glucan on growth, physiological, and immune responses in Litopenaeus vannamei (Boone, 1931) - Hong-Xia Zhao; Jun-Ming Cao; An-Li Wang; Zhen-Yu Du; Chao-Xia Ye; Yan-Hua Huang; Han-Bing Lan; Ting-Ting Zhou; Guo-Li Li (Aquaculture International, 2012)

The Reanalysis of Currents and Throughflow Volume Transport in the Taiwan Strait - Ting Yu; Zengan Deng; Guijun Han; Xinrong Wu; Hongli Fu; Kejian Wu (Marine Geodesy, 2012)

Genetic diversity of Centella asiatica in China analyzed by inter-simple sequence repeat (ISSR) markers: combination analysis with chemical diversity - Xiao-Gang Zhang; Ting Han; Zhi-Gao He; Qiao-Yan Zhang; Lei Zhang; Khalid Rahman; Lu-Ping Qin (Journal of Natural Medicines, 2012)

Inhibition of phosphodiesterase-4 decreases ethanol intake in mice - Wei Hu; Tina Lu; Alan Chen; Ying Huang; Rolf Hansen; L. Judson Chandler; Han-Ting Zhang (Psychopharmacology, 2011)

Identification of SACE_7040, a Member of TetR Family Related to the Morphological Differentiation of Saccharopolyspora erythraea - Shu Han; Ping Song; Ting Ren; Xunduan Huang; Cheng Cao; Buchang Zhang (Current Microbiology, 2011)

Variation and removal efficiency of assimilable organic carbon (AOC) in an advanced water treatment system - Jie-Chung Lou; Bi-Hsiang Chen; Ting-Wei Chang; Hung-Wen Yang; Jia-Yun Han (Environmental Monitoring and Assessment, 2011)

A regional ocean reanalysis system for coastal waters of China and adjacent seas - Guijun Han; Wei Li; Xuefeng Zhang; Dong Li; Zhongjie He; Xidong Wang; Xinrong Wu; Ting Yu; Jirui Ma (Advances in Atmospheric Sciences, 2011)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

Prevention of cerebral ischemia-induced memory deficits by inhibition of phosphodiesterase-4 in rats - Ling-Xia Li; Yu-Fang Cheng; Huan-Bing Lin; Chuang Wang; Jiang-Ping Xu; Han-Ting Zhang (Metabolic Brain Disease, 2011)

Comparative research of chemical constituents and bioactivities between petroleum ether extracts of the aerial part and the rhizome of Atractylodes macrocephala - Wei Peng; Ting Han; Wen-Bo Xin; Xiao-Gang Zhang; Qiao-Yan Zhang; Min Jia; Lu-Ping Qin (Medicinal Chemistry Research, 2011)

A recombinant peroxisome proliferator response element-driven luciferase assay for evaluation of potential environmental obesogens - Ya-Fen Wang; How-Ran Chao; Chia-Hsin Wu; Chu-Han Tseng; Ya-Ting Kuo; Tsui-Chun Tsou (Biotechnology Letters, 2010)

Several Important Issues in Salinity Quality Control of Argo Float - Ting Yu; Guijun Han; Changlong Guan; Zengan Deng (Marine Geodesy, 2010)

Inhibition of phosphodiesterase-4 reverses memory deficits produced by Aβ25–35 or Aβ1–40 peptide in rats - Yu-Fang Cheng; Chuang Wang; Huan-Bing Lin; Yun-Feng Li; Ying Huang; Jiang-Ping Xu; Han-Ting Zhang (Psychopharmacology, 2010)

Comparative features of colorectal and gastric cancers with microsatellite instability in Chinese patients - Yan-qin Huang; Ying Yuan; Wei-ting Ge; Han-guang Hu; Su-zhan Zhang; Shu Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Phenotypic and Genetic Characteristics of Macrolide and Lincosamide Resistant Ureaplasma urealyticum Isolated in Guangzhou, China - Chun Lu; Ting lu Ye; Guo xing Zhu; Pei ying Feng; Han Ma; Rong biao Lu; Wei Lai (Current Microbiology, 2010)

Genetic diversity and population structure of 10 Chinese indigenous egg-type duck breeds assessed by microsatellite polymorphism - Hui-Fang Li; Wei-Tao Song; Jing-Ting Shu; Kuan-Wei Chen; Wen-Qi Zhu; Wei Han; Wen-Juan Xu (Journal of Genetics, 2010)

Antidepressant properties of bioactive fractions from the extract of Crocus sativus L. - Yang Wang; Ting Han; Yu Zhu; Cheng-Jian Zheng; Qian-Liang Ming; Khalid Rahman; Lu-Ping Qin (Journal of Natural Medicines, 2010)

Memory deficits and neurochemical changes induced by C-reactive protein in rats: implication in Alzheimer’s disease - Huan-Bing Lin; Xue-Mei Yang; Tie-Jun Li; Yu-Fang Cheng; Han-Ting Zhang; Jiang-Ping Xu (Psychopharmacology, 2009)

Differential global genomic changes in rice root in response to low-, middle-, and high-osmotic stresses - Ting-chen Ma; Rong-jun Chen; Rong-rong Yu; Han-lai Zeng; Duan-pin Zhang (Acta Physiologiae Plantarum, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Nuclear translocation of dihydrofolate reductase is not a pre-requisite for DNA damage induced apoptosis - Ting-Ting Yuan; Ying Huang; Ci-Xiang Zhou; Yun Yu; Li-Shun Wang; Han-Yi Zhuang; Guo-Qiang Chen (Apoptosis, 2009)

An easy method to discover cell membrane antigen with atomic force microscopy - Wang Shu; Yang Ting Shu; Han Bao Shi; Liu Xiao Fei; Wang Lei; Qi Guan ming (Molecular Biology Reports, 2008)

Cognitive dysfunction induced by chronic administration of common cancer chemotherapeutics in rats - Gregory W. Konat; Michal Kraszpulski; Isaac James; Han-Ting Zhang; Jame Abraham (Metabolic Brain Disease, 2008)

Cytoplasmic male sterility with self-incompatibility, a novel approach to utilizing heterosis in rapeseed (Brassica napus L.) - Jin-xiong Shen; Han-zhong Wang; Ting-dong Fu; Bao-ming Tian (Euphytica, 2008)

Identification and characterization of piggyBac-like elements in the genome of domesticated silkworm, Bombyx mori - Han-Fu Xu; Qing-You Xia; Chun Liu; Ting-Cai Cheng; Ping Zhao; Jun Duan; Xing-Fu Zha; Shi-Ping Liu (Molecular Genetics and Genomics, 2006)

Antidepressant-like effects of PDE4 inhibitors mediated by the high-affinity rolipram binding state (HARBS) of the phosphodiesterase-4 enzyme (PDE4) in rats - Han-Ting Zhang; Yu Zhao; Ying Huang; Chengjun Deng; Allen T. Hopper; Michael De Vivo; Gregory M. Rose; James M. O’Donnell (Psychopharmacology, 2006)

Interaction between the antidepressant-like behavioral effects of beta adrenergic agonists and the cyclic AMP PDE inhibitor rolipram in rats - Han-Ting Zhang; Ying Huang; Kathleen Mishler; Sandra C. Roerig; James M. O'Donnell (Psychopharmacology, 2005)

FORMOSAT-3/COSMIC science mission update - Bor-Han Wu; Vicky Chu; Paul Chen; Thomas Ting (GPS Solutions, 2005)

Effects of the novel PDE4 inhibitors MEM1018 and MEM1091 on memory in the radial-arm maze and inhibitory avoidance tests in rats - Han-Ting Zhang; Ying Huang; Neesha U. Suvarna; Chengjun Deng; Alicia M. Crissman; Allen T. Hopper; Michael De Vivo; Gregory M. Rose; James M. O’Donnell (Psychopharmacology, 2005)

Antagonism of the antidepressant-like effects of clenbuterol by central administration of ?-adrenergic antagonists in rats - Han-Ting Zhang; Ying Huang; James M. O'Donnell (Psychopharmacology, 2003)

Comparison of the effects of isoproterenol administered into the hippocampus, frontal cortex, or amygdala on behavior of rats maintained by differential reinforcement of low response rate - Han-Ting Zhang; Sandra A. Frith; John Wilkins; James M. O'Donnell (Psychopharmacology, 2001)

A historical examination on land desertification in North China - Ting-zhen Yan; Xi-bo Chen; Guang-hui Han (Chinese Geographical Science, 2001)

Effects of rolipram on scopolamine-induced impairment of working and reference memory in the radial-arm maze tests in rats - Han-Ting Zhang; James M. O'Donnell (Psychopharmacology, 2000)